Offset printing method, and plate cleaning agent for on-machine image type offset printing plates.

JP7933777B2Active Publication Date: 2026-10-13FUJIFILM CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023551443
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-09-28
Filing Date
2022-09-22
Publication Date
2026-10-13
Estimated Expiration
2042-09-22

AI Technical Summary

Benefits of technology

【0015】 本開示の一実施形態によれば、キズ汚れ抑制性に優れる平版印刷方法を提供することができる。 また、本開示の他の一実施形態によれば、キズ汚れ抑制性に優れる機上現像型平版印刷版用版面洗浄剤を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007933777000061
    Figure 0007933777000061
  • Figure 0007933777000062
    Figure 0007933777000062
  • Figure 0007933777000063
    Figure 0007933777000063
Patent Text Reader

Abstract

Provided are: a lithographic printing method comprising a step for preparing a lithographic printing plate precursor having, on a support, an image recording layer containing an infrared absorber, a step for exposing the lithographic printing plate precursor in the form of an image, a step for at least developing a non-image part of the image recording layer by supplying at least dampening water to the exposed lithographic printing plate precursor, and a step for cleaning the plate surface of the developed lithographic printing plate precursor by using a plate surface detergent, wherein the plate surface detergent contains, with respect to the total mass of the plate surface detergent, 3.0 mass% or more of a solvent having a ClogP value of -1.5 to 2.5 (exclusive of -1.5); and a plate surface detergent for an on-press development-type lithographic printing plate containing, with respect to the total mass of the plate surface detergent, 3.0 mass% or more of a solvent having a ClogP value of -1.5 to 2.5 (exclusive of -1.5).
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This disclosure relates to a lithographic printing method and a plate cleaning agent for on-press lithographic printing plates. [Background technology]

[0002] Generally, a lithographic printing plate consists of an oil-based image area that receives ink during the printing process and a hydrophilic non-image area that receives dampening solution. Lithographic printing utilizes the property that water and oil-based inks repel each other, by designating the oil-based image area of ​​the lithographic printing plate as the ink-receiving area and the hydrophilic non-image area as the dampening solution-receiving area (non-ink-receiving area). This creates a difference in ink adhesion on the surface of the lithographic printing plate, allowing ink to adhere only to the image area, and then transferring the ink to a substrate such as paper to print. To produce these lithographic printing plates, conventionally, lithographic printing plates (PS plates) made by providing an oil-lipophilic photosensitive resin layer (image recording layer) on a hydrophilic support have been widely used. Typically, the lithographic printing plate is produced by exposing the lithographic printing plate to an original image such as lithographic film, leaving the image portion of the image recording layer intact, and dissolving and removing the other unnecessary parts of the image recording layer with an alkaline developer or organic solvent, thereby exposing the surface of the hydrophilic support and forming the non-image portion.

[0003] Furthermore, with growing concern for the global environment, environmental issues related to wastewater from wet processing such as developing have come into focus. In response to the environmental challenges mentioned above, efforts are being made to simplify or eliminate the processing of developing or platemaking. One such simplified method is called "on-press development." In this method, after exposing the lithographic printing plate, conventional developing is not performed; instead, the plate is mounted directly onto the printing press, and the removal of unwanted parts of the image recording layer is carried out in the early stages of the normal printing process. In this disclosure, a lithographic printing plate master that can be used for such on-press development is referred to as an "on-press development type lithographic printing plate master," and a lithographic printing plate obtained by on-press development is referred to as an "on-press development type lithographic printing plate."

[0004] Conventional emulsifying plate cleaning agents for lithographic printing plates include, for example, those described in Patent Document 1. Patent Document 1 describes an emulsified plate cleaning agent for lithographic printing plates used for lithographic printing plates obtained by manufacturing plates from a photopolymerizable lithographic printing plate master plate provided with an oxygen-barrier protective layer, characterized in that the total cation content of the salt contained in the plate cleaning agent, based on the total mass, is 0.5% by mass or more, and based on the mass of the total cations, 30% by mass or more is at least one selected from potassium, cesium, and rubidium.

[0005] Examples of conventional dampening solutions for lithographic printing include those described in Patent Document 2. Patent Document 2 describes a dampening solution composition for lithographic printing, characterized by containing an acyclic hydrocarbon compound having two OH groups and a total of 9 carbon atoms, and a water-soluble copolymer having at least one selected from phosphorus oxyacid groups and carboxyl groups, and at least one selected from sulfonic acid groups and betaine structures in its side chain.

[0006] Patent Document 1: Japanese Unexamined Patent Publication No. 2012-171326 Patent Document 2: Japanese Unexamined Patent Publication No. 2012-30548 [Overview of the project] [Problems that the invention aims to solve]

[0007] One embodiment of this disclosure aims to solve the problem of providing a lithographic printing method that is excellent in suppressing scratches and stains. Another embodiment of the present disclosure aims to solve the problem of providing a plate surface cleaning agent for on-press development type lithographic printing plates that is excellent in suppressing scratches and stains. [Means for solving the problem]

[0008] The means for solving the above problems include the following embodiments. <1> A lithographic printing method comprising the steps of: preparing a lithographic printing plate having an image recording layer containing an infrared absorbent on a support; exposing the lithographic printing plate to an image; developing at least the non-image portion of the image recording layer by supplying at least dampening water to the exposed lithographic printing plate; and cleaning the plate surface of the developed lithographic printing plate using a plate cleaning agent, wherein the plate cleaning agent contains 3.0% by mass or more of a solvent having a ClogP value greater than -1.5 and 2.5 or less, based on the total mass of the plate cleaning agent. <2> The above-described developing process involves mounting the exposed lithographic printing plate onto a printing press and supplying at least dampening solution on the printing press to develop at least the non-image portion of the image recording layer. <1> The lithographic printing method described above. <3> Solvents with a ClogP value greater than -1.5 and less than or equal to 2.5 contain the compound represented by the following formula (A). <1> or <2> The lithographic printing method described above.

[0009] [ka]

[0010] In formula (A), R1 represents a hydrogen atom, a linear alkyl group having 1 to 5 carbon atoms, or a branched alkyl group having 3 to 5 carbon atoms; R2 independently represents a hydrogen atom or a methyl group; and m represents an integer from 1 to 5.

[0011] <4> The above-mentioned plate cleaning agent further contains at least one selected from the group consisting of organic acids and their salts. <1> ~ <3> A lithographic printing method described in any one of the following. <5> The total content of the above-mentioned organic acids and their salts is 0.002 moles or more in terms of organic acids per 100g of the total amount of the plate cleaning agent. <4> The lithographic printing method described above. <6> The above-mentioned plate cleaning agent further contains at least one selected from the group consisting of inorganic acids and their salts. <1> ~ <5> A lithographic printing method described in any one of the following. <7> The total content of the above-mentioned inorganic acids and their salts is 0.002 moles or more in terms of inorganic acid per 100g of the total amount of the plate cleaning agent. <6> The lithographic printing method described above. <8> The above-mentioned plate cleaning agent further contains water and is a single-phase aqueous solution. <1> ~ <7> A lithographic printing method described in any one of the following. <9> The water content mentioned above is 90% by mass or less of the total mass of the plate cleaning agent. <8> The lithographic printing method described above. <10> The process further includes treating the printing plate surface with a two-phase solution containing water and a hydrocarbon solvent before, during, or after the above cleaning process. <1> ~ <9> A lithographic printing method described in any one of the following. <11> The cleaning agent contains at least 3.0% by mass of a solvent with a ClogP value greater than -1.5 and 2.5 or less, relative to the total mass of the plate surface cleaning agent. A plate cleaning agent for on-press developing type lithographic printing plates. <12> Solvents with a ClogP value greater than -1.5 and less than or equal to 2.5 contain the compound represented by the following formula (A). <11> A plate cleaning agent for on-press type lithographic printing plates as described above.

[0012] [ka]

[0013] In formula (A), R1 represents a hydrogen atom, a linear alkyl group having 1 to 5 carbon atoms, or a branched alkyl group having 3 to 5 carbon atoms; R2 independently represents a hydrogen atom or a methyl group; and m represents an integer from 1 to 5.

[0014] <13> The above-mentioned plate cleaning agent further contains at least one selected from the group consisting of organic acids and their salts. <11> or <12> A plate cleaning agent for on-press type lithographic printing plates as described above. <14> The total content of the above-mentioned organic acids and their salts is 0.002 moles or more in terms of organic acids per 100g of the total amount of the plate cleaning agent. <13> A plate cleaning agent for on-press type lithographic printing plates as described above. <15> The above-mentioned plate cleaning agent further contains at least one selected from the group consisting of inorganic acids and their salts. <11> ~ <14> A plate cleaning agent for on-press developing type lithographic printing plates, as described in any one of the following. <16> The total content of the above-mentioned inorganic acids and their salts is 0.002 moles or more in terms of inorganic acid per 100g of the total amount of the plate cleaning agent. <15> A plate cleaning agent for on-press type lithographic printing plates as described above. <17> The above-mentioned plate cleaning agent further contains water and is a single-phase aqueous solution. <11> ~ <16> A plate cleaning agent for on-press developing type lithographic printing plates, as described in any one of the following. <18> The water content mentioned above is 90% by mass or less of the total mass of the plate cleaning agent. <17> A plate cleaning agent for on-press type lithographic printing plates as described above. [Effects of the Invention]

[0015] According to one embodiment of this disclosure, a lithographic printing method with excellent scratch and stain resistance can be provided. Furthermore, according to another embodiment of the present disclosure, a plate surface cleaning agent for on-press developing type lithographic printing plates that exhibits excellent scratch and stain suppression properties can be provided. [Brief explanation of the drawing]

[0016] [Figure 1] This is a schematic cross-sectional view of one embodiment of an aluminum support preferably used in the present disclosure. [Figure 2] This is a schematic cross-sectional view of one embodiment of an aluminum support having an anodized coating. [Figure 3] This is a schematic diagram of an anodizing apparatus used in the anodizing process in the manufacturing method of an aluminum support having an anodized coating. [Figure 4] This graph shows an example of an alternating waveform current waveform diagram used in the electrochemical roughening treatment in the manufacturing method of an aluminum support having an anodized coating. [Figure 5] This is a side view showing an example of a radial cell used in an electrochemical roughening treatment using alternating current in a method for manufacturing an aluminum support having an anodized film. [Modes for carrying out the invention]

[0017] The contents of this disclosure are described in detail below. The descriptions of the constituent elements described below may be based on representative embodiments of this disclosure, but this disclosure is not limited to such embodiments. In this specification, the "~" symbol indicating a numerical range is used to mean that the numbers before and after it are included as the lower and upper limits, respectively. Furthermore, in the notation of groups (atomic groups) in this specification, the notation that does not specify whether they are substituted or unsubstituted includes both those with and without substituents. For example, "alkyl group" includes not only alkyl groups without substituents (unsubstituted alkyl groups) but also alkyl groups with substituents (substituted alkyl groups). In this specification, "(meth)acrylic" is a term used to encompass both acrylic and methacrylic, and "(meth)acryloyl" is a term used to encompass both acryloyl and methacryloyl. Furthermore, the term "process" in this specification includes not only independent processes but also processes that cannot be clearly distinguished from other processes, as long as their intended purpose is achieved. In addition, in this disclosure, "mass%" and "weight%" are synonymous, and "parts by mass" and "parts by weight" are synonymous. Unless otherwise specified, each component in the composition or each structural unit in the polymer in this disclosure may be included alone or in combination of two or more types. Furthermore, in this disclosure, the amount of each component in the composition or each constituent unit in the polymer means the total amount of the multiple substances or constituent units present in the composition or polymer, unless otherwise specified, if there are multiple substances or constituent units corresponding to each component or constituent unit in the polymer. Furthermore, in this disclosure, a combination of two or more preferred embodiments is a more preferred embodiment. Furthermore, unless otherwise specified, the weight-average molecular weight (Mw) and number-average molecular weight (Mn) in this disclosure are molecular weights obtained by detecting the molecules using a differential refractometer with THF (tetrahydrofuran) as the solvent, using a gel permeation chromatography (GPC) analyzer with TSKgel GMHxL, TSKgel G4000HxL, or TSKgel G2000HxL columns (all product names of Tosoh Corporation), and then converting them using polystyrene as the standard substance. In this disclosure, the term "lithographic printing plate" includes not only the lithographic printing plate but also the sacrificial plate. Furthermore, the term "lithographic printing plate" includes not only the lithographic printing plate produced from the lithographic printing plate through operations such as exposure and development as necessary, but also the sacrificial plate. In the case of a sacrificial plate, exposure and development operations are not necessarily required. A sacrificial plate is, for example, a lithographic printing plate used to attach to a printing cylinder that is not being used when printing some pages in single color or two colors in color newspaper printing. Furthermore, in this disclosure, the asterisk (*) in the chemical structural formula indicates a bonding position with other structures. The details of this disclosure are described below.

[0018] (lithographic printing method) The lithographic printing method according to this disclosure includes the steps of: preparing a lithographic printing plate having an image recording layer containing an infrared absorbent on a support (hereinafter also referred to as the "preparation step"); exposing the lithographic printing plate to an image (hereinafter also referred to as the "exposure step"); developing at least the non-image portion of the image recording layer by supplying at least dampening water to the exposed lithographic printing plate (hereinafter also referred to as the "tree development step"); and cleaning the plate surface of the developed lithographic printing plate using a plate surface cleaning agent (hereinafter also referred to as the "cleaning step"), wherein the plate surface cleaning agent contains 3.0% by mass or more of a solvent having a ClogP value greater than -1.5 and 2.5 or less, based on the total mass of the plate surface cleaning agent.

[0019] Furthermore, it is preferable that the above-mentioned lithographic printing plate is a negative-type lithographic printing plate.

[0020] In conventional lithographic printing methods, the image recording layer often adheres to scratches formed on the support of the lithographic printing plate during on-press development. This leads to a problem where ink adheres to the lipophilic image recording layer attached to the scratches, resulting in scratch-like ink stains (scratch stains). Through diligent research, the inventors have found that by cleaning the printing plate after on-press development with a plate cleaning agent containing 3.0% or more by mass of a solvent with a ClogP value greater than -1.5 and 2.5 or less, relative to the total mass of the plate cleaning agent, the image recording layer that has penetrated deep into scratches, which could not be completely removed by conventional cleaning methods, can be easily removed, resulting in excellent scratch stain suppression.

[0021] Furthermore, the lithographic printing method relating to this disclosure, as described above, also excels at suppressing smudges that occur when printing is temporarily paused, so-called stop smudges.

[0022] The details of each constituent element in the lithographic printing method relating to this disclosure are described below.

[0023] <Preparation process> The lithographic printing method relating to this disclosure includes the step of preparing a lithographic printing plate master having an image recording layer containing an infrared absorbent on a support. The lithographic printing plates used in this disclosure are press-developed lithographic printing plates, and known plates may be used. A lithographic printing plate suitable for use in this disclosure will be described in detail later.

[0024] <Exposure process> The lithographic printing method relating to this disclosure includes an exposure step of exposing the lithographic printing plate to an image. The lithographic printing plates used in this disclosure are preferably exposed to laser light through a transparent original image having line images, halftone images, etc., or exposed to an image-like state by laser light scanning using digital data. The wavelength of the light source is preferably 750 nm to 1,400 nm. Suitable light sources with a wavelength of 750 nm to 1,400 nm include solid-state lasers and semiconductor lasers that emit infrared light. For infrared lasers, the output is preferably 100 mW or more, the exposure time per pixel is preferably 20 microseconds or less, and the irradiation energy is preferably 10 mJ / cm². 2 ~300 mJ / cm 2 It is preferable that this be the case. Furthermore, it is preferable to use a multi-beam laser device in order to shorten the exposure time. The exposure mechanism may be any of the following: an internal drum system, an external drum system, or a flatbed system. Image exposure can be performed using conventional methods, such as with a platesetter. In the case of on-press development, the lithographic printing plate can be mounted on the printing press, and then the image exposure may be performed on the press.

[0025] <On-press development process> The lithographic printing method according to this disclosure preferably includes an on-press development step of developing at least the non-image portion of the image recording layer by supplying at least dampening water to the exposed lithographic printing plate. Furthermore, the on-press development process is preferably a process in which the exposed lithographic printing plate is attached to a printing press and at least dampening water is supplied on the printing press to develop at least the non-image portion of the image recording layer. The onboard film processing method is described below.

[0026] [On-press development method] In the on-press development method, it is preferable that the exposed lithographic printing plate is supplied with oil-based ink and water-based components on the printing press, and the image recording layer in the non-image areas is removed to produce the lithographic printing plate. In other words, when a lithographic printing plate is exposed to image light and then mounted directly onto a printing press without any development process, or when the lithographic printing plate is mounted on a printing press, exposed to image light on the press, and then printed with oil-based ink and aqueous components, in the early stages of printing, the image recording layer in the non-image areas is dissolved or dispersed and removed by either or both of the supplied oil-based ink and aqueous components, exposing a hydrophilic surface in those areas. On the other hand, in the image areas, the image recording layer forms an oil-based ink receiving area with a lipophilic surface. Initially, either oil-based ink or aqueous components may be supplied to the plate surface, but it is preferable to supply oil-based ink first to prevent contamination of the aqueous components by the components of the removed image recording layer. In this way, the lithographic printing plate is developed on the printing press and used directly for printing many copies. As the oil-based ink and aqueous components, ordinary lithographic printing ink and dampening solution are preferably used.

[0027] For the laser used to image-expose the lithographic printing plate master used in the above disclosure, the wavelength of the light source is preferably 300 nm to 450 nm or 750 nm to 1,400 nm. In the case of a 300 nm to 450 nm light source, a lithographic printing plate master containing an absorption maximum in this wavelength region in the image recording layer is preferably used, and for a 750 nm to 1,400 nm light source, the above-mentioned type is preferably used. A semiconductor laser is preferred as the light source with a wavelength of 300 nm to 450 nm.

[0028] <Washing process> The lithographic printing method relating to this disclosure includes a cleaning step of cleaning the surface of the developed lithographic printing plate using a plate cleaning agent. A plate cleaning agent preferably used in this disclosure will be described in detail later. The cleaning method in the cleaning process may be any method of bringing the plate surface cleaning agent into contact with the plate surface of the developed lithographic printing plate. Examples include applying or soaking the plate surface cleaning agent into a cleaning material such as a cloth, nonwoven fabric, paper, or sponge, and wiping or rubbing the plate surface of the developed lithographic printing plate; immersing at least the plate surface of the developed lithographic printing plate in the plate surface cleaning agent; or applying the plate surface cleaning agent to the plate surface of the developed lithographic printing plate. Known methods can be used to apply the plate cleaning agent, such as the coating method, shower method, and dipping method. There are no particular restrictions on the washing temperature and washing time during the washing process; they should be selected as appropriate as needed. Furthermore, there are no particular restrictions on the amount of plate cleaning agent used in the cleaning process; it should be selected as needed.

[0029] <Printing process> The lithographic printing method according to this disclosure preferably includes a printing step of supplying printing ink to a lithographic printing plate and printing on a recording medium. There are no particular restrictions on the printing ink, and various known inks can be used as desired. Oil-based inks or UV-curing inks are preferred as printing inks. Furthermore, dampening solution may be supplied during the printing process as needed. Furthermore, the above printing process may be carried out continuously with the above on-press development process without stopping the printing press. There are no particular restrictions on the recording medium; any known recording medium can be used as desired.

[0030] In the lithographic printing method according to this disclosure, the entire surface of the lithographic printing plate may be heated before exposure, during exposure, and between exposure and development, if necessary. Such heating promotes the image formation reaction in the image recording layer, which can result in advantages such as improved sensitivity and print durability, and stabilized sensitivity. Pre-development heating is preferably carried out under mild conditions of 150°C or less. This configuration prevents problems such as hardening of non-image areas. For post-development heating, very strong conditions are preferred, preferably in the range of 100°C to 500°C. This range provides sufficient image enhancement and suppresses problems such as deterioration of the support and thermal decomposition of the image area.

[0031] <Two-phase solution processing process> The lithographic printing method according to this disclosure preferably further includes a step of treating the printing plate surface with a two-phase solution containing water and a hydrocarbon solvent (also referred to as the "two-phase solution treatment step") before, during, or simultaneously with the cleaning step, from the viewpoint of preventing scratches and stains and preventing stop stains. In this disclosure, performing the two-phase solution treatment step simultaneously with the cleaning step means performing the cleaning step on a portion of the printing plate surface of one developed lithographic printing plate while performing the two-phase solution treatment step on another portion of the printing plate surface. In this disclosure, a two-phase solution refers to a liquid having an aqueous phase and a hydrocarbon solvent phase as micelles or emulsions. Examples of hydrocarbon solvents include aliphatic hydrocarbon solvents, aromatic hydrocarbon solvents, and squalane, while petroleum fractions and mineral spirits are also suitably used. The above two-phase solution may be either a water-in-oil type or an oil-in-water type, but an oil-in-water type is preferred. The above two-phase solution preferably contains a surfactant. Suitable surfactants include those described in the section on plate cleaning agents, which will be discussed later. Furthermore, the above two-phase solution may contain other components. Suitable other components include, for example, the components contained in the plate cleaning agent described later. In the two-phase solution treatment step, the plate surface treatment method using a two-phase solution is not particularly limited, and a known method can be used. A method of bringing the two-phase solution into contact with the plate surface of the lithographic printing plate precursor described above is preferred, and suitable examples of the contacting method include the method of bringing the plate surface cleaning agent into contact in the cleaning step described above. The treatment temperature and treatment time in the two-phase solution treatment step are not particularly limited, and may be appropriately selected as necessary. Further, the amount of the two-phase solution used in the two-phase solution treatment step is also not particularly limited, and may be appropriately selected as necessary.

[0032] <Other Steps> The lithographic printing method according to the present disclosure may include known steps other than those described above. Examples of other steps include a step of interrupting printing, a step of resuming printing, and the like.

[0033] <Plate Surface Cleaning Agent> The lithographic printing method according to the present disclosure includes a step of cleaning the plate surface of the developed lithographic printing plate precursor using a plate surface cleaning agent, and the plate surface cleaning agent contains 3.0% by mass or more of a solvent having a ClogP value of greater than -1.5 and 2.5 or less, relative to the total mass of the plate surface cleaning agent.

[0034] <<Solvent having a ClogP value of greater than -1.5 and 2.5 or less>> The plate surface cleaning agent contains 3.0% by mass or more of a solvent having a ClogP value of greater than -1.5 and 2.5 or less, relative to the total mass of the plate surface cleaning agent. From the viewpoints of scratch stain suppression property and stop stain suppression property, the content is preferably 3.0% by mass to 99.5% by mass, more preferably 5.0% by mass to 80% by mass, and particularly preferably 25% by mass to 75% by mass. Furthermore, if the above-mentioned plate cleaning agent contains water as described later, the above-mentioned plate cleaning agent preferably contains 15% to 99.5% by mass, more preferably 50% to 99% by mass, even more preferably 70% to 98% by mass, and particularly preferably 80% to 95% by mass, of the total mass of the plate cleaning agent other than water, of a solvent having a ClogP value greater than -1.5 and 2.5 or less, from the viewpoint of scratch stain suppression and stop stain suppression. Furthermore, the above-mentioned plate surface cleaning agent may contain one solvent with a ClogP value greater than -1.5 and 2.5 or less, or it may contain two or more solvents. However, from the viewpoint of suppressing scratches and stains and suppressing stop stains, it is preferable to contain two or more solvents, more preferably two or three solvents, and particularly preferable to contain two solvents.

[0035] Of the solvents with a ClogP value greater than -1.5 and less than or equal to 2.5, from the viewpoint of scratch and stain suppression and stop stain suppression, solvents with a ClogP value of -1.3 to 2.0 are preferred, and solvents with a ClogP value of 0.4 to 1.2 are more preferred.

[0036] In this disclosure, the ClogP value is a value used to calculate the common logarithm logP of the partition coefficient P between n-octanol and water. The ClogP values ​​are calculated using the method described in "Substituent Constants for Correlation Analysis in Chemistry and Biology," and unless otherwise specified, the predicted values ​​from Chem Draw Professional ver. 20.1.1.125 (PerkinElmer Informatics) are listed.

[0037] The solvents with a ClogP value greater than -1.5 and 2.5 or less are preferably compounds having a hydroxyl group, more preferably compounds having a hydroxyl group and an ether bond, even more preferably compounds having one hydroxyl group and one or more ether bonds, and particularly preferably compounds having one hydroxyl group and one or two ether bonds. When a solvent with a ClogP value greater than -1.5 and 2.5 or less has hydroxyl groups, the number of hydroxyl groups is preferably 1 to 3, more preferably 1 or 2, and particularly preferably 1, from the viewpoint of scratch stain suppression and stop stain suppression. Furthermore, if the solvent having a ClogP value greater than -1.5 and 2.5 or less has ether bonds, the number of ether bonds is preferably 1 to 10, more preferably 1 to 4, and particularly preferably 1 or 2, from the viewpoint of scratch stain suppression and stop stain suppression.

[0038] For solvents with a ClogP value greater than -1.5 and 2.5 or less, the number of carbon atoms is preferably 3 to 20, more preferably 4 to 16, even more preferably 5 to 12, and particularly preferably 6 to 8, from the viewpoint of scratch and stain suppression and stop stain suppression.

[0039] Solvents with a ClogP value greater than -1.5 and 2.5 or less preferably contain a compound represented by the following formula (A) from the viewpoint of scratch stain suppression and stop stain suppression.

[0040] [ka]

[0041] In formula (A), R1 represents a hydrogen atom, a linear alkyl group having 1 to 5 carbon atoms, or a branched alkyl group having 3 to 5 carbon atoms; R2 independently represents a hydrogen atom or a methyl group; and m represents an integer from 1 to 5.

[0042] In formula (A), R1 is preferably a linear alkyl group having 1 to 5 carbon atoms or a branched alkyl group having 3 to 5 carbon atoms, more preferably a linear alkyl group having 3 to 5 carbon atoms or a branched alkyl group having 3 to 5 carbon atoms, even more preferably a linear alkyl group having 3 or 4 carbon atoms or a branched alkyl group having 3 or 4 carbon atoms, and is particularly preferably an n-butyl group, an isobutyl group, an s-butyl group, or a t-butyl group. In formula (A), it is preferable that R2 consists entirely of hydrogen atoms or entirely of methyl groups. In formula (A), m is preferably an integer from 1 to 4, more preferably an integer from 1 to 3, even more preferably 1 or 2, and particularly preferably 1, from the viewpoint of scratch and stain suppression and stop stain suppression.

[0043] Specific examples of solvents with a ClogP value greater than -1.5 and less than or equal to 2.5 include, for example, propylene glycol-n-butyl ether (BFG, ClogP value 1.1), ethylene glycol mono-t-butyl ether (ETB, ClogP value 0.49), diethylene glycol-n-butyl ether (ClogP value 0.67), ethylene glycol mono-n-butyl ether (ClogP value 0.84), propylene glycol-t-butyl ether (ClogP value 0.89), Solfit (ClogP value 0.42), diethylene glycol (ClogP value -1.3), and 1-hexanol (ClogP value 1.9). Furthermore, as a solvent having a ClogP value greater than -1.5 and 2.5 or less, the compound described in paragraph 0037 of Japanese Patent Application Publication No. 2012-30548 can also be suitably used.

[0044] <<Wed>> The plate cleaning agent used in this disclosure does not necessarily contain water, but it is preferable to contain water from the viewpoint of suppressing deterioration of the plate cleaning agent due to drying, and it is more preferable that the water content is 90% by mass or less of the total mass of the plate cleaning agent. Furthermore, from the viewpoint of preventing scratches and stains, the above-mentioned plate cleaning agent is preferably a single-phase aqueous solution that also contains water. In this disclosure, a "single-phase aqueous solution" of a printing plate cleaning agent refers to a solvent and water whose ClogP value is greater than -1.5 and 2.5 or less, in which case the solvent and water do not separate into phases and are dissolved in each other. There are no particular restrictions on the type of water used; tap water, well water, distilled water, deionized water, pure water, etc., can be used. Among these, distilled water, deionized water, or pure water is preferred. The water content consists of the solvent, which has a ClogP value greater than -1.5 and 2.5 or less, and the remainder of the components described later, but is preferably 90% by mass or less, more preferably 80% by mass, and particularly preferably 15% to 80% by mass, relative to the total mass of the plate cleaning agent.

[0045] <<Other Solvents>> The plate cleaning agent used in this disclosure may contain a solvent other than water and a solvent with a ClogP value greater than -1.5 and 2.5 or less, but it is preferable that the solvent does not contain any solvent other than the solvent with a ClogP value greater than -1.5 and 2.5 or less. Other solvents are preferably organic solvents, and known organic solvents can be used. Furthermore, the other solvents are preferably compounds that are liquid at 1 atmosphere and 20°C. Furthermore, the other solvents preferably contain compounds with a boiling point of 150°C or higher, more preferably contain compounds with a boiling point of 150°C to 300°C, even more preferably contain compounds with a boiling point of 150°C to 250°C, and particularly preferably contain compounds with a boiling point of 150°C to 200°C. Other solvents include, for example, ketones, esters, and amides. Examples of ketones include methyl-n-amyl ketone, methyl-n-hexyl ketone, ethyl-n-butyl ketone, di-n-propyl ketone, diacetone alcohol, and cyclohexanone. Esters include benzoic acid esters such as n-amyl acetate, isoamyl acetate, methylisoamyl acetate, methoxybutyl acetate, benzyl acetate, ethyl lactate, butyl lactate, n-amyl lactate, methyl benzoate, ethyl benzoate and benzyl benzoate, dimethyl phthalate, diethyl phthalate, dibutyl phthalate, di-2-ethylhexyl phthalate, dioctyl phthalate, dinonyl phthalate, didecyl phthalate, dilauryl phthalate, and phthalate. Examples include phthalate diesters such as butylbenzyl acid, aliphatic dibasic acid esters such as dioctyl adipate, butyl glycol adipate, dioctyl azelate, dibutyl sebacate, di(2-ethylhexyl) sebacate, and dioctyl sebacate, epoxidized triglycerides such as epoxidized soybean oil, and phosphate esters such as tricresyl phosphate, trioctyl phosphate, and trichlorethyl phosphate. Examples of amides include N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, and N-butyl-2-pyrrolidone.

[0046] The plate cleaning agent used in this disclosure may contain one or more other solvents. If the plate cleaning agent used in this disclosure contains other solvents, the content of the other solvents is preferably 10% by mass or less, and more preferably 1% by mass or less, based on the total mass of the plate cleaning agent.

[0047] <<Acidic compounds (pH adjusters)>> The plate cleaning agent used in this disclosure preferably contains an acidic compound, from the viewpoint of adjusting the pH to an acidic range. Examples of acidic compounds include organic acids, inorganic acids, and their salts. Examples of organic acids include citric acid, maleic acid, fumaric acid, succinic acid, adipic acid, glutaric acid, ascorbic acid, malic acid, tartaric acid, propionic acid, lactic acid, acetic acid, glycolic acid, gluconic acid, oxalic acid, malonic acid, levulinic acid, sulfanilic acid, p-toluenesulfonic acid, phytic acid, and organic phosphonic acids. Examples of inorganic acids include phosphoric acid, nitric acid, sulfuric acid, and polyphosphates (such as hexametaphosphate). Furthermore, alkali metal salts, alkaline earth metal salts, ammonium salts, or organic amine salts of these organic or inorganic acids are also suitably used.

[0048] The plate cleaning agent used in this disclosure may contain one acidic compound alone or two or more acidic compounds. The content of the acidic compound is preferably 0.1% to 20% by mass relative to the total mass of the plate cleaning agent.

[0049] <<Basic compounds (pH adjusters)>> Furthermore, the plate cleaning agent used in this disclosure may contain basic compounds such as alkali metal hydroxides, alkali metal phosphates, alkali metal carbonates, and silicates from the viewpoint of pH adjustment. For example, it can be used as a dampening solution in a neutral to alkaline range of around pH 7 to 11.

[0050] The plate cleaning agent used in this disclosure may contain one basic compound alone or two or more basic compounds. The content of the basic compound is preferably 0.1% to 20% by mass relative to the total mass of the plate cleaning agent.

[0051] From the viewpoint of preventing scratches and stains, the above-mentioned printing plate cleaning agent preferably further contains an organic acid as an acidic compound, and at least one selected from the group consisting of salts of organic acids as an acidic compound or basic compound. The plate cleaning agent used in this disclosure may contain one organic acid or a salt thereof, or it may contain two or more organic acids. The total content of the above-mentioned organic acids and their salts is preferably 0.002 moles or more, more preferably 0.005 moles or more, and particularly preferably 0.007 moles to 0.02 moles, in terms of organic acid equivalent, per 100g of the total amount of the plate cleaning agent, from the viewpoint of scratch and stain suppression and stop stain suppression. Furthermore, from the viewpoint of preventing scratches and stains and preventing staining, the above-mentioned plate surface cleaning agent preferably further contains at least one selected from the group consisting of an inorganic acid as an acidic compound, and a salt of an inorganic acid as an acidic compound or basic compound. The plate cleaning agent used in this disclosure may contain one inorganic acid and / or a salt thereof, or two or more. The total content of the above-mentioned inorganic acid and its salts is preferably 0.002 moles or more, more preferably 0.005 moles or more, and particularly preferably 0.012 moles to 0.05 moles, in terms of inorganic acid equivalent, per 100g of the total amount of the plate cleaning agent, from the viewpoint of scratch and stain suppression and stop stain suppression.

[0052] <<Water-soluble polymer compounds>> The plate cleaning agent used in this disclosure preferably contains a water-soluble polymer compound from the viewpoint of suppressing contamination of non-image areas. Specific examples of water-soluble polymer compounds include natural products and their derivatives of natural products such as gum arabic, starch derivatives (e.g., dextrin, enzymatically hydrolyzed dextrin, hydroxypropylated enzymatically hydrolyzed dextrin, carboxymethylated starch, phosphate starch, octenyl succinate starch, etc.), alginates, and cellulose derivatives (e.g., carboxymethylcellulose, carboxyethylcellulose, hydroxyethylcellulose, methylcellulose, hydroxypropylcellulose, hydroxypropylmethylcellulose, and their glyoxal-modified derivatives, etc.), as well as synthetic products such as polyvinyl alcohol and its derivatives, polyvinylpyrrolidone, polyacrylamide and its copolymers, polyacrylic acid and its copolymers, vinyl methyl ether / maleic anhydride copolymers, and vinyl acetate / maleic anhydride copolymers. Among the water-soluble polymer compounds mentioned above, at least one compound selected from the group consisting of hydroxypropylcellulose, hydroxypropylmethylcellulose, and polyvinylpyrrolidone is particularly preferred.

[0053] The plate cleaning agent used in this disclosure may contain one water-soluble polymer compound alone or two or more water-soluble polymer compounds. The content of the water-soluble polymer compound is preferably 0.001% to 20% by mass, more preferably 0.01% to 10% by mass, and particularly preferably 0.03% to 10% by mass, based on the total mass of the plate cleaning agent.

[0054] <<Chelating Compounds>> The plate cleaning agent used in this disclosure preferably contains a chelate compound. When the plate cleaning agent used in this disclosure is diluted with tap water, well water, etc., and used as dampening water, the inclusion of a chelate compound suppresses the effect of calcium ions and other substances contained in the diluted tap water or well water on printing, thereby suppressing soiling of printed materials. Examples of chelating compounds include ethylenediaminetetraacetic acid, its potassium salt, its sodium salt; diethylenetriaminepentaacetic acid, its potassium salt, its sodium salt; triethylenetetraminehexaacetic acid, its potassium salt, its sodium salt; hydroxyethylethylenediaminetriacetic acid, its potassium salt, its sodium salt; nitrilotriacetic acid, its potassium salt, its sodium salt; 1,2-diaminocyclohexanetetraacetic acid, its potassium salt, its sodium salt; 1,3-diamino-2-propanoltetraacetic acid, its potassium salt, its sodium salt Examples include aminopolycarboxylic acids such as salts, and organic phosphonic acids or phosphonoalkanetricarboxylic acids such as 2-phosphonobutanetricarboxylic acid-1,2,4, its potassium salt and sodium salt; 2-phosphonobutanetricarboxylic acid-2,3,4, its potassium salt and sodium salt; 1-phosphonoethanetricarboxylic acid-1,2,2, its potassium salt and sodium salt; 1-hydroxyethane-1,1-diphosphonic acid, its potassium salt and sodium salt; and aminotri(methylenephosphonic acid), its potassium salt and sodium salt. Instead of the sodium or potassium salts of the chelating agents mentioned above, ammonium or organic amine salts are also effective.

[0055] The plate cleaning agent used in this disclosure may contain one chelating compound alone or two or more chelating compounds. The chelating compound content is preferably 0.01% to 20% by mass, and more preferably 0.1% to 10% by mass, relative to the total mass of the plate cleaning agent.

[0056] <<Surfactants>> The plate cleaning agent used in this disclosure preferably contains a surfactant from the viewpoint of improving wettability. Examples of surfactants include anionic surfactants, nonionic surfactants, cationic surfactants, and amphoteric surfactants. Examples of anionic surfactants include fatty acid salts, abietins, hydroxyalkanesulfons, alkanesulfons, dialkylsulfosuccinates, linear alkylbenzenesulfons, branched alkylbenzenesulfons, alkylnaphthalenesulfons, alkylphenoxypolyoxyethylenepropylsulfons, polyoxyethylene alkylsulfophenyl ether salts, sodium N-methyl-N-oleyl taurate, disodium N-alkylsulfosuccinate monoamide, petroleum sulfons, hydrogenated castor oil, sulfated beef tallow, and alkyl fatty acid esters. Examples include sulfate ester salts, alkyl sulfate ester salts, polyoxyethylene alkyl ether sulfate ester salts, fatty acid monoglyceride sulfate ester salts, polyoxyethylene alkylphenyl ether sulfate ester salts, polyoxyethylene styrylphenyl ether sulfate ester salts, alkyl phosphate ester salts, polyoxyethylene alkyl ether phosphate ester salts, polyoxyethylene alkylphenyl ether phosphate ester salts, partially saponified styrene-maleic anhydride copolymers, partially saponified olefin-maleic anhydride copolymers, naphthalene sulfonate formalin condensates, and the like. Among these, dialkyl sulfosuccinates, alkyl sulfate esters, and alkylnaphthalene sulfonates are particularly preferred.

[0057] Examples of nonionic surfactants include polyoxyalkyl ethers, polyoxyethylene alkylphenyl ethers, polyoxyethylene polystyrenephenyl ethers, polyoxyethylene polyoxypropylene alkyl ethers, glycerin fatty acid partial esters, sorbitan fatty acid partial esters, pentaerythritol fatty acid partial esters, propylene glycol mono fatty acid partial esters, sucrose fatty acid partial esters, polyoxyethylene sorbitan fatty acid partial esters, polyoxyethylene sorbitol fatty acid partial esters, polyglycerin fatty acid partial esters, polyoxyethylene castor oils, polyoxyethylene glycerin fatty acid partial esters, fatty acid diethanolamides, N,N-bis-2-hydroxyalkylamines, polyoxyethylene alkylamines, triethanolamine fatty acid esters, and trialkylamine oxides. Among these, polyoxyethylene alkylphenyl ethers and polyoxyethylene-polyoxypropylene block polymers are preferred.

[0058] Examples of cationic surfactants include alkylamine salts, quaternary ammonium salts, polyoxyethylene alkylamine salts, and polyethylene polyamine derivatives. Examples of amphoteric surfactants include alkylimidazolines. Furthermore, fluorine-based surfactants can be suitably used as the surfactant. Examples of fluorinated anionic surfactants include perfluoroalkyl sulfonates, perfluoroalkyl carboxylates, and perfluoroalkyl phosphate esters, while examples of fluorinated nonionic surfactants include perfluoroalkyl ethylene oxide adducts and perfluoroalkyl propylene oxide adducts. Examples of fluorine-based cationic surfactants include perfluoroalkyltrimethylammonium salts.

[0059] The plate cleaning agent used in this disclosure may contain one surfactant alone or two or more surfactants. The surfactant content is preferably 10% by mass or less, and more preferably 0.1% to 5% by mass, relative to the total mass of the plate cleaning agent.

[0060] <<Hydrotrope Compounds>> The plate cleaning agent used in this disclosure preferably contains a hydrotrope compound, from the viewpoint of reducing the viscosity of the composition and improving the solubility of components such as solvents in water. As hydrotrope compounds, aromatic sulfonates such as toluenesulfonate, xylenesulfonate, and cumenesulfonate can be preferably used. Preferred salt structures of these include alkali metal salts, ammonium salts, and amine salts.

[0061] The plate cleaning agent used in this disclosure may contain one hydrotrope compound alone or two or more hydrotrope compounds. The hydrotrope compound content is preferably 0.01% to 20% by mass, and more preferably 0.1% to 10% by mass, relative to the total mass of the plate cleaning agent.

[0062] <<Humectant>> The plate cleaning agent used in this disclosure preferably contains a wetting agent from the viewpoint of improving wettability. Preferred humectants include glycols and alcohols. Examples of such wetting agents include propylene glycol, dipropylene glycol, tripropylene glycol, tetrapropylene glycol and pentapropylene glycol, ethylene glycol, diethylene glycol, triethylene glycol, polyethylene glycol, butylene glycol, hexylene glycol, ethyl alcohol, n-propyl alcohol, benzyl alcohol, glycerin, diglycerin, polyglycerin, and pentaerythritol.

[0063] The plate cleaning agent used in this disclosure may contain one type of wetting agent alone or two or more types of wetting agents. The wetting agent content is preferably 0.1% to 10% by mass, and more preferably 0.3% to 5% by mass, relative to the total mass of the plate cleaning agent.

[0064] The plate cleaning agent used in this disclosure can completely replace isopropyl alcohol. Furthermore, there are no issues with print quality even when using isopropyl alcohol and ethanol, n-propanol, t-butanol, amyl alcohol, etc., up to about 15% by mass in the dampening solution during use.

[0065] <<Diol Compounds>> The plate cleaning agent used in this disclosure preferably contains a diol compound from the viewpoint of improving the solubility of other components and suppressing contamination of the water supply roller. Preferred diol compounds include, specifically, 2-butyl-2-ethyl-1,3-propanediol, 2,4-diethyl-1,5-pentanediol, and 2-ethyl-1,3-hexanediol. Furthermore, as the diol compound, the diol compound described in Japanese Patent Publication No. 2009-96177 can be suitably used. Furthermore, among the diol compounds, those having two hydroxyl groups, with the shortest number of carbon atoms between the two hydroxyl groups being 2 to 6, and a total number of carbon atoms being 9, are particularly preferred.

[0066] The plate cleaning agent used in this disclosure may contain one diol compound alone or two or more diol compounds. The content of the diol compound is preferably 0.01% to 20% by mass, more preferably 0.05% to 10% by mass, even more preferably 0.1% to 7% by mass, and particularly preferably 0.2% to 5% by mass, based on the total mass of the plate cleaning agent.

[0067] <<Pyrrolidone derivatives>> The plate cleaning agent used in this disclosure preferably contains a pyrrolidone derivative from the viewpoint of improving wettability. Preferred pyrrolidone derivatives include compounds represented by the following formula (pyr).

[0068] [ka]

[0069] In the formula (pyr), R pyr This represents an alkyl group with 2 to 12 carbon atoms.

[0070] Specific examples of the above-mentioned pyrrolidone derivatives include ethylpyrrolidone, butylpyrrolidone, pentylpyrrolidone, hexylpyrrolidone, octylpyrrolidone, and laurylpyrrolidone. One or more of these compounds can be used. Among these compounds, R in formula (pyr) pyr Compounds in which the alkyl group has 6 or more carbon atoms are preferred, and octylpyrrolidone is particularly preferred.

[0071] The plate cleaning agent used in this disclosure may contain one pyrrolidone derivative alone or two or more derivatives. The pyrrolidone derivative content is preferably 0.01% to 20% by mass, more preferably 0.01% to 10% by mass, and particularly preferably 0.1% to 10% by mass, based on the total mass of the plate cleaning agent.

[0072] <<Acetylene glycols, acetylene alcohols, and their alkylene oxide adducts>> The plate cleaning agent used in this disclosure may contain at least one compound selected from the group consisting of acetylene glycols, acetylene alcohols, and alkylene oxide adducts thereof. Ethylene oxide and propylene oxide are preferred examples of the alkylene oxide. Specific examples of these compounds include 3,5-dimethyl-1-hexyn-3-ol, 2,5-dimethyl-3-hexyn-2,5-diol, 2,4,7,9-tetramethyl-5-decine-4,7-diol, 3,6-dimethyl-4-octin-3,6-diol, 2-butyn-1,4-diol, 3-methyl-1-butyn-3-ol, and their ethylene oxide and / or propylene oxide adducts. Among these, compounds obtained by adding 4 to 10 ethylene oxide groups to 3,6-dimethyl-4-octin-3,6-diol, 2,4,7,9-tetramethyl-5-decine-4,7-diol, or 2,4,7,9-tetramethyl-5-decine-4,7-diol are particularly preferred.

[0073] The plate cleaning agent used in this disclosure may contain one or more acetylene glycols, acetylene alcohols, and their alkylene oxide adducts. The content of acetylene glycols, acetylene alcohols, and their alkylene oxide adducts is preferably 0.001% to 20% by mass, and more preferably 0.01% to 10% by mass, based on the total mass of the plate cleaning agent.

[0074] <<Sugars>> The plate cleaning agent used in this disclosure preferably contains sugars from the viewpoint of suppressing contamination of non-image areas. Sugars can be selected from monosaccharides, disaccharides, and oligosaccharides, and sugar alcohols obtained by hydrogenation are also included. Specific examples include D-erythrose, D-threose, D-arabinose, D-ribose, D-xylose, D-erythropentulose, D-allulose, D-galactose, D-glucose, D-mannose, D-talose, β-D-fructose, α-L-sorbose, 6-deoxy-D-glucose, D-glycero-D-galactose, α-D-allo-heptulose, β-D-altro-3-heptulose, saccharose, lactose, D-maltose, isomaltose, inulobiose, hyalubiouron, maltotriose, D,L-arabit, ribit, xylitol, D,L-sorbitol, D,L-mannitol, D,L-ijit, D,L-talitol, dulcit, arodulcit, maltitol, and reduced starch syrup. These sugars may be used individually or in combination of two or more.

[0075] The plate cleaning agent used in this disclosure may contain one type of sugar or two or more types of sugars. The sugar content is preferably 0.1% to 20% by mass, and more preferably 0.5% to 10% by mass, relative to the total mass of the plate cleaning agent.

[0076] <<Preservatives>> The plate cleaning agent used in this disclosure preferably contains a preservative from the viewpoint of storage stability. Specific examples of preservatives include benzoic acid and its derivatives, phenol or its derivatives, formalin, imidazole derivatives, sodium dehydroacetate, 4-isothiazolin-3-one derivatives, benztriazole derivatives, amidine or guanidine derivatives, quaternary ammonium salts, pyridine, quinoline or guanidine derivatives, diazine or triazole derivatives, oxazole or oxazine derivatives, halogenonitropropane compounds, bromonitro alcohol-based bromonitropropanol, 1,1-dibromo-1-nitro-2-ethanol, 3-bromo-3-nitropentan-2,4-diol, and the like.

[0077] The plate cleaning agent used in this disclosure may contain one preservative alone or two or more preservatives. The amount of preservatives varies depending on the type of bacteria, mold, and yeast, but it is preferable that it be between 0.001% and 10% by mass relative to the total mass of the plate cleaning agent.

[0078] <<Other additives>> The plate cleaning agent used in this disclosure may contain other additives besides those described above. Other additives are not particularly limited and known additives can be used, such as colorants, rust inhibitors, defoamers, fragrances, and masking agents. Food colorants are preferably used as coloring agents. For example, yellow colorants include CI No. 19140 and 15985; red colorants include CI No. 16185, 45430, 16255, 45380, and 45100; purple colorant includes CI No. 42640; blue colorants include CI No. 42090 and 73015; and green colorant includes CI No. 42095. Examples of rust inhibitors include benzotriazole, 5-methylbenzotriazole, thiosalicylic acid, benzimidazole, and their derivatives. As an antifoaming agent, silicone antifoaming agents are preferred. Both emulsified dispersion type and solubilized type silicone antifoaming agents can be used. Furthermore, non-silicone antifoaming agents can be used in combination or alone.

[0079] The plate cleaning agent used in this disclosure may further contain corrosion inhibitors such as magnesium nitrate, zinc nitrate, calcium nitrate, sodium nitrate, potassium nitrate, lithium nitrate, and ammonium nitrate; hardening agents such as chromium compounds and aluminum compounds; organic solvents such as cyclic ethers: for example, 4-butyrolactone; and water-soluble surfactant organometallic compounds as described in Japanese Patent Publication No. 61-193893.

[0080] The content of each of these other additives is preferably 0.001% to 10% by mass, relative to the total mass of the plate cleaning agent.

[0081] <<pH of the printing plate cleaning agent>> When the plate cleaning agent used in this disclosure contains water, the pH of the plate cleaning agent is preferably 2 to 10, and particularly preferably 3 to 9. In this disclosure, the pH of the printing plate cleaning agent is the value measured at 25°C using HM-30R manufactured by Toa DKK Co., Ltd.

[0082] <Lithographic printing plate original plate> The lithographic printing method relating to this disclosure includes the step of preparing a lithographic printing plate master having an image recording layer containing an infrared absorbent on a support. The following embodiments are preferred for the lithographic printing plates used in this disclosure.

[0083] <<Image Recording Layer>> The lithographic printing plate used in this disclosure has an image recording layer formed on a support. The above image recording layer contains an infrared absorbent, and preferably contains a polymerizable compound, a polymerization initiator, and an infrared absorbent. The image recording layer used in this disclosure is preferably a negative-type image recording layer, and more preferably a water-soluble or water-dispersible negative-type image recording layer. From the viewpoint of on-press developability, it is preferable that the lithographic printing plate used in this disclosure allows for the removal of unexposed portions of the image recording layer by at least one of dampening solution and printing ink.

[0084] The following describes the details of each component contained in the image recording layer.

[0085] [Infrared absorber] The lithographic printing plate used in this disclosure includes an infrared absorbent in the image recording layer. There are no particular restrictions on the infrared absorber; for example, pigments and dyes can be used. Dyes used as infrared absorbers include commercially available dyes and known dyes listed in literature such as the "Dye Handbook" (edited by the Society of Synthetic Organic Chemistry, published in 1970). Specifically, examples of dyes include azo dyes, metal complex azo dyes, pyrazolone azo dyes, naphthoquinone dyes, anthraquinone dyes, phthalocyanine dyes, carbonium dyes, quinone imine dyes, methine dyes, cyanine dyes, squarylium dyes, pyryllium salts, and metal thiolate complexes.

[0086] Among these dyes, particularly preferred are cyanine dyes, squarylium dyes, pyryllium salts, nickel thiolate complexes, and indorenine-cyanine dyes. Furthermore, cyanine dyes and indorenine-cyanine dyes are also preferred. Of these, cyanine dyes are particularly preferred.

[0087] The infrared absorber described above is preferably a cationic polymethine dye having an oxygen or nitrogen atom at the meso position. Examples of cationic polymethine dyes include cyanine dyes, pyrylium dyes, thiopyrillium dyes, and azulenium dyes, with cyanine dyes being preferred from the viewpoint of ease of acquisition and solvent solubility during the introduction reaction.

[0088] Specific examples of cyanine dyes include the compounds described in paragraphs 0017 to 0019 of Japanese Patent Publication No. 2001-133969, the compounds described in paragraphs 0016 to 0021 of Japanese Patent Publication No. 2002-023360, the compounds described in paragraphs 0012 to 0037 of Japanese Patent Publication No. 2002-040638, preferably the compounds described in paragraphs 0034 to 0041 of Japanese Patent Publication No. 2002-278057, the compounds described in paragraphs 0080 to 0086 of Japanese Patent Publication No. 2008-195018, particularly preferably the compounds described in paragraphs 0035 to 0043 of Japanese Patent Publication No. 2007-90850, and the compounds described in paragraphs 0105 to 0113 of Japanese Patent Publication No. 2012-206495. Furthermore, the compounds described in paragraphs 0008 to 0009 of Japanese Patent Publication No. 5-5005 and paragraphs 0022 to 0025 of Japanese Patent Publication No. 2001-222101 can also be preferably used. As pigments, compounds described in paragraphs 0072 to 0076 of Japanese Patent Publication No. 2008-195018 are preferred.

[0089] Furthermore, as an infrared absorber, the one described in International Publication No. 2020 / 262692 can be suitably used. Furthermore, as infrared absorbers that are decomposed by infrared exposure, those described in Japanese Patent Publication No. 2008-544322 or International Publication No. 2016 / 027886 can be suitably used.

[0090] Furthermore, the value of the highest occupied orbital (HOMO) of the infrared absorber used in this disclosure is preferably -5.00 eV or less, and more preferably -5.30 eV or less, from the viewpoint of print durability and halftone reproducibility. Furthermore, as a lower limit, from the viewpoint of print durability and halftone reproducibility, it is preferable to be -5.90 eV or higher, more preferably -5.75 eV or higher, and even more preferably -5.60 eV or higher.

[0091] In this disclosure, the highest occupied orbit (HOMO) and lowest unoccupied orbit (LUMO) are calculated by the following method. First, free counterions in the compounds being calculated are excluded from the calculation. For example, in cationic one-electron-accepting polymerization initiators and cationic infrared absorbers, counter anions are excluded, and in anionic one-electron-donating polymerization initiators, counter cations are excluded. Here, "free" means that the compound in question and its counterion are not covalently bonded. Using the quantum chemistry calculation software Gaussian09, structural optimization is performed using DFT (B3LYP / 6-31G(d)). The MO (molecular orbital) energy calculation is performed using DFT (B3LYP / 6-31+G(d,p) / CPCM(solvent=methanol)) with the structure obtained from the above structure optimization. The MO energy Ebare (unit: hartree) obtained from the above MO energy calculation is converted to Escaled (unit: eV), which will be used as the HOMO and LUMO values ​​in this disclosure, using the following formula. Escaled=0.823168×27.2114×Ebare-1.07634 Note that 27.2114 is simply a coefficient for converting Hartree to eV, while 0.823168 and -1.07634 are adjustment coefficients used to determine the HOMO and LUMO of the compound being calculated so that the calculation matches the experimentally observed values.

[0092] Infrared absorbers may be used individually or in combination of two or more types. Furthermore, pigments and dyes may be used in combination as infrared absorbers. The total amount of infrared absorbent in the image recording layer is preferably 0.1% to 10.0% by mass, and more preferably 0.5% to 5.0% by mass, relative to the total mass of the image recording layer.

[0093] [Polymerizable compound] The image recording layer in this disclosure preferably contains a polymerizable compound. In this disclosure, "polymerizable compound" means a compound having a polymerizable group. The polymerizable group is not particularly limited and any known polymerizable group is acceptable, but it is preferably an ethylenically unsaturated group. Furthermore, the polymerizable group may be a radical polymerizable group or a cationic polymerizable group, but it is preferably a radical polymerizable group. Examples of radical polymerizable groups include (meth)acryloyl groups, allyl groups, vinylphenyl groups, and vinyl groups, with (meth)acryloyl groups being preferred from the viewpoint of reactivity. The molecular weight of the polymerizable compound (or weight-average molecular weight if it has a molecular weight distribution) is preferably 50 or more and less than 2,500.

[0094] The polymerizable compounds used in this disclosure may be, for example, radical polymerizable compounds or cationic polymerizable compounds, but are preferably addition polymerizable compounds (ethylenically unsaturated compounds) having at least one ethylenically unsaturated bond. The ethylenically unsaturated compound is preferably a compound having at least one terminal ethylenically unsaturated bond, and more preferably a compound having two or more terminal ethylenically unsaturated bonds. The polymerizable compound may have chemical forms such as monomers, prepolymers, i.e., dimers, trimers or oligomers, or mixtures thereof. In particular, from the viewpoint of print resistance, the polymerizable compound preferably contains a polymerizable compound with three or more functions, more preferably a polymerizable compound with seven or more functions, and even more preferably a polymerizable compound with ten or more functions. Furthermore, from the viewpoint of print resistance in the resulting lithographic printing plate, the polymerizable compound preferably contains an ethylenically unsaturated compound with three or more functions (preferably seven or more functions, more preferably ten or more functions), and even more preferably a (meth)acrylate compound with three or more functions (preferably seven or more functions, more preferably ten or more functions).

[0095] Furthermore, from the viewpoint of on-pressure developability and stain suppression, the polymerizable compound preferably contains a polymerizable compound with two or fewer functions, more preferably a bifunctional polymerizable compound, and particularly preferably a bifunctional (meth)acrylate compound. The content of a bifunctional polymerizable compound (preferably a bifunctional polymerizable compound) is preferably 5% to 100% by mass, more preferably 10% to 100% by mass, and particularly preferably 15% to 100% by mass, relative to the total mass of polymerizable compounds in the image recording layer, from the viewpoint of print resistance, on-press developability, and stain suppression.

[0096] -Oligomer- It is preferable that the polymerizable compound contained in the image recording layer is an oligomeric polymerizable compound (hereinafter also simply referred to as "oligomer"). In this disclosure, "oligomer" refers to a polymerizable compound having a molecular weight (or weight-average molecular weight if it has a molecular weight distribution) of 600 or more and 10,000 or less, and containing at least one polymerizable group. From the viewpoint of excellent chemical resistance and print resistance, the molecular weight of the oligomer is preferably between 1,000 and 5,000.

[0097] Furthermore, from the viewpoint of improving print resistance, the number of polymerizable groups in one oligomer molecule is preferably 2 or more, more preferably 3 or more, even more preferably 6 or more, and particularly preferably 10 or more. Furthermore, there is no particular upper limit on the number of polymerizable groups in the oligomer, but it is preferable that the number of polymerizable groups be 20 or less.

[0098] From the viewpoint of print resistance and on-press developability, the oligomer preferably has 7 or more polymerizable groups and a molecular weight of 1,000 to 10,000, and more preferably has 7 to 20 polymerizable groups and a molecular weight of 1,000 to 5,000. Furthermore, the product may contain polymer components that may be generated during the manufacturing process of the oligomer.

[0099] From the viewpoint of print resistance, visibility, and on-press developability, the oligomer preferably has at least one compound selected from the group consisting of compounds having a urethane bond, compounds having an ester bond, and compounds having an epoxy residue, and it is preferable that it has a compound having a urethane bond. In this disclosure, the term "epoxy residue" refers to a structure formed by an epoxy group, and means a structure similar to that obtained by a reaction between an acid group (such as a carboxylic acid group) and an epoxy group.

[0100] As for compounds having a urethane bond, those described in International Publication No. 2020 / 262692 can be suitably used.

[0101] Furthermore, as a compound having a urethane bond, a compound obtained by introducing polymerizable groups through a polymer reaction into a polyurethane obtained by the reaction of a polyisocyanate compound and a polyol compound may be used. For example, a compound having a urethane bond may be obtained by reacting a polyurethane oligomer, which is obtained by reacting a polyol compound having an acid group with a polyisocyanate compound, with a compound having an epoxy group and a polymerizable group.

[0102] In a compound having an ester bond, which is an example of an oligomer, the number of polymerizable groups is preferably 3 or more, and more preferably 6 or more.

[0103] As examples of oligomers containing epoxy residues, compounds containing a hydroxyl group within the compound are preferred. Furthermore, the number of polymerizable groups in the compound having epoxy residues is preferably 2 to 6, and more preferably 2 to 3. Compounds having the above-mentioned epoxy residue can be obtained, for example, by reacting a compound having an epoxy group with acrylic acid.

[0104] Specific examples of oligomers are shown in the table below, but the oligomers used in this disclosure are not limited to these. Commercial oligomers may be used, including, but are not limited to, UA510H, UA-306H, UA-306I, UA-306T (all manufactured by Kyoeisha Chemical Co., Ltd.), UV-1700B, UV-6300B, UV7620EA (all manufactured by Nippon Synthetic Chemical Industry Co., Ltd.), U-15HA (manufactured by Shin Nakamura Chemical Industry Co., Ltd.), EBECRYL450, EBECRYL657, EBECRYL885, EBECRYL800, EBECRYL3416, EBECRYL860 (all manufactured by Daicel Ornex Co., Ltd.).

[0105] From the viewpoint of improving chemical resistance, print resistance, and suppression of on-press development residue, the oligomer content is preferably 30% to 100% by mass, more preferably 50% to 100% by mass, and even more preferably 80% to 100% by mass, based on the total mass of polymerizable compounds in the image recording layer.

[0106] -Low molecular polymerizable compounds- The polymerizable compound may further contain polymerizable compounds other than the above-mentioned oligomer. From the viewpoint of chemical resistance, polymerizable compounds other than oligomers are preferably low-molecular-weight polymerizable compounds. Low-molecular-weight polymerizable compounds may be in chemical forms such as monomers, dimers, trimers, or mixtures thereof. Furthermore, from the viewpoint of chemical resistance, the low molecular weight polymerizable compound is preferably at least one polymerizable compound selected from the group consisting of polymerizable compounds having three or more ethylenically unsaturated groups and polymerizable compounds having an isocyanuric ring structure.

[0107] In this disclosure, "low molecular weight polymerizable compound" refers to a polymerizable compound with a molecular weight (or weight-average molecular weight, if a molecular weight distribution exists) of 50 or more and less than 600. The molecular weight of the low molecular weight polymerizable compound is preferably 100 or more and less than 600, more preferably 300 or more and less than 600, and even more preferably 400 or more and less than 600, from the viewpoint of excellent chemical resistance, print resistance, and suppression of on-press developer residue.

[0108] When the polymerizable compound includes low molecular weight polymerizable compounds as polymerizable compounds other than oligomers (the total amount if it includes two or more types of low molecular weight polymerizable compounds), from the viewpoint of chemical resistance, print resistance, and suppression of on-press developer residue, the ratio of the oligomer to the low molecular weight polymerizable compound (oligomer / low molecular weight polymerizable compound) is preferably 10 / 1 to 1 / 10 by mass, more preferably 10 / 1 to 3 / 7, and even more preferably 10 / 1 to 7 / 3.

[0109] Furthermore, as low molecular weight polymerizable compounds, polymerizable compounds described in paragraphs 0082 to 0086 of International Publication No. 2019 / 013268 can also be suitably used.

[0110] The structure of the polymerizable compound, whether it is used alone or in combination, and the amount added, as well as other details of its usage, can be arbitrarily determined. In particular, the image recording layer preferably contains two or more polymerizable compounds from the viewpoint of print resistance. The content of polymerizable compounds (or the total content of polymerizable compounds if two or more polymerizable compounds are included) is preferably 5% to 75% by mass, more preferably 10% to 70% by mass, and even more preferably 15% to 60% by mass, based on the total mass of the image recording layer.

[0111] [Polymerization initiator] The image recording layer in this disclosure preferably contains a polymerization initiator. Furthermore, from the viewpoint of sensitivity, print resistance, on-press developability, and ink adhesion, the polymerization initiator preferably includes an electron-donating polymerization initiator, and more preferably includes both an electron-accepting polymerization initiator and an electron-donating polymerization initiator.

[0112] -Electron-accepting polymerization initiator- The image recording layer described above preferably contains an electron-accepting polymerization initiator as a polymerization initiator. Electron-accepting polymerization initiators are compounds that, when electrons in an infrared absorber are excited by infrared exposure, accept one electron through intermolecular electron transfer, thereby generating polymerization initiator species such as radicals. The electron-accepting polymerization initiators used in this disclosure are compounds that generate polymerization initiator species such as radicals or cations in response to light, heat, or both of these energies, and can be appropriately selected from known thermal polymerization initiators, compounds having bonds with low bond dissociation energy, photopolymerization initiators, etc. As electron-accepting polymerization initiators, radical polymerization initiators are preferred, and onium salt compounds are more preferred. Furthermore, an infrared photosensitive polymerization initiator is preferred as the electron-accepting polymerization initiator. Examples of electron-accepting radical polymerization initiators include (a) organic halides, (b) carbonyl compounds, (c) azo compounds, (d) organic peroxides, (e) metallocene compounds, (f) azide compounds, (g) hexaarylbiimidazole compounds, (i) disulfone compounds, (j) oxime ester compounds, and (k) onium salt compounds.

[0113] (a) As organic halides, for example, the compounds described in paragraphs 0022 to 0023 of Japanese Patent Publication No. 2008-195018 are preferred. (b) As a carbonyl compound, for example, the compound described in paragraph 0024 of Japanese Patent Publication No. 2008-195018 is preferred. (c) As the azo compound, for example, the azo compound described in Japanese Patent Publication No. 8-108621 can be used. (d) As for the organic peroxide, for example, the compound described in paragraph 0025 of Japanese Patent Application Publication No. 2008-195018 is preferred. (e) As a metallocene compound, for example, the compound described in paragraph 0026 of Japanese Patent Publication No. 2008-195018 is preferred. (f) Examples of azide compounds include 2,6-bis(4-azidobenzylidene)-4-methylcyclohexanone. (g) As a hexaarylbiimidazole compound, for example, the compound described in paragraph 0027 of Japanese Patent Publication No. 2008-195018 is preferred. (i) Examples of disulfone compounds include those described in Japanese Patent Publication No. 61-166544 and Japanese Patent Publication No. 2002-328465. (j) As oxime ester compounds, for example, the compounds described in paragraphs 0028 to 0030 of Japanese Patent Publication No. 2008-195018 are preferred.

[0114] Among the electron-accepting polymerization initiators mentioned above, oxime ester compounds and onium salt compounds are preferred from the viewpoint of curability. In particular, iodonium salt compounds, sulfonium salt compounds, or azinium salt compounds are preferred from the viewpoint of print resistance, iodonium salt compounds or sulfonium salt compounds are more preferred, and iodonium salt compounds are especially preferred. Specific examples of these compounds are given below, but this disclosure is not limited to them.

[0115] Examples of iodonium salt compounds include diaryliodonium salt compounds, more preferably diphenyliodonium salt compounds substituted with electron-donating groups, such as alkyl or alkoxyl groups, and asymmetric diphenyliodonium salt compounds. Specific examples include diphenyliodonium = hexafluorophosphate, 4-methoxyphenyl-4-(2-methylpropyl)phenyliodonium = hexafluorophosphate, 4-(2-methylpropyl)phenyl-p-tolylliodonium = hexafluorophosphate, 4-hexyloxyphenyl-2,4,6-trimethoxyphenyliodonium = hexafluorophosphate, 4-hexyloxyphenyl-2,4-diethoxyphenyliodonium = tetrafluoroborate, 4-octyloxyphenyl-2,4,6-trimethoxyphenyliodonium = 1-perfluorobutanesulfonate, 4-octyloxyphenyl-2,4,6-trimethoxyphenyliodonium = hexafluorophosphate, and bis(4-t-butylphenyl)iodonium = hexafluorophosphate.

[0116] Examples of sulfonium salt compounds include triarylsulfonium salt compounds, and particularly preferred are triarylsulfonium salt compounds in which at least a portion of the electron-withdrawing group, for example, the group on the aromatic ring, is substituted with a halogen atom. Triarylsulfonium salt compounds in which the total number of halogen atom substitutions on the aromatic ring is 4 or more are even more preferred. Specific examples include triphenylsulfonium=hexafluorophosphate, triphenylsulfonium=benzoylformate, bis(4-chlorophenyl)phenylsulfonium=benzoylformate, bis(4-chlorophenyl)-4-methylphenylsulfonium=tetrafluoroborate, tris(4-chlorophenyl)sulfonium=3,5-bis(methoxycarbonyl)benzenesulfonate, tris(4-chlorophenyl)sulfonium=hexafluorophosphate, and tris(2,4-dichlorophenyl)sulfonium=hexafluorophosphate.

[0117] Furthermore, as counter anions for iodonium salt compounds and sulfonium salt compounds, sulfonamide anions or sulfonimide anions are preferred, with sulfonimide anions being more preferred. As the sulfonamide anion, an aryl sulfonamide anion is preferred. Furthermore, bisarylsulfonimide anions are preferred as sulfonimide anions. Specific examples of sulfonamide anions or sulfonimide anions are preferably those described in International Publication No. 2020 / 262692.

[0118] Furthermore, the electron-accepting polymerization initiator may also contain a compound represented by the following formula (II) from the viewpoint of developability and print durability of the resulting lithographic printing plate.

[0119] [ka]

[0120] In formula (II), X A represents a halogen atom, RA This represents an aryl group.

[0121] X in equation (II) A Specifically, examples include fluorine atoms, chlorine atoms, bromine atoms, and iodine atoms. Of these, chlorine atoms or bromine atoms are preferred due to their excellent sensitivity, and bromine atoms are particularly preferred. Furthermore, in equation (II), R A From the viewpoint of providing an excellent balance between sensitivity and storage stability, aryl groups substituted with amide groups are preferred.

[0122] As a specific example of the electron-accepting polymerization initiator represented by the above formula (II), the one described in International Publication No. 2020 / 262692 can be suitably used.

[0123] The lowest unoccupied orbital (LUMO) of the electron-accepting polymerization initiator is preferably -3.00 eV or less, and more preferably -3.02 eV or less, from the viewpoint of improving sensitivity and reducing the occurrence of plate skipping. Furthermore, the lower limit is preferably -3.80 eV or higher, and more preferably -3.60 eV or higher.

[0124] Electron-accepting polymerization initiators may be used alone or in combination of two or more. The content of the electron-accepting polymerization initiator is preferably 0.1% to 50% by mass, more preferably 0.5% to 30% by mass, and particularly preferably 0.8% to 20% by mass, based on the total mass of the image recording layer.

[0125] -Electron-donating polymerization initiator- From the viewpoint of contributing to improved chemical resistance and print resistance in lithographic printing plates, the polymerization initiator preferably includes an electron-donating polymerization initiator, and more preferably includes both an electron-donating polymerization initiator and the above-mentioned electron-donating polymerization initiator. Examples of electron-donating polymerization initiators include the following five types: (i) Alkyl or arylate complexes: These are thought to oxidatively break the carbon-heterobond and generate active radicals. Specifically, borate salt compounds are examples. (ii) Aminoacetic acid compounds: It is thought that oxidation causes the CX bond on the carbon adjacent to the nitrogen to break, generating an active radical. X is preferably a hydrogen atom, a carboxyl group, a trimethylsilyl group, or a benzyl group. Specifically, examples include N-phenylglycines (which may have substituents on the phenyl group) and N-phenyliminodiacetic acid (which may have substituents on the phenyl group). (iii) Sulfur-containing compounds: Compounds obtained by replacing the nitrogen atom of the above-mentioned aminoacetic acid compounds with a sulfur atom can generate active radicals through a similar mechanism. Specifically, examples include phenylthioacetic acid (which may have substituents on the phenyl group). (iv) Tin-containing compounds: Compounds in which the nitrogen atoms of the above-mentioned aminoacetic acid compounds are replaced with tin atoms can generate active radicals through a similar mechanism. (v) Sulfinates: These can generate active radicals upon oxidation. Examples include sodium arylsulfinate.

[0126] Among these electron-donating polymerization initiators, the image recording layer preferably contains a borate salt compound. As the borate salt compound, tetraarylborate salt compounds or monoalkyltriarylborate salt compounds are preferred, and from the viewpoint of compound stability, tetraarylborate salt compounds are more preferred, and tetraphenylborate salt compounds are particularly preferred. The countercation of the borate salt compound is not particularly limited, but it is preferably an alkali metal ion or a tetraalkylammonium ion, and more preferably a sodium ion, a potassium ion, or a tetrabutylammonium ion.

[0127] Sodium tetraphenylborate is a preferred example of a borate salt compound.

[0128] Furthermore, the highest occupied orbital (HOMO) of the electron-donating polymerization initiator used in this disclosure is preferably -6.00 eV or higher, more preferably -5.95 eV or higher, even more preferably -5.93 eV or higher, and particularly preferably greater than -5.90 eV, from the viewpoint of chemical resistance and print resistance. Furthermore, the upper limit is preferably -5.00 eV or less, and more preferably -5.40 eV or less.

[0129] Preferred examples of electron-donating polymerization initiators include those described in International Publication No. 2020 / 262692.

[0130] Furthermore, from the viewpoint of visibility, print resistance, and stability over time, the image recording layer preferably contains at least one compound selected from the group consisting of an onium salt compound as the electron-accepting polymerization initiator and a borate salt compound as the electron-donating polymerization initiator, and more preferably contains an onium salt compound as the electron-accepting polymerization initiator and a borate salt compound as the electron-donating polymerization initiator. Furthermore, the image recording layer preferably contains a borate salt compound as the electron-donating polymerization initiator, and more preferably contains a borate salt compound as the electron-donating polymerization initiator, and the HOMO-HOMO ratio of the infrared absorber to the borate salt compound is 0.70 eV or less.

[0131] Electron-donating polymerization initiators may be added individually or in combination of two or more. The content of the electron-donating polymerization initiator is preferably 0.01% to 30% by mass, more preferably 0.05% to 25% by mass, and even more preferably 0.1% to 20% by mass, relative to the total mass of the image recording layer.

[0132] Furthermore, one preferred embodiment in this disclosure is one in which the electron-accepting polymerization initiator and the electron-donating polymerization initiator form a salt. Specifically, for example, the onium salt compound is a salt of an onium ion and an anion in the electron-donating polymerization initiator (e.g., tetraphenylborate anion). More preferably, an iodonium borate salt compound is obtained in which an iodonium cation (e.g., di-p-tolyliodonium cation) in the iodonium salt compound forms a salt with a borate anion in the electron-donating polymerization initiator. A specific example of the embodiment in which the above-mentioned electron-accepting polymerization initiator and the above-mentioned electron-donating polymerization initiator form a salt is preferably the one described in International Publication No. 2020 / 262692.

[0133] In this disclosure, if the image recording layer includes an onium ion and an anion in the electron-donating polymerization initiator described above, the image recording layer shall include an electron-accepting polymerization initiator and the electron-donating polymerization initiator.

[0134] [Relationship between electron-donating polymerization initiators, electron-accepting polymerization initiators, and infrared absorbers] The image recording layer in this disclosure comprises the electron-donating polymerization initiator, the electron-accepting polymerization initiator, and the infrared absorber, wherein the HOMO of the electron-donating polymerization initiator is -6.0 eV or higher, and the LUMO of the electron-accepting polymerization initiator is -3.0 eV or lower. More preferred embodiments of the HOMO of the electron-donating polymerization initiator and the LUMO of the electron-accepting polymerization initiator are as described above. In the image recording layer of this disclosure, it is presumed that the electron-donating polymerization initiator, at least one of the infrared absorbers, and the electron-accepting polymerization initiator exchange energy as shown in the following chemical formula, for example. Therefore, if the HOMO of the electron-donating polymerization initiator is -6.0 eV or higher, and the LUMO of the electron-accepting polymerization initiator is -3.0 eV or lower, the radical generation efficiency will improve, and thus the chemical resistance and print resistance are likely to be superior.

[0135] [ka]

[0136] From the viewpoint of print resistance and chemical resistance, the HOMO-HOMO value of the infrared absorber to the electron-donating polymerization initiator is preferably 1.0 eV or less, more preferably 0.70 eV or less, and particularly preferably 0.60 eV or less. Similarly, from the same viewpoint, the HOMO-HOMO value of the infrared absorber to the electron-donating polymerization initiator is preferably -0.200 eV or more, and more preferably -0.100 eV or more. A negative value means that the HOMO of the electron-donating polymerization initiator is higher than the HOMO of the infrared absorber. Furthermore, from the viewpoint of print resistance and chemical resistance, the LUMO-LUMO value of the electron-accepting polymerization initiator and the infrared absorber is preferably 1.00 eV or less, and more preferably 0.700 eV or less. Also, from the same viewpoint, the LUMO-LUMO value of the electron-accepting polymerization initiator and the infrared absorber is preferably -0.200 eV or more, and more preferably -0.100 eV or more. Furthermore, from a similar viewpoint, the LUMO value of the electron-accepting polymerization initiator and the LUMO value of the infrared absorber are preferably 1.00 eV to -0.200 eV, and more preferably 0.700 eV to -0.100 eV. A negative value indicates that the LUMO of the infrared absorber is higher than that of the electron-accepting polymerization initiator.

[0137] 〔particle〕 The above image recording layer preferably contains particles from the viewpoint of print resistance. The particles may be organic or inorganic, but from the viewpoint of print resistance, it is preferable to include organic particles, and more preferable to include polymer particles. As inorganic particles, known inorganic particles can be used, and metal oxide particles such as silica particles and titania particles can be suitably used.

[0138] The polymer particles are preferably selected from the group consisting of thermoplastic resin particles, thermally reactive resin particles, polymer particles having a polymerizable group, microcapsules encapsulating a hydrophobic compound, and microgels (crosslinked polymer particles). Among these, polymer particles having a polymerizable group or microgels are preferred. In a particularly preferred embodiment, the polymer particles contain at least one ethylenically unsaturated group. The presence of such polymer particles provides the effect of enhancing the printing durability of exposed areas and the on-press developability of unexposed areas. Further, the polymer particles are preferably thermoplastic resin particles from the viewpoints of printing durability and on-press developability.

[0139] As the thermoplastic resin particles, the thermoplastic polymer particles described in Research Disclosure No.33303 dated January 1992, JP-A-9-123387, JP-A-9-131850, JP-A-9-171249, JP-A-9-171250, European Patent No.931647, and the like are preferred. Specific examples of the polymer constituting the thermoplastic resin particles include homopolymers or copolymers of monomers such as ethylene, styrene, vinyl chloride, methyl acrylate, ethyl acrylate, methyl methacrylate, ethyl methacrylate, vinylidene chloride, acrylonitrile, vinylcarbazole, acrylates or methacrylates having a polyalkylene structure, and mixtures thereof. Preferred examples include polystyrene, copolymers containing styrene and acrylonitrile, and polymethyl methacrylate. The average particle diameter of the thermoplastic resin particles is preferably from 0.01 μm to 3.0 μm.

[0140] Examples of the thermally reactive resin particles include polymer particles having a thermally reactive group. The thermally reactive polymer particles form a hydrophobized region through crosslinking caused by thermal reaction and accompanying functional group change.

[0141] The thermally reactive group in the polymer particles having a thermally reactive group may be any functional group that undergoes a reaction as long as a chemical bond is formed, and is preferably a polymerizable group, examples of which include ethylenically unsaturated groups that undergo radical polymerization reaction (e.g., acryloyl group, methacryloyl group, vinyl group, allyl group, etc.), cationically polymerizable groups (e.g., vinyl group, vinyloxy group, epoxy group, oxetanyl group, etc.), isocyanato groups or blocked bodies thereof that undergo addition reaction, epoxy groups, vinyloxy groups, and functional groups having an active hydrogen atom that is a reaction partner thereof (e.g., amino group, hydroxy group, carboxy group, etc.), carboxy groups that undergo condensation reaction and hydroxy groups or amino groups that are reaction partners thereof, acid anhydrides that undergo ring-opening addition reaction and amino groups or hydroxy groups that are reaction partners thereof, and the like are preferably mentioned.

[0142] As the microcapsules, for example, as described in JP-A-2001-277740 and JP-A-2001-277742, at least a part of the constituent components of the image recording layer is encapsulated in the microcapsules. The constituent components of the image recording layer can also be contained outside the microcapsules. A preferred embodiment of the image recording layer containing microcapsules has a configuration in which hydrophobic constituent components are encapsulated in the microcapsules, and hydrophilic constituent components are contained outside the microcapsules.

[0143] The microgel (crosslinked polymer particles) can contain a part of the constituent components of the image recording layer on at least one of the surface or the interior thereof. In particular, a reactive microgel having a radical polymerizable group on its surface is preferable from the viewpoints of the sensitivity of the obtained lithographic printing plate precursor and the press life of the obtained lithographic printing plate.

[0144] Known methods can be applied to microencapsulate or microgelate the constituent components of the image recording layer.

[0145] Furthermore, as polymer particles, those obtained by the reaction of a polyhydric isocyanate compound, which is an adduct of a polyhydric phenol compound having two or more hydroxyl groups in its molecule with isophorone diisocyanate, and a compound having active hydrogen are preferred from the viewpoint of print resistance, stain resistance, and storage stability of the resulting lithographic printing plate. As the above-mentioned polyhydric phenol compound, a compound having multiple benzene rings with phenolic hydroxyl groups is preferred. The compound having the active hydrogen described above is preferably a polyol compound or a polyamine compound, more preferably a polyol compound, and even more preferably at least one compound selected from the group consisting of propylene glycol, glycerin, and trimethylolpropane. As resin particles obtained by the reaction of a polyvalent isocyanate compound, which is an adduct of a polyvalent phenol compound having two or more hydroxyl groups in its molecule with isophorone diisocyanate, and a compound having active hydrogen, polymer particles described in paragraphs 0032 to 0095 of Japanese Patent Application Publication No. 2012-206495 are preferred.

[0146] Furthermore, from the viewpoint of print resistance and solvent resistance of the resulting lithographic printing plate, it is preferable that the polymer particles include both i) constituent units having a hydrophobic main chain and a pendant cyano group directly bonded to the hydrophobic main chain, and ii) constituent units having a pendant group containing a hydrophilic polyalkylene oxide segment. As the hydrophobic main chain mentioned above, an acrylic resin chain is preferred. Preferred examples of the pendant cyano group mentioned above include -[CH2CH(C≡N)]- or -[CH2C(CH3)(C≡N)]-. Furthermore, the constituent units having the pendant cyano group can be easily derived from ethylene-based unsaturated monomers, such as acrylonitrile or methacrylonitrile, or combinations thereof. Furthermore, as the alkylene oxide in the hydrophilic polyalkylene oxide segment described above, ethylene oxide or propylene oxide is preferred, and ethylene oxide is more preferred. The number of repeating alkylene oxide structures in the hydrophilic polyalkylene oxide segment described above is preferably 10 to 100, more preferably 25 to 75, and even more preferably 40 to 50. Particles of a resin having a hydrophobic main chain and comprising both i) a constituent unit having a pendant cyano group directly bonded to the hydrophobic main chain, and ii) a constituent unit having a pendant group containing a hydrophilic polyalkylene oxide segment, are preferably those described in paragraphs 0039 to 0068 of Japanese Patent Publication No. 2008-503365.

[0147] Furthermore, the polymer particles described above preferably have hydrophilic groups from the viewpoint of print resistance and on-press developability. The hydrophilic groups mentioned above are not particularly limited as long as they have a hydrophilic structure, but examples include acidic groups such as carboxyl groups, hydroxyl groups, amino groups, cyano groups, and polyalkylene oxide structures. In particular, from the viewpoint of on-press developability and print durability, the polyalkylene oxide structure is preferred, and the polyethylene oxide structure, polypropylene oxide structure, or polyethylene / propylene oxide structure is more preferred. Furthermore, from the viewpoint of on-pressure development and suppression of developing residue during on-pressure development, it is preferable that the polyalkylene oxide structure has a polypropylene oxide structure, and it is more preferable that it has both a polyethylene oxide structure and a polypropylene oxide structure. Furthermore, the hydrophilic group preferably includes a constituent unit having a cyano group or a group represented by the following formula Z, more preferably a constituent unit represented by the following formula (AN) or a group represented by the following formula Z, and particularly preferably a group represented by the following formula Z, from the viewpoint of print resistance, ink transfer, and on-press developability. *-QWY formula Z In Formula Z, Q represents a divalent linking group, W represents a divalent group having a hydrophilic structure or a divalent group having a hydrophobic structure, Y represents a monovalent group having a hydrophilic structure or a monovalent group having a hydrophobic structure, either W or Y has a hydrophilic structure, and * represents a bonding site to another structure.

[0148]

Chemical Formula

[0149] In Formula (AN), R AN represents a hydrogen atom or a methyl group.

[0150] From the viewpoint of press life, the polymer contained in the polymer particles preferably includes a structural unit formed by a compound having a cyano group. The cyano group is usually preferably introduced into the resin as a structural unit containing a cyano group using a compound (monomer) having a cyano group. Examples of the compound having a cyano group include acrylonitrile compounds, and (meth)acrylonitrile is suitably mentioned. The structural unit having a cyano group is preferably a structural unit formed by an acrylonitrile compound, more preferably a structural unit formed by (meth)acrylonitrile, that is, a structural unit represented by the above Formula (AN). When the polymer includes a polymer having a structural unit having a cyano group, the content of the structural unit having a cyano group in the polymer having a structural unit having a cyano group, preferably the structural unit represented by the above Formula (AN), is preferably 5% by mass to 90% by mass, more preferably 20% by mass to 80% by mass, and particularly preferably 30% by mass to 60% by mass, based on the total mass of the polymer having a structural unit having a cyano group, from the viewpoint of press life.

[0151] Further, from the viewpoints of press life, inking properties, and on-press developability, the polymer particles preferably include polymer particles having a group represented by the above Formula Z.

[0152] Q in the above formula Z is preferably a divalent linking group having 1 to 20 carbon atoms, and more preferably a divalent linking group having 1 to 10 carbon atoms. Further, Q in the above formula Z is preferably an alkylene group, an arylene group, an ester bond, an amide bond, or a group formed by combining two or more of these, and more preferably a phenylene group, an ester bond, or an amide bond.

[0153] The divalent group having a hydrophilic structure in W of the above formula Z is preferably a polyalkyleneoxy group, or a group in which -CH2CH2NR is bonded to one terminal of the polyalkyleneoxy group W -. Here, R W each represents a hydrogen atom or an alkyl group. The divalent group having a hydrophobic structure in W of the above formula Z is preferably -R WA -, -O-R WA -O-, -R W N-R WA -NR W -, -OC(=O)-R WA -O-, or -OC(=O)-R WA -O-. Here, each R WA independently represents a linear, branched or cyclic alkylene group having 6 to 120 carbon atoms, a haloalkylene group having 6 to 120 carbon atoms, an arylene group having 6 to 120 carbon atoms, an alkarylene group (a divalent group obtained by removing one hydrogen atom from an alkylaryl group) having 6 to 120 carbon atoms, or an aralkylene group having 6 to 120 carbon atoms.

[0154] The monovalent group having a hydrophilic structure in Y of the above formula Z is -OH, -C(=O)OH, a polyalkyleneoxy group whose terminal is a hydrogen atom or an alkyl group, or a group in which -CH2CH2NR is bonded to the other terminal of the polyalkyleneoxy group whose terminal is a hydrogen atom or an alkyl group W -. The monovalent group having a hydrophobic structure in Y of the above formula Z is a linear, branched, or cyclic alkyl group having 6 to 120 carbon atoms, a haloalkyl group having 6 to 120 carbon atoms, an aryl group having 6 to 120 carbon atoms, an alcaryl group (alkylaryl group) having 7 to 120 carbon atoms, an aralkyl group having 7 to 120 carbon atoms, or -OR WB , -C(=O)OR WB , or -OC(=O)R WB It is preferable that this is the case. WB This represents an alkyl group having 6 to 20 carbon atoms.

[0155] In polymer particles having the group represented by the above formula Z, from the viewpoint of print resistance, ink transfer, and on-press developability, it is more preferable that W is a divalent group having a hydrophilic structure, Q is a phenylene group, an ester bond, or an amide bond, W is a polyalkylene oxy group, and Y is a polyalkylene oxy group whose terminal end is a hydrogen atom or an alkyl group.

[0156] Furthermore, from the viewpoint of print resistance and on-press developability, the above polymer particles preferably include polymer particles having polymerizable groups, and more preferably include polymer particles having polymerizable groups on the particle surface. Furthermore, from the viewpoint of print resistance, the above polymer particles preferably include polymer particles having hydrophilic groups and polymerizable groups. The polymerizable group described above may be a cationic polymerizable group or a radical polymerizable group, but from the viewpoint of reactivity, a radical polymerizable group is preferable. The polymerizable group is not particularly limited as long as it is polymerizable, but from the viewpoint of reactivity, an ethylenically unsaturated group is preferred, a vinylphenyl group (styryl group), a (meth)acryloxy group, or a (meth)acrylamide group is more preferred, and a (meth)acryloxy group is particularly preferred. Furthermore, it is preferable that the polymer in polymer particles having polymerizable groups has constituent units having polymerizable groups. Furthermore, polymerizable groups may be introduced to the surface of polymer particles by polymer reaction.

[0157] Furthermore, from the viewpoint of print resistance and on-press developability, the image recording layer preferably contains addition polymerization resin particles having a dispersible group as the polymer particles, and more preferably the dispersible group contains a group represented by the formula Z.

[0158] Furthermore, the polymer particles preferably contain a resin having urea bonds, from the viewpoint of print resistance, ink transfer properties, on-press developability, and suppression of developing residue during on-press development. Suitable resins having the above-mentioned urea bond include those described in International Publication No. 2020 / 262692.

[0159] Furthermore, the image recording layer preferably contains thermoplastic resin particles from the viewpoint of print resistance and on-press developability. The thermoplastic resin contained in the thermoplastic resin particles is not particularly limited and includes, for example, polyethylene, polystyrene, polyvinyl chloride, polyvinylidene chloride, methyl poly(meth)acrylate, ethyl poly(meth)acrylate, butyl poly(meth)acrylate, polyacrylonitrile, polyvinyl acetate, and copolymers thereof. The thermoplastic resin may also be in latex form. The thermoplastic resin according to this disclosure is preferably a resin that melts or softens due to the heat generated in the exposure process described later, thereby forming part or all of the hydrophobic film that forms the recording layer.

[0160] From the viewpoint of ink adhesion and print resistance, the above thermoplastic resin preferably includes a resin having structural units formed by aromatic vinyl compounds and structural units having cyano groups. Suitable examples of resins having structural units formed from aromatic vinyl compounds and structural units having cyano groups include those described in International Publication No. 2020 / 262692.

[0161] The thermoplastic resin contained in the above-mentioned thermoplastic resin particles preferably has hydrophilic groups from the viewpoint of print resistance and on-press developability. There are no particular restrictions on hydrophilic groups as long as they have a hydrophilic structure, but examples include acidic groups such as carboxyl groups, hydroxyl groups, amino groups, cyano groups, and polyalkylene oxide structures. The hydrophilic group is preferably a group having a polyalkylene oxide structure, a group having a polyester structure, or a sulfonic acid group, from the viewpoint of print resistance and on-press developability, more preferably a group having a polyalkylene oxide structure or a sulfonic acid group, and even more preferably a group having a polyalkylene oxide structure.

[0162] From the viewpoint of on-air developability, the above polyalkylene oxide structure is preferably a polyethylene oxide structure, a polypropylene oxide structure, or a poly(ethylene oxide / propylene oxide) structure. Furthermore, from the viewpoint of on-air developability, among the hydrophilic groups mentioned above, it is preferable that the polyalkylene oxide structure has a polypropylene oxide structure, and it is more preferable that it has both a polyethylene oxide structure and a polypropylene oxide structure. From the viewpoint of in-flight developability, the number of alkylene oxide structures in the above polyalkylene oxide structure is preferably 2 or more, more preferably 5 or more, even more preferably 5 to 200, and particularly preferably 8 to 150.

[0163] Furthermore, from the viewpoint of on-pressure development, the hydrophilic group is preferably the group represented by the formula Z.

[0164] The glass transition temperature (Tg) of the thermoplastic resin is preferably 60°C to 150°C, more preferably 80°C to 140°C, and even more preferably 90°C to 130°C, from the viewpoint of print resistance and ink adhesion. When thermoplastic resin particles contain two or more types of thermoplastic resins, the value obtained by the FOX formula described later is called the glass transition temperature of the thermoplastic resin.

[0165] In this disclosure, the glass transition temperature of the resin can be measured using differential scanning calorimetry (DSC). The specific measurement method shall be carried out in accordance with the methods described in JIS K 7121 (1987) or JIS K 6240 (2011). In this specification, the glass transition temperature used is the extrapolation glass transition onset temperature (hereinafter sometimes referred to as Tig). The method for measuring the glass transition temperature will be explained in more detail. To determine the glass transition temperature, the apparatus is held at a temperature approximately 50°C lower than the expected Tg of the resin until it stabilizes. Then, the temperature is heated at a heating rate of 20°C / min to a temperature approximately 30°C higher than the temperature at which the glass transition is completed, and a differential thermal analysis (DTA) curve or digital sensor cell (DSC) curve is created. The extrapolation glass transition onset temperature (Tig), i.e., the glass transition temperature Tg as defined herein, is determined as the temperature at the intersection of a straight line drawn by extending the low-temperature baseline of the DTA curve or DSC curve toward the high-temperature side, and a tangent line drawn at the point where the slope of the curve representing the stepwise transition portion of the glass transition is maximum.

[0166] When thermoplastic resin particles contain two or more types of thermoplastic resins, the Tg of the thermoplastic resins contained in the thermoplastic resin particles can be determined as follows. When the Tg of the first thermoplastic resin is denoted as Tg1(K), and the mass fraction of the first thermoplastic resin relative to the total mass of thermoplastic resin components in the thermoplastic resin particle is denoted as W1, and the Tg of the second resin is denoted as Tg2(K), and the mass fraction of the second resin relative to the total mass of thermoplastic resin components in the thermoplastic resin particle is denoted as W2, the Tg0(K) of the thermoplastic resin particle can be estimated according to the following FOX formula. FOX formula: 1 / Tg0=(W1 / Tg1)+(W2 / Tg2) Furthermore, if the thermoplastic resin particles contain three types of resin, or if the pretreatment solution contains three types of thermoplastic resin particles with different types of thermoplastic resin, the Tg of the thermoplastic resin particles can be estimated according to the following formula, as described above, where Tgn(K) is the Tg of the nth resin and Wn is the mass fraction of the nth resin relative to the total mass of the resin components in the thermoplastic resin particles. FOX formula: 1 / Tg0=(W1 / Tg1)+(W2 / Tg2)+(W3 / Tg3)...+(Wn / Tgn)

[0167] For example, the EXSTAR6220 from SII Nanotechnology can be used as a differential scanning calorimeter (DSC).

[0168] From the viewpoint of print resistance, the arithmetic mean particle size of the thermoplastic resin particles is preferably 1 nm or more and 200 nm or less, more preferably 3 nm or more and less than 80 nm, and even more preferably 10 nm or more and 49 nm or less.

[0169] In this disclosure, the arithmetic mean particle size of thermoplastic resin particles refers to the value measured by dynamic light scattering (DLS), unless otherwise specified. The measurement of the arithmetic mean particle size of thermoplastic resin particles by DLS is performed using a Brookhaven BI-90 (manufactured by Brookhaven Instrument Company) in accordance with the manual for the above-mentioned instrument.

[0170] The weight-average molecular weight of the thermoplastic resin contained in the thermoplastic resin particles is preferably 3,000 to 300,000, and more preferably 5,000 to 100,000.

[0171] The method for producing the thermoplastic resin contained in the thermoplastic resin particles is not particularly limited and can be produced by known methods. For example, it can be obtained by polymerizing a styrene compound, an acrylonitrile compound, and, if necessary, at least one compound selected from the group consisting of the above N-vinyl heterocyclic compound, a compound used to form a structural unit having an ethylenically unsaturated group, a compound used to form a structural unit having an acidic group, a compound used to form a structural unit having a hydrophobic group, and a compound used to form other structural units, by a known method.

[0172] Specific examples of thermoplastic resins contained in thermoplastic resin particles include those described in International Publication No. 2020 / 262692.

[0173] The average particle size of the above particles is preferably 0.01 μm to 3.0 μm, more preferably 0.03 μm to 2.0 μm, and even more preferably 0.10 μm to 1.0 μm. Good resolution and stability over time can be obtained within this range. In this disclosure, the average primary particle size of the above particles shall be measured by light scattering, or by taking electron microscope images of the particles, measuring the particle size of a total of 5,000 particles on the image, and calculating the average value. For non-spherical particles, the particle size shall be the particle size of a spherical particle having the same particle area as the particle on the image. Furthermore, unless otherwise specified, the average particle size in this disclosure refers to the volume-average particle size.

[0174] The image recording layer described above may contain one type of particle, particularly polymer particles, or two or more types. Furthermore, from the viewpoint of on-press developability and print durability, the content of particles, particularly polymer particles, in the image recording layer is preferably 5% to 90% by mass, more preferably 10% to 90% by mass, even more preferably 20% to 90% by mass, and particularly preferably 50% to 90% by mass, based on the total mass of the image recording layer. Furthermore, from the viewpoint of on-press developability and print durability, the polymer particle content in the image recording layer is preferably 20% to 100% by mass, more preferably 35% to 100% by mass, even more preferably 50% to 100% by mass, and particularly preferably 80% to 100% by mass, based on the total mass of the components with a molecular weight of 3,000 or more in the image recording layer.

[0175] [Binder polymer] The image recording layer may contain a binder polymer. The polymer particles described above do not fall under the category of the binder polymer. In other words, the binder polymer is a polymer that is not in the form of particles. As the binder polymer, (meth)acrylic resin, polyvinyl acetal resin, or polyurethane resin is preferred.

[0176] In particular, known binder polymers used in the image recording layer of lithographic printing plates can be suitably used as the binder polymer. As an example, a binder polymer used in press-developed lithographic printing plates (hereinafter also referred to as press-developed binder polymer) will be described in detail. For binder polymers used in on-pressure development, binder polymers having alkylene oxide chains are preferred. Binder polymers having alkylene oxide chains may have poly(alkylene oxide) moieties in the main chain or in the side chains. Alternatively, they may be graft polymers having poly(alkylene oxide) in the side chains, or block copolymers composed of blocks of poly(alkylene oxide)-containing repeating units and blocks of (alkylene oxide)-free repeating units. When the main chain contains a poly(alkylene oxide) moiety, polyurethane resin is preferred. When the side chain contains a poly(alkylene oxide) moiety, examples of main chain polymers include (meth)acrylic resin, polyvinyl acetal resin, polyurethane resin, polyurea resin, polyimide resin, polyamide resin, epoxy resin, polystyrene resin, novolac-type phenolic resin, polyester resin, synthetic rubber, and natural rubber, with (meth)acrylic resin being particularly preferred.

[0177] Another preferred example of a binder polymer is a polymer compound (hereinafter also referred to as a star-shaped polymer compound) having a polyfunctional thiol with 6 to 10 functionalities as a core, to which polymer chains are bonded by sulfide bonds, and in which the polymer chains have polymerizable groups. From the viewpoint of curability, star-shaped polymer compounds are preferably those having polymerizable groups such as ethylenically unsaturated groups in the main chain or side chains, more preferably in the side chains. Examples of star-shaped polymer compounds include those described in Japanese Patent Publication No. 2012-148555 or International Publication No. 2020 / 262692.

[0178] The molecular weight of the binder polymer, as calculated by the GPC method in terms of polystyrene, is preferably 2,000 or more, more preferably 5,000 or more, and even more preferably 10,000 to 300,000 in weight-average molecular weight (Mw).

[0179] If necessary, hydrophilic polymers such as polyacrylic acid and polyvinyl alcohol described in Japanese Patent Publication No. 2008-195018 can be used in combination. Furthermore, lipophilic polymers and hydrophilic polymers can also be used in combination.

[0180] Furthermore, the image recording layer preferably contains a polymer having structural units formed from aromatic vinyl compounds, and more preferably contains a polymer having structural units formed from aromatic vinyl compounds and an infrared absorbent that decomposes upon infrared exposure, from the viewpoint of print resistance and on-press developability.

[0181] Furthermore, the binder polymer used in this disclosure preferably has a glass transition temperature (Tg) of 50°C or higher, more preferably 70°C or higher, even more preferably 80°C or higher, and particularly preferably 90°C or higher, from the viewpoint of suppressing a decrease in on-pressure developability over time. Furthermore, regarding the upper limit of the glass transition temperature of the binder polymer, from the viewpoint of how easily water penetrates into the image recording layer, 200°C is preferred, and 120°C or lower is more preferred.

[0182] As the binder polymer having the above-mentioned glass transition temperature, polyvinyl acetal is preferred from the viewpoint of further suppressing the decrease in on-pressure developability over time. Polyvinyl acetal is a resin obtained by acetalizing the hydroxyl groups of polyvinyl alcohol with an aldehyde. In particular, polyvinyl butyral obtained by acetalizing (i.e., butyralizing) the hydroxyl group of polyvinyl alcohol with butyraldehyde is preferred. Furthermore, polyvinyl acetal is preferably made of ethylenically unsaturated groups from the viewpoint of improving print resistance. Suitable examples of polyvinyl acetal include those described in International Publication No. 2020 / 262692.

[0183] The image recording layer in this disclosure preferably contains a resin having fluorine atoms, and more preferably contains a copolymer containing fluoroaliphatic groups. By using a resin containing fluorine atoms, particularly a copolymer containing fluoroaliphatic groups, surface abnormalities caused by foaming during the formation of the image recording layer can be suppressed, improving the texture of the coated surface, and further enhancing the ink adhesion of the formed image recording layer. Furthermore, an image recording layer containing a fluoroaliphatic group-containing copolymer results in higher gradation, high sensitivity to laser light, good fogging due to scattered and reflected light, and excellent print durability, making it possible to obtain a lithographic printing plate.

[0184] As the fluoroaliphatic group-containing copolymer mentioned above, those described in International Publication No. 2020 / 262692 can be suitably used.

[0185] In the image recording layer used in this disclosure, one type of binder polymer may be used alone, or two or more types may be used in combination. The binder polymer can be included in the image recording layer in any amount, but the binder polymer content is preferably 1% to 90% by mass, and more preferably 5% to 80% by mass, relative to the total mass of the image recording layer.

[0186] [Coloring agent] From the viewpoint of visibility, the above image recording layer preferably contains a color developer, and more preferably contains an acid color developer. As used in this disclosure, "chromogen" means a compound that changes the color of an image recording layer by changing color or decolorizing in response to stimuli such as light or acid, and "acid chromogen" means a compound that changes the color of an image recording layer by changing color or decolorizing when heated while accepting an electron-accepting compound (e.g., a proton such as an acid). As an acid chromogen, a colorless compound having a partial skeleton such as a lactone, lactam, salton, spiropyran, ester, or amide, in which these partial skeletons rapidly open or cleave when in contact with an electron-accepting compound, is particularly preferred.

[0187] Specific examples of acid colorants include those described in International Publication No. 2020 / 158138.

[0188] In particular, the colorant used in this disclosure is preferably at least one compound selected from the group consisting of spiropyran compounds, spirooxazine compounds, spirolactone compounds, and spirolactam compounds, from the viewpoint of color development. From the viewpoint of visibility, the hue of the pigment after color development is preferably green, blue, or black.

[0189] Furthermore, the above-mentioned acid colorant preferably contains a leuco dye from the viewpoint of color development and visibility. The above-mentioned leuco dye is not particularly limited as long as it has a leuco structure, but it is preferable that it has a spiro structure, and more preferably that it has a spirolactone ring structure. Furthermore, from the viewpoint of color development and visibility of the exposed area, the leuco dye is preferably a leuco dye having a phthalide structure or a fluorane structure. Furthermore, the leuco dye having the phthalide structure or fluorane structure described above is preferably a compound represented by any of the following formulas (Le-1) to (Le-3), and more preferably a compound represented by the following formula (Le-2), from the viewpoint of color development and visibility of the exposed area.

[0190] [ka]

[0191] In formulas (Le-1) to (Le-3), ERG each independently represents an electron-donating group, X1 to X4 each independently represents a hydrogen atom, a halogen atom, or a dialkylanilino group, and X5 to X 10 Each of the following independently represents a hydrogen atom, a halogen atom, or a monovalent organic group; Y1 and Y2 independently represent C or N; if Y1 is N, X1 is absent; if Y2 is N, X4 is absent; Ra1 represents a hydrogen atom, an alkyl group, or an alkoxy group; and Rb1 to Rb4 independently represent a hydrogen atom, an alkyl group, an aryl group, or a heteroaryl group.

[0192] In the ERG of formulas (Le-1) to (Le-3), the electron-donating group is preferably an amino group, alkylamino group, arylamino group, heteroarylamino group, dialkylamino group, monoalkylmonoarylamino group, monoalkylmonoheteroarylamino group, diarylamino group, diheteroarylamino group, monoarylmonoheteroarylamino group, alkoxy group, allyloxy group, heteroaryloxy group, or alkyl group, more preferably an amino group, alkylamino group, arylamino group, heteroarylamino group, dialkylamino group, monoalkylmonoarylamino group, monoalkylmonoheteroarylamino group, diarylamino group, diheteroarylamino group, monoarylmonoheteroarylamino group, alkoxy group, or allyloxy group, even more preferably a monoalkylmonoarylamino group, diarylamino group, diheteroarylamino group, or monoarylmonoheteroarylamino group, and particularly preferably a monoalkylmonoarylamino group. Furthermore, as the electron-donating group in the above ERG, from the viewpoint of color development and visibility of the exposed area, it is preferable that the disubstituted amino group has an aryl group having a substituent at least one ortho position or a heteroaryl group having a substituent at least one ortho position, more preferably that the disubstituted amino group has a substituent at least one ortho position and a phenyl group having an electron-donating group at the para position, even more preferably that the amino group has a substituent at least one ortho position and a phenyl group having an electron-donating group at the para position and an aryl group or heteroaryl group, and particularly preferably that the amino group has a substituent at least one ortho position and a phenyl group having an electron-donating group at the para position and an aryl group having an electron-donating group or a heteroaryl group having an electron-donating group. In this disclosure, the ortho position in an aryl group or heteroaryl group other than a phenyl group refers to the bond position adjacent to position 1 (for example, position 2) when the bond position to another structure of the aryl group or heteroaryl group is considered position 1. Furthermore, from the viewpoint of color development and visibility of the exposed area, the electron-donating group of the aryl group or heteroaryl group is preferably an amino group, alkylamino group, arylamino group, heteroarylamino group, dialkylamino group, monoalkylmonoarylamino group, monoalkylmonoheteroarylamino group, diarylamino group, diheteroarylamino group, monoarylmonoheteroarylamino group, alkoxy group, allyloxy group, heteroaryloxy group, or alkyl group, more preferably an alkoxy group, allyloxy group, heteroaryloxy group, or alkyl group, and particularly preferably an alkoxy group.

[0193] In formulas (Le-1) to (Le-3), X1 to X4 are each independently preferably hydrogen atoms or chlorine atoms, and more preferably hydrogen atoms, from the viewpoint of color development and visibility of the exposed area. X5~X in equation (Le-2) or equation (Le-3) 10Each of these groups is preferably, from the viewpoint of color development and visibility of the exposed area, a hydrogen atom, halogen atom, alkyl group, aryl group, amino group, alkylamino group, arylamino group, heteroarylamino group, dialkylamino group, monoalkylmonoarylamino group, monoalkylmonoheteroarylamino group, diarylamino group, diheteroarylamino group, monoarylmonoheteroarylamino group, hydroxyl group, alkoxy group, allyloxy group, heteroallyloxy group, acyl group, alkoxycarbonyl group, allyloxycarbonyl group, heteroallyloxycarbonyl group, or cyano group; more preferably a hydrogen atom, halogen atom, alkyl group, aryl group, alkoxy group, or allyloxy group; even more preferably a hydrogen atom, halogen atom, alkyl group, or aryl group; and particularly preferably a hydrogen atom. In formulas (Le-1) to (Le-3), at least one of Y1 and Y2 is preferably C, and more preferably both Y1 and Y2 are C, from the viewpoint of color development and visibility of the exposed area. In formulas (Le-1) to (Le-3), Ra1 is preferably an alkyl group or an alkoxy group, more preferably an alkoxy group, and particularly preferably a methoxy group, from the viewpoint of color development and visibility of the exposed area. In formulas (Le-1) to (Le-3), Rb1 to Rb4 are each independently preferably a hydrogen atom or an alkyl group, more preferably an alkyl group, and particularly preferably a methyl group, from the viewpoint of color development and visibility of the exposed area.

[0194] Furthermore, the leuco dye having the phthalide structure or fluorane structure described above is more preferably a compound represented by any of the following formulas (Le-4) to (Le-6), and even more preferably a compound represented by the following formula (Le-5), from the viewpoint of color development and visibility of the exposed area.

[0195] [ka]

[0196] In formulas (Le-4) to (Le-6), ERG independently represents an electron-donating group, X1 to X4 independently represent a hydrogen atom, a halogen atom, or a dialkylanilino group, Y1 and Y2 independently represent C or N, if Y1 is N, then X1 is absent, if Y2 is N, then X4 is absent, Ra1 represents a hydrogen atom, an alkyl group, or an alkoxy group, and Rb1 to Rb4 independently represent a hydrogen atom, an alkyl group, an aryl group, or a heteroaryl group.

[0197] In equations (Le-4) to (Le-6), ERG, X1 to X4, Y1, Y2, Ra1, and Rb1 to Rb4 are equivalent to ERG, X1 to X4, Y1, Y2, Ra1, and Rb1 to Rb4 in equations (Le-1) to (Le-3), and the same applies to the preferred embodiment.

[0198] Furthermore, the leuco dye having the phthalide structure or fluorane structure described above is more preferably a compound represented by any of the following formulas (Le-7) to (Le-9), and is particularly preferably a compound represented by the following formula (Le-8), from the viewpoint of color development and visibility of the exposed area.

[0199] [ka]

[0200] In formulas (Le-7) to (Le-9), X1 to X4 each independently represent a hydrogen atom, a halogen atom, or a dialkylanilino group; Y1 and Y2 each independently represent C or N; if Y1 is N, X1 is absent; if Y2 is N, X4 is absent; Ra1 to Ra4 each independently represent a hydrogen atom, an alkyl group, or an alkoxy group; Rb1 to Rb4 each independently represent a hydrogen atom, an alkyl group, an aryl group, or a heteroaryl group; and Rc1 and Rc2 each independently represent an aryl group or a heteroaryl group.

[0201] In equations (Le-7) to (Le-9), X1 to X4, Y1 and Y2 are equivalent to X1 to X4, Y1 and Y2 in equations (Le-1) to (Le-3), and the preferred embodiment is also equivalent. In formula (Le-7) or formula (Le-9), Ra1 to Ra4 are each independently preferably alkyl groups or alkoxy groups, more preferably alkoxy groups, and particularly preferably methoxy groups, from the viewpoint of color development and visibility of the exposed area. In formulas (Le-7) to (Le-9), Rb1 to Rb4 are each independently preferably substituted with a hydrogen atom, an alkyl group, or an alkoxy group, more preferably an alkyl group, and particularly preferably a methyl group, from the viewpoint of color development and visibility of the exposed area. In formula (Le-8), Rc1 and Rc2 are each preferably a phenyl group or an alkylphenyl group, and more preferably a phenyl group, from the viewpoint of color development and visibility of the exposed area. Furthermore, Rc1 and Rc2 in formula (Le-8) are each preferably, from the viewpoint of color development and visibility of the exposed area, an aryl group having a substituent at least one ortho position, or a heteroaryl group having a substituent at least one ortho position, more preferably an aryl group having a substituent at least one ortho position, even more preferably a phenyl group having a substituent at least one ortho position, and particularly preferably a phenyl group having a substituent at least one ortho position and an electron-donating group at the para position. Examples of substituents in Rc1 and Rc2 are those described later. Furthermore, in formula (Le-8), from the viewpoint of color development and visibility of the exposed area, it is preferable that X1 to X4 are hydrogen atoms and Y1 and Y2 are carbon. Furthermore, in formula (Le-8), from the viewpoint of color development and visibility of the exposed area, it is preferable that Rb1 and Rb2 are each independently substituted with an alkyl group or an alkoxy group aryl group. Furthermore, in formula (Le-8), from the viewpoint of color development and visibility of the exposed area, it is preferable that Rb1 and Rb2 are each independently an aryl group or a heteroaryl group, more preferably an aryl group, even more preferably an aryl group having an electron-donating group, and particularly preferably a phenyl group having an electron-donating group at the para position. Furthermore, the electron-donating groups in Rb1, Rb2, Rc1, and Rc2 are preferably amino groups, alkylamino groups, arylamino groups, heteroarylamino groups, dialkylamino groups, monoalkylmonoarylamino groups, monoalkylmonoheteroarylamino groups, diarylamino groups, diheteroarylamino groups, monoarylmonoheteroarylamino groups, alkoxy groups, allyloxy groups, heteroaryloxy groups, or alkyl groups, more preferably alkoxy groups, allyloxy groups, heteroaryloxy groups, or alkyl groups, and particularly preferably alkoxy groups.

[0202] Furthermore, as an acid colorant, it is preferable to include a compound represented by the following formula (Le-10) from the viewpoint of color development and visibility of the exposed area.

[0203] [ka]

[0204] In formula (Le-10), each Ar1 independently represents an aryl group or a heteroaryl group, and each Ar2 independently represents an aryl group having a substituent at least one ortho position, or a heteroaryl group having a substituent at least one ortho position.

[0205] In equation (Le-10), Ar1 is equivalent to Rb1 and Rb2 in equations (Le-7) to (Le-9), and the same applies to the preferred embodiment. In equation (Le-10), Ar2 is synonymous with Rc1 and Rc2 in equations (Le-7) to (Le-9), and the preferred embodiment is similar.

[0206] Furthermore, as an acid colorant, it is preferable to include a compound represented by the following formula (Le-11) from the viewpoint of color development and visibility of the exposed area.

[0207] [ka]

[0208] In formula (Le-11), ERG each independently represents an electron-donating group, n11 represents an integer from 1 to 5, X1 to X4 each independently represents a hydrogen atom, a halogen atom, or a dialkylanilino group, and X5 to X 10 Each of the following independently represents a hydrogen atom, a halogen atom, or a monovalent organic group; Y1 and Y2 independently represent C or N; if Y1 is N, X1 is absent; if Y2 is N, X4 is absent; Ra1 represents a hydrogen atom, an alkyl group, or an alkoxy group; and Rb2 and Rb4 independently represent a hydrogen atom, an alkyl group, an aryl group, or a heteroaryl group.

[0209] In formula (Le-11), ERG, X1-X4, Y1, Y2, Ra1, Rb2, and Rb4 are equivalent to ERG, X1-X4, Y1, Y2, Ra1, Rb2, and Rb4 in formulas (Le-1) to (Le-3), respectively, and the same applies to preferred embodiments. In equation (Le-11), n11 is preferably an integer between 1 and 3, and more preferably 1 or 2.

[0210] The alkyl groups in formulas (Le-1) to (Le-9) or (Le-11) may be linear, branched, or have a ring structure. Furthermore, the number of carbon atoms in the alkyl group in formulas (Le-1) to (Le-9) or (Le-11) is preferably 1 to 20, more preferably 1 to 8, even more preferably 1 to 4, and particularly preferably 1 or 2. In formulas (Le-1) to (Le-11), the number of carbon atoms in the aryl group is preferably 6 to 20, more preferably 6 to 10, and particularly preferably 6 to 8. Specific examples of aryl groups in formulas (Le-1) to (Le-11) include phenyl groups, naphthyl groups, anthracenyl groups, and phenantrenyl groups, which may have substituents. Specific examples of heteroaryl groups in formulas (Le-1) to (Le-11) include furyl groups, pyridyl groups, pyrimidyl groups, pyrazoyl groups, and thiophenyl groups, which may have substituents.

[0211] Furthermore, each of the monovalent organic groups, alkyl groups, aryl groups, heteroaryl groups, dialkylanilino groups, alkylamino groups, alkoxy groups, etc. in formulas (Le-1) to (Le-11) may have substituents. Examples of substituents include alkyl groups, aryl groups, heteroaryl groups, halogen atoms, amino groups, alkylamino groups, arylamino groups, heteroarylamino groups, dialkylamino groups, monoalkylmonoarylamino groups, monoalkylmonoheteroarylamino groups, diarylamino groups, diheteroarylamino groups, monoarylmonoheteroarylamino groups, hydroxyl groups, alkoxy groups, allyloxy groups, heteroallyloxy groups, acyl groups, alkoxycarbonyl groups, allyloxycarbonyl groups, heteroallyloxycarbonyl groups, cyano groups, etc. Moreover, these substituents may be further substituted with other substituents.

[0212] The following compounds are examples of leuco dyes having the above-mentioned phthalide structure or fluorane structure that are preferably used.

[0213] [ka]

[0214] [ka]

[0215]

change

[0216]

change

[0217]

change

[0218]

change

[0219]

change

[0220]

change

[0221]

change

[0222] It is also possible to use commercially available colorants, such as ETAC, RED500, RED520, CVL, S-205, BLACK305, BLACK400, BLACK100, BLACK500, H-7001, GREEN300, NIRBLACK78, BLUE220, H-3035, BLUE203, ATP, H-1046, H-2114 (all manufactured by Fukui Yamada Chemical Industry Co., Ltd.), ORANGE-DCF, and Vermilio. Examples include n-DCF, PINK-DCF, RED-DCF, BLMB, CVL, GREEN-DCF, TH-107 (all manufactured by Hodogaya Chemical Co., Ltd.), ODB, ODB-2, ODB-4, ODB-250, ODB-BlackXV, Blue-63, Blue-502, GN-169, GN-2, Green-118, Red-40, Red-8 (all manufactured by Yamamoto Kasei Co., Ltd.), and Crystal Violet Lactone (manufactured by Tokyo Chemical Industry Co., Ltd.). Among these commercially available products, ETAC, S-205, BLACK305, BLACK400, BLACK100, BLACK500, H-7001, GREEN300, NIRBLACK78, H-3035, ATP, H-1046, H-2114, GREEN-DCF, Blue-63, GN-169, and Crystal Violet Lactone are preferred because the resulting film has good visible light absorption.

[0223] These colorants may be used individually or in combination of two or more components. The content of the colorant is preferably 0.5% to 10% by mass, and more preferably 1% to 5% by mass, relative to the total mass of the image recording layer.

[0224] [Chain transport agent] The image recording layer used in this disclosure may contain a chain transfer agent. The chain transfer agent contributes to improving the print durability of the lithographic printing plate. As the chain transfer agent, thiol compounds are preferred, thiol compounds with 7 or more carbon atoms are more preferred from the viewpoint of boiling point (low volatility), and compounds having a mercapto group on the aromatic ring (aromatic thiol compounds) are even more preferred. The above thiol compounds are preferably monofunctional thiol compounds. Specific examples of chain transfer agents include those described in International Publication No. 2020 / 262692.

[0225] Chain transfer agents may be added individually or in combination of two or more types. The content of the chain transfer agent is preferably 0.01% to 50% by mass, more preferably 0.05% to 40% by mass, and even more preferably 0.1% to 30% by mass, relative to the total mass of the image recording layer.

[0226] [Lipid-reducing agent] The image recording layer preferably further contains an oil-sensitive agent to improve ink adhesion. The lipid-reducing agent is preferably of an SP value of less than 18.0, more preferably between 14 and less than 18, even more preferably between 15 and 17, and particularly preferably between 16 and 16.9. Furthermore, the lipid-reducing agent may be a compound with a molecular weight (or weight-average molecular weight if there is a molecular weight distribution) of 2,000 or more, or a compound with a molecular weight of less than 2,000.

[0227] SP values ​​(solubility parameters, unit: MPa) in this disclosure 1 / 2 The Hansen solubility parameter shall be used. The Hansen solubility parameter is a representation of the solubility parameter introduced by Hildebrand, divided into three components: dispersion term δd, polarity term δp, and hydrogen bonding term δh, and expressed in three-dimensional space. In this disclosure, the SP value is expressed as δ(unit: (MPa)). 1 / 2 It is expressed as ) and the value calculated using the following formula is used. δ (MPa) 1 / 2 =(δd 2 +δp 2+δh 2 ) 1 / 2 Furthermore, the dispersion term δd, polarity term δp, and hydrogen bonding term δh have been extensively determined by Hansen and his successors, and are described in detail in the Polymer Handbook (fourth edition), VII-698~711. Furthermore, in this disclosure, the SP value of the polymer is calculated from the molecular structure of the polymer using the Hoy method described in the Polymer Handbook fourth edition.

[0228] Examples of the above-mentioned lipid-reducing agents include onium salt compounds, nitrogen-containing low molecular weight compounds, and ammonium compounds such as ammonium group-containing polymers. In particular, when inorganic layered compounds are included in the outermost layer, these compounds function as surface coating agents for the inorganic layered compounds, thereby suppressing the decrease in ink adhesion during printing caused by the inorganic layered compounds.

[0229] Furthermore, from the viewpoint of meat-adhering properties, the fat-sensing agent is preferably an onium salt compound. Examples of onium salt compounds include phosphonium compounds, ammonium compounds, and sulfonium compounds. From the above viewpoint, at least one selected from the group consisting of phosphonium compounds and ammonium compounds is preferred as the onium salt compound. Furthermore, the onium salt compounds in the development accelerators or electron-accepting polymerization initiators, as described later, are compounds with an SP value exceeding 18 and are not included in the category of lipid-sensitive agents.

[0230] Examples of phosphonium compounds include those described in Japanese Patent Publication No. 2006-297907 and Japanese Patent Publication No. 2007-50660. Specific examples include 1,4-bis(triphenylphosphonio)butane=di(hexafluorophosphonate), 1,7-bis(triphenylphosphonio)heptane=sulfate, and 1,9-bis(triphenylphosphonio)nonane=naphthalene-2,7-disulfonate.

[0231] Preferred ammonium compounds include nitrogen-containing low molecular weight compounds and ammonium group-containing polymers.

[0232] Examples of nitrogen-containing low molecular weight compounds include amine salts and quaternary ammonium salts. Also included are imidazolinium salts, benzimidazolinium salts, pyridinium salts, and quinolinium salts. Among these, quaternary ammonium salts and pyridinium salts are preferred. Specific examples include tetramethylammonium = hexafluorophosphate, tetrabutylammonium = hexafluorophosphate, dodecyltrimethylammonium = p-toluenesulfonate, benzyltriethylammonium = hexafluorophosphate, benzyldimethyloctylammonium = hexafluorophosphate, benzyldimethyldodecylammonium = hexafluorophosphate, compounds described in paragraphs 0021 to 0037 of Japanese Patent Publication No. 2008-284858, compounds described in paragraphs 0030 to 0057 of Japanese Patent Publication No. 2009-90645, and the like.

[0233] The ammonium group-containing polymer only needs to have an ammonium group in its structure, and a polymer containing 5 mol% to 80 mol% of (meth)acrylate having an ammonium group in its side chain as a copolymer component is preferred. Specific examples include the polymer described in paragraphs 0089 to 0105 of Japanese Patent Application Publication No. 2009-208458.

[0234] The ammonium salt-containing polymer preferably has a reduced viscosity (unit: ml / g) value in the range of 5 to 120, more preferably in the range of 10 to 110, and particularly preferably in the range of 15 to 100, determined according to the measurement method described in Japanese Patent Publication No. 2009-208458. When the above reduced viscosity is converted to weight-average molecular weight (Mw), it is preferably 10,000 to 150,000, more preferably 17,000 to 140,000, and particularly preferably 20,000 to 130,000.

[0235] The following are specific examples of ammonium group-containing polymers. (1) 2-(trimethylammonio)ethyl methacrylate = p-toluenesulfonate / 3,6-dioxaheptyl methacrylate copolymer (molar ratio 10 / 90, Mw 45,000) (2) 2-(trimethylammonio)ethyl methacrylate = hexafluorophosphate / 3,6-dioxaheptyl methacrylate copolymer (molar ratio 20 / 80, Mw 60,000) (3) 2-(ethyldimethylammonio)ethyl methacrylate = p-toluenesulfonate / hexyl methacrylate copolymer (molar ratio 30 / 70, Mw 45,000) (4) 2-(trimethylammonio)ethyl methacrylate = hexafluorophosphate / 2-ethylhexyl methacrylate copolymer (molar ratio 20 / 80, Mw 60,000) (5) 2-(trimethylammonio)ethyl methacrylate = methyl sulfate / hexyl methacrylate copolymer (molar ratio 40 / 60, Mw 70,000) (6) 2-(butyldimethylammonio)ethyl methacrylate = hexafluorophosphate / 3,6-dioxaheptyl methacrylate copolymer (molar ratio 25 / 75, Mw 65,000) (7) 2-(butyldimethylammonio)ethyl acrylate = hexafluorophosphate / 3,6-dioxaheptyl methacrylate copolymer (molar ratio 20 / 80, Mw 65,000) (8) 2-(butyldimethylammonio)ethyl methacrylate = 13-ethyl-5,8,11-trioxa-1-heptadecanesulfonate / 3,6-dioxaheptyl methacrylate copolymer (molar ratio 20 / 80, Mw 75,000)

[0236] The amount of the lipid-sensitive agent is preferably 1% to 40.0% by mass, more preferably 2% to 25.0% by mass, and even more preferably 3% to 20.0% by mass, relative to the total mass of the image recording layer.

[0237] The image recording layer may contain one type of lipid-sensitive agent alone, or two or more types in combination. One preferred embodiment of the image recording layer used in this disclosure is an embodiment that contains two or more compounds as an oil-sensitive agent. Specifically, in order to achieve both on-pressure developability and ink-bearing properties, the image recording layer used in this disclosure preferably uses a combination of a phosphonium compound, a nitrogen-containing low molecular weight compound, and an ammonium group-containing polymer as an oil-sensitive agent, and more preferably uses a combination of a phosphonium compound, a quaternary ammonium salt, and an ammonium group-containing polymer.

[0238] [Developing accelerator] The image recording layer used in this disclosure preferably further contains a development accelerator. The development accelerator preferably has a polarity term value of SP of 6.0 to 26.0, more preferably 6.2 to 24.0, even more preferably 6.3 to 23.5, and particularly preferably 6.4 to 22.0.

[0239] SP values ​​(solubility parameters, unit: cal / cm³) in this disclosure 3 ) 1 / 2 The value of the polarity term in ) shall be the value of the polarity term δp in the Hansen solubility parameter. The Hansen solubility parameter is a representation in three dimensions of the solubility parameter introduced by Hildebrand, divided into three components: dispersion term δd, polarity term δp, and hydrogen bonding term δh. In this disclosure, the above polarity term δp is used. δp[cal / cm 3 ] is the Hansen solubility parameter, dipole force term, V [cal / cm 3 ] is the molar volume, and μ[D] is the dipole moment. For δp, the following simplified formula by Hansen and Beerbower is generally used.

[0240]

number

[0241] The development accelerator is preferably a hydrophilic polymer compound or a hydrophilic low-molecular-weight compound. In this disclosure, hydrophilicity means that the polarity term of the SP value is between 6.0 and 26.0, a hydrophilic polymer compound means a compound with a molecular weight (or weight-average molecular weight if it has a molecular weight distribution) of 3,000 or more, and a hydrophilic low molecular weight compound means a compound with a molecular weight (or weight-average molecular weight if it has a molecular weight distribution) of less than 3,000.

[0242] Examples of hydrophilic polymer compounds include cellulose compounds, with cellulose compounds being preferred. Examples of cellulose compounds include cellulose, or compounds in which at least a portion of cellulose has been modified (modified cellulose compounds), with modified cellulose compounds being preferred. Preferred modified cellulose compounds include compounds in which at least a portion of the hydroxyl groups of cellulose are substituted with at least one group selected from the group consisting of alkyl groups and hydroxyalkyl groups. The degree of substitution in a compound in which at least a portion of the hydroxyl groups of the cellulose described above is substituted with at least one group selected from the group consisting of alkyl groups and hydroxyalkyl groups is preferably 0.1 to 6.0, and more preferably 1 to 4. As the modified cellulose compound, alkylcellulose compounds or hydroxyalkylcellulose compounds are preferred, and hydroxyalkylcellulose compounds are more preferred. Methylcellulose is a preferred example of an alkylcellulose compound. Hydroxypropylcellulose is a preferred example of a hydroxyalkylcellulose compound.

[0243] The molecular weight (or weight-average molecular weight if it has a molecular weight distribution) of the hydrophilic polymer compound is preferably 3,000 to 5,000,000, and more preferably 5,000 to 200,000.

[0244] Examples of hydrophilic low molecular weight compounds include glycol compounds, polyol compounds, organic amine compounds, organic sulfonic acid compounds, organic sulfamine compounds, organic sulfuric acid compounds, organic phosphonic acid compounds, organic carboxylic acid compounds, and betaine compounds, with polyol compounds, organic sulfonic acid compounds, or betaine compounds being preferred.

[0245] Examples of glycol compounds include glycols such as ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dipropylene glycol, and tripropylene glycol, as well as ether or ester derivatives of these compounds. Examples of polyol compounds include glycerin, pentaerythritol, and tris(2-hydroxyethyl) isocyanurate. Examples of organic amine compounds include triethanolamine, diethanolamine, monoethanolamine, and their salts. Examples of organic sulfonic acid compounds include alkyl sulfonic acid, toluene sulfonic acid, benzene sulfonic acid, and their salts, with alkyl sulfonic acid having 1 to 10 carbon atoms in the alkyl group being preferred. Examples of organic sulfamine compounds include alkyl sulfamic acids and their salts. Examples of organic sulfuric acid compounds include alkyl sulfuric acid, alkyl ether sulfuric acid, and their salts. Examples of organic phosphonic acid compounds include phenylphosphonic acid and its salts. Examples of organic carboxylic acid compounds include tartaric acid, oxalic acid, citric acid, malic acid, lactic acid, gluconic acid, and their salts. Examples of betaine compounds include phosphobetaine compounds, sulfobetaine compounds, and carboxybetaine compounds, with trimethylglycine being a preferred example.

[0246] The molecular weight (or weight-average molecular weight if a molecular weight distribution exists) of the hydrophilic low molecular weight compound is preferably 100 or more and less than 3,000, and more preferably 300 to 2,500.

[0247] The development accelerator is preferably a compound having a cyclic structure. The cyclic structure is not particularly limited, but examples include glucose rings, isocyanuric rings, aromatic rings, and aliphatic rings, in which at least some of the hydroxyl groups may be substituted, with glucose rings or isocyanuric rings being preferred. Examples of compounds containing a glucose ring include the cellulose compounds mentioned above. Examples of compounds having an isocyanuric ring include the aforementioned tris(2-hydroxyethyl)isocyanurate. Examples of compounds having an aromatic ring include the aforementioned toluenesulfonic acid and benzenesulfonic acid. Examples of compounds having an aliphatic ring include the alkyl sulfates mentioned above, in which the alkyl group has a ring structure.

[0248] Furthermore, the compound having the above cyclic structure preferably has a hydroxyl group. Preferred examples of compounds having a hydroxyl group and a cyclic structure include the cellulose compounds mentioned above and the tris(2-hydroxyethyl) isocyanurate mentioned above.

[0249] Furthermore, the development accelerator is preferably an onium salt compound. Examples of onium salt compounds include ammonium compounds and sulfonium compounds, with ammonium compounds being preferred. Examples of onium salt compounds used as development accelerators include trimethylglycine. Furthermore, the onium salt compounds in the above-mentioned electron-accepting polymerization initiators are compounds whose SP value polarity term is not between 6.0 and 26.0, and are therefore not included in the development accelerators.

[0250] The image recording layer may contain one type of development accelerator alone, or two or more types in combination. One preferred embodiment of the image recording layer used in this disclosure is an embodiment that contains two or more compounds as a development accelerator. Specifically, the image recording layer used in this disclosure preferably contains, from the viewpoint of on-pressure developability and ink transfer, the above polyol compound and the above betaine compound, the above betaine compound and the above organic sulfonic acid compound, or the above polyol compound and the above organic sulfonic acid compound as a development accelerator.

[0251] The content of the development accelerator relative to the total mass of the image recording layer is preferably 0.1% by mass or more and 20% by mass or less, more preferably 0.5% by mass or more and 15% by mass or less, and even more preferably 1% by mass or more and 10% by mass or less.

[0252] [Color-forming compound] In the on-press type lithographic printing plate master according to this disclosure, it is preferable that the image recording layer contains a color-producing compound capable of reacting with decomposition products generated by exposure of the image recording layer. In this disclosure, "color reaction" refers to a chemical reaction that involves the phenomenon of color development or discoloration. There are no particular limitations on the decomposition products generated by exposure of the image recording layer, but from the viewpoint of visibility of the exposed area, it is preferable that they be decomposition products of a polymerization initiator or decomposition products of an infrared absorber, more preferably decomposition products of a polymerization initiator, and particularly preferably decomposition products of an electron-donating polymerization initiator. Furthermore, the decomposition products generated by exposure of the image recording layer include not only the decomposition products decomposed by exposure of the image recording layer, but also compounds formed by further decomposition or modification of the above-mentioned decomposition products. Furthermore, from the viewpoint of visibility of the exposed area, the above color reaction is preferably a complex formation reaction, and more preferably a boron complex formation reaction.

[0253] An example of the above color reaction is shown below. The following shows the color reaction when curcumin is used as the color-developing compound, and sodium tetraphenylborate decomposes to produce boric acid as a decomposition product upon exposure of the image recording layer. Due to keto-enol tautomerism, the enol form of curcumin is produced in equilibrium. The enol form reacts with boric acid to produce the boron complex shown below, resulting in a color reaction from curcumin (yellow) to the boron complex (red). Furthermore, although the following shows an example of hydrolysis to boric acid, for example, diphenylmonohydroxyboron, monophenyldihydroxyboron, etc., may form a complex with curcumin, or triphenylboron may coordinate to enol-type curcumin as a zero-valent ligand to form a complex.

[0254] [ka]

[0255] The above-mentioned color-producing compound is preferably a compound having one or more ketone structures from the viewpoint of visibility of the exposed area and tonal reproducibility, more preferably a compound having one or more 1,3-diketone structures, β-hydroxyketone structures, or β-aminoketone structures, even more preferably a compound having one or more 1,3-diketone structures or β-hydroxyketone structures, and particularly preferably a compound having one or more 1,3-diketone structures. Furthermore, examples of the above-mentioned color-producing compounds include compounds having one or more 1-hydroxy-3-amino or 1-hydroxy-3-imino structures. Furthermore, the above-mentioned color-producing compound is preferably a compound having an aromatic ring structure, more preferably a compound having two or more aromatic ring structures, even more preferably a compound having two to four aromatic ring structures, and particularly preferably a compound having two aromatic ring structures. As for the aromatic ring structure, from the viewpoint of visibility of the exposed area and tone reproducibility, at least one selected from the group consisting of a benzene ring structure and a naphthalene ring structure is preferred, and a benzene ring structure is more preferred. Furthermore, the above-mentioned color-producing compound may be a salt or a hydrate. Furthermore, when the above-mentioned color-producing compound reacts with decomposition products generated by exposure of the image recording layer to form a complex, the complex may be monodentate or polydentate. However, from the viewpoint of complex formation, visibility of the exposed area, and tone reproducibility, a polydentate ligand is preferred, a bidentate to hexadentate ligand is more preferred, a bidentate to quadentate ligand is even more preferred, a bidentate or tridentate ligand is particularly preferred, and a bidentate ligand is most preferred.

[0256] The on-press type lithographic printing plate master according to this disclosure preferably contains a compound represented by the following formula 1C or formula 2C as the color-developing compound, and more preferably contains a compound represented by the following formula 1C, from the viewpoint of visibility of the exposed area and tonal reproducibility. Furthermore, in the on-press type lithographic printing plate master according to this disclosure, after exposure, it is preferable that a compound represented by the following formula 1C or formula 2C reacts with the decomposition products generated by exposure of the image recording layer to form a complex having the compound represented by the following formula 1C or formula 2C as a zero-valent ligand or an anion obtained by removing one hydrogen atom from the compound represented by the following formula 1C or formula 2C as a monovalent ligand, and it is more preferable that the compound represented by the following formula 1C or formula 2C reacts with the decomposition products generated by exposure of the image recording layer to form a complex having an anion obtained by removing one hydrogen atom from the compound represented by the following formula 1C or formula 2C as a monovalent ligand.

[0257] [ka]

[0258] In equations 1C and 2C, R 1C ~R 4C Each of these independently represents a monovalent organic group, L1C and L 2C Each of these independently represents a divalent organic group, A C is OH or NR 5C R 6C Represents R 5C and R 6C Each of these independently represents a hydrogen atom or a monovalent organic group, and the dotted line portion represents a portion that may be a double bond.

[0259] In equation 1C, R 1C , L 1C , and R 2C Two or more of these may be bonded together to form a ring structure. In equation 2C, R 3C , L 2C , R 4C , R 5C , and R 6C Two or more of these may be bonded together to form a ring structure. R in Equation 1C 1C and R 2C Each of these groups is preferably a monovalent organic group having an aromatic ring, more preferably an aryl group or an alkenyl group having an aryl group, and particularly preferably a 2-aryl vinyl group, from the viewpoint of visibility of the exposed area and tone reproducibility. Furthermore, the above-mentioned aryl group may have substituents, and from the viewpoint of visibility of the exposed area and tone reproducibility, it is preferable that the substituent is an aryl group having one or more groups selected from the group consisting of hydroxyl groups and alkoxy groups, more preferably a phenyl group having one or more groups selected from the group consisting of hydroxyl groups and alkoxy groups, and particularly preferable a phenyl group having hydroxyl groups and alkoxy groups as substituents. Furthermore, R in equation 1C 1C and R 2C The number of carbon atoms in each component is preferably 6 to 50, more preferably 6 to 20, and particularly preferably 8 to 20. Also, R in equation 1C 1C and R 2C It is preferable that they are the same group. L in Equation 1C 1C From the viewpoint of visibility of the exposed area and tonal reproducibility, it is preferable that the group is an alkylene group or an alkylene group having an acyloxy group, and more preferably a methylene group or an acyloxymethylene group. Furthermore, from the viewpoint of visibility of the exposed area, the acyloxy group is preferably an acyloxy group having 1 to 10 carbon atoms, more preferably an acyloxy group having 1 to 4 carbon atoms, and particularly preferably an acetoxy group.

[0260] R in Equation 2C 3C From the viewpoint of visibility of the exposed area and tone reproducibility, it is preferable that the group is a monovalent organic group having an aromatic ring, and more preferably an aryl group or an alkenyl group having an aryl group. In formula 2C, from the viewpoint of visibility of the exposed area and tone reproducibility, L 2C and R 4C It is preferable that the two are bonded together to form an aromatic ring, L 2C and R 4C It is more preferable that the two are bonded together to form a benzene ring. Also, R in equation 2C 3C and R 4C The number of carbon atoms in each atom is preferably 6 to 50, more preferably 6 to 30, and particularly preferably 6 to 20. L in equation 2C 2C R 4C If not bonded, from the viewpoint of visibility of the exposed area and tone reproducibility, it is preferable that the group be an alkylene group or an alkylene group having an acyloxy group, and more preferably a methylene group or an acyloxymethylene group. Furthermore, from the viewpoint of visibility of the exposed area, the acyloxy group is preferably an acyloxy group having 1 to 10 carbon atoms, more preferably an acyloxy group having 1 to 4 carbon atoms, and particularly preferably an acetoxy group. Also, L in equation 2C 2C R 4CIt is preferable that it is bonded to and forms a ring member of the aromatic ring structure. The compound represented by formula 2C is preferably a compound having a 1-hydroxyanthraquinone structure or a 1-aminoanthraquinone structure, and more preferably a compound having a 1-hydroxyanthraquinone structure, from the viewpoint of visibility of the exposed area and tone reproducibility. A in equation 2C C From the viewpoint of visibility of the exposed area and tone reproducibility, OH or NHR 6C It is preferable that it be OH, and more preferably OH. NR of Equation 2C 5C R 6C In R 5C It is preferably a hydrogen atom, an alkyl group, or an aryl group, more preferably a hydrogen atom or an alkyl group, and particularly preferably a hydrogen atom. NR of Equation 2C 5C R 6C In R 6C The element is preferably a hydrogen atom, an alkyl group, or an anthraquinolyl group, more preferably an anthraquinolyl group, and particularly preferably a 1-anthraquinolyl group.

[0261] Specific examples of the above-mentioned color-producing compounds include, for example, curcumin, demethoxycurcumin, alizarin, iminodianthraquinone, carmic acid, azomethine H, 1,3-bis(4-methoxyphenyl)-1,3-propanedione, 4-methoxychalcone, 1,3-bis(4-dimethylaminophenyl)-1,3-propanedione, and acetoxycurcumin.

[0262] The above-mentioned color-developing compounds may be used individually or in combination of two or more. Furthermore, the compound represented by formula 1C or formula 2C may be used alone or in combination of two or more compounds. Furthermore, the above complex may be formed by one type only, or by two or more types. From the viewpoints of the visibility of exposed areas and tone reproducibility, the content of the above chromogenic compound is preferably 0.001% by mass to 5% by mass, more preferably 0.01% by mass to 3% by mass, still more preferably 0.05% by mass to 2.5% by mass, and particularly preferably 0.05% by mass to 1.0% by mass, relative to the total mass of the above image recording layer.

[0263] The content M of the above chromogenic compound in the above image recording layer C and the content M of a polymerization initiator to be described later I preferably have a molar ratio of M C / M I =0.001 to 1, more preferably M C / M I =0.01 to 0.8, and particularly preferably M C / M I =0.05 to 0.5. Further, the content M of the above chromogenic compound in the above image recording layer C and the content M of an electron-donating polymerization initiator to be described later DI preferably have a molar ratio of M C / M DI =0.001 to 1.5, more preferably M C / M DI =0.01 to 1, and particularly preferably M C / M DI =0.05 to 0.8.

[0264] [Oil Agent] The above image recording layer preferably contains an oil agent. The oil agent in the present disclosure refers to a hydrophobic compound that is in a liquid state at 80°C and does not mix and separates when mixed with water of the same mass. When two or more oil agents are used, even if a compound having a melting point of 80°C or higher is contained, it is sufficient that the mixture of the two or more oil agents is in a liquid state at 80°C. Furthermore, from the viewpoint of on-board developing properties and dampening solution turbidity suppression, the above-mentioned oil agent is preferably a compound with a molecular weight of less than 1,000, more preferably a compound with a molecular weight of 200 to 800, and particularly preferably a compound with a molecular weight of 300 to 500. Furthermore, from the viewpoint of in-flight developability and dampening solution turbidity suppression, the above oil agent is preferably a compound with a boiling point of 200°C or higher at 1 atm, more preferably a compound with a boiling point of 250°C or higher at 1 atm, even more preferably a compound with a boiling point of 300°C or higher at 1 atm, and particularly preferably a compound with a boiling point of 400°C or higher and 500°C or lower at 1 atm. In this disclosure, unless otherwise specified, the term "boiling point" refers to the boiling point at 1 atmosphere. Furthermore, the melting point of the above-mentioned oil agent at 1 atmosphere is preferably 50°C or lower, more preferably 30°C or lower, and particularly preferably -200°C or higher and 25°C or lower, from the viewpoint of on-pressure developingability and dampening solution turbidity suppression. In this disclosure, unless otherwise specified, the term "melting point" refers to the melting point at 1 atmosphere.

[0265] Examples of the above-mentioned oil agents include phosphate ester compounds, aromatic hydrocarbon compounds, glyceride compounds, fatty acid compounds, aromatic ester compounds, and the like. In particular, from the viewpoint of UV resistance, ink transfer, on-press developability, and dampening solution turbidity suppression, at least one compound selected from the group consisting of phosphate ester compounds, aromatic hydrocarbon compounds, glyceride compounds, and aromatic ester compounds is preferred, at least one compound selected from the group consisting of phosphate ester compounds, aromatic hydrocarbon compounds, and glyceride compounds is more preferred, at least one compound selected from the group consisting of phosphate ester compounds and aromatic hydrocarbon compounds is even more preferred, and phosphate ester compounds are particularly preferred.

[0266] As for the phosphate ester compound, from the viewpoint of UV resistance, ink transfer, on-press developability, and dampening solution turbidity suppression, triester phosphate compounds are preferred, triaryl phosphate compounds are more preferred, tricresil phosphate is even more preferred, and a mixture of two or more of the ortho, meta, and para isomers of tricresil phosphate is particularly preferred. As for aromatic hydrocarbon compounds, compounds having two or more aromatic rings are preferred from the viewpoint of on-engine developability and dampening solution turbidity suppression, and compounds having two or more unfused benzene rings are more preferred. As for the glyceride compound, triglyceride compounds are preferred from the viewpoint of on-engine developability and dampening solution turbidity suppression, fatty oils are more preferred, and fatty oils that are liquid at 25°C, such as castor oil, are particularly preferred. As for the fatty acid compound, unsaturated fatty acids are preferred from the viewpoint of on-air developability and dampening solution turbidity suppression, unsaturated fatty acids with 8 to 30 carbon atoms are more preferred, and unsaturated fatty acids with 12 to 24 carbon atoms are particularly preferred. As aromatic ester compounds, aromatic diester compounds are preferred from the viewpoint of on-air developability and dampening solution turbidity suppression, and aromatic diester compounds having an aliphatic ring are more preferred. As for aliphatic ester compounds, from the viewpoint of in-flight developability and dampening solution turbidity suppression, aliphatic ester compounds having a branched alkyl group are preferred, and aliphatic ester compounds having a branched alkyl group and having 10 to 24 carbon atoms are more preferred.

[0267] The above-mentioned oil agent preferably contains an oil agent having phosphorus atoms, and more preferably contains an oil agent having phosphorus atoms, from the viewpoint of UV resistance, ink transfer properties, on-press developability, and dampening solution turbidity suppression. Furthermore, from the viewpoint of in-flight developability and dampening solution turbidity suppression, the above oil agent preferably contains an oil agent having an aromatic ring, more preferably contains an oil agent having two or more aromatic rings, and particularly preferably contains an oil agent having two or more non-fused benzene rings.

[0268] The clogP value of the above-mentioned oil agent is preferably 5.0 or higher, more preferably 5.50 or higher, even more preferably 5.50 or higher, even more preferably 5.50 to 10.0, and particularly preferably 5.60 to 7.00, from the viewpoint of UV resistance, ink transfer, on-press developability, and dampening solution turbidity suppression. The clogP value is the value obtained by calculating the common logarithm logP of the partition coefficient P between 1-octanol and water. While publicly known methods and software can be used to calculate the clogP value, unless otherwise specified, this disclosure uses the ClogP program integrated into Cambridge Soft's ChemBioDraw Ultra 12.0.

[0269] Specific examples of the above-mentioned oil agents include tricresyl phosphate, dimethyl(1-phenylethyl)benzene, 2,4-diphenyl-4-methyl-1-pentene, dicyclohexyl phthalate, castor oil, alpha-linolenic acid, and tri(2-ethylhexyl) phosphate.

[0270] The above oil agent may be used alone or in combination of two or more types, but the above image recording layer preferably contains two or more oil agents having different structures from the viewpoint of on-pressure developmentability and dampening solution turbidity suppression. The content of the above-mentioned oil agent is preferably 0.0001% to 10.0% by mass, more preferably 0.0002% to 1.0% by mass, even more preferably 0.0005% to 0.5% by mass, and particularly preferably 0.001% to 0.05% by mass, relative to the total mass of the image recording layer.

[0271] [Other ingredients] The image recording layer may contain other components such as surfactants, polymerization inhibitors, higher fatty acid derivatives, plasticizers, and inorganic layered compounds. Specifically, refer to paragraphs 0114 to 0159 of Japanese Patent Application Publication No. 2008-284817.

[0272] [Formation of the image recording layer] The image recording layer in the lithographic printing plate used in this disclosure can be formed, for example, by dispersing or dissolving the necessary components in a known solvent to prepare a coating solution, applying the coating solution onto a support by a known method such as bar coating, and drying it, as described in paragraphs 0142 to 0143 of Japanese Patent Application Publication No. 2008-195018. Any known solvent can be used as the solvent. Specifically, examples include water, acetone, methyl ethyl ketone (2-butanone), cyclohexane, ethyl acetate, ethylene dichloride, tetrahydrofuran, toluene, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol dimethyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, acetylacetone, cyclohexanone, diacetone alcohol, ethylene glycol monomethyl ether acetate, ethylene glycol ethyl ether acetate, ethylene glycol monoisopropyl ether, ethylene glycol monobutyl ether acetate, 1-methoxy-2-propanol, 3-methoxy-1-propanol, methoxymethoxyethanol, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, 3-methoxypropyl acetate, N,N-dimethylformamide, dimethyl sulfoxide, γ-butyrolactone, methyl lactate, ethyl lactate, etc. The solvent may be used alone or in combination of two or more types. The solid content concentration in the coating solution is preferably 1% to 50% by mass. The amount of coating (solid content) of the image recording layer after coating and drying varies depending on the application, but from the viewpoint of obtaining good sensitivity and good film characteristics of the image recording layer, 0.3 g / m² is recommended. 2 ~3.0g / m 2 It is preferable. Furthermore, the thickness of the image recording layer is preferably 0.1 μm to 3.0 μm, and more preferably 0.3 μm to 2.0 μm. In this disclosure, the thickness of each layer in a lithographic printing plate is determined by preparing a section cut perpendicular to the surface of the lithographic printing plate and observing the cross-section of the section using a scanning microscope (SEM).

[0273] <<Support>> The lithographic printing plate used in this disclosure has a support. As the support material, it can be appropriately selected and used from known supports for lithographic printing plates. As the support, a support having a hydrophilic surface (hereinafter also referred to as "hydrophilic support") is preferred.

[0274] In this disclosure, an aluminum plate that has been roughened and anodized by a known method is preferred as the support. That is, the support in this disclosure preferably has an aluminum plate and an anodized aluminum coating disposed on the aluminum plate.

[0275] Furthermore, the support comprises an aluminum plate and an anodic oxide film of aluminum disposed on the aluminum plate, wherein the anodic oxide film is located on the image recording layer side of the aluminum plate, and the anodic oxide film has micropores extending in the depth direction from the surface on the image recording layer side, and preferably the average diameter of the micropores on the surface of the anodic oxide film is greater than 10 nm and less than or equal to 100 nm. Furthermore, it is preferable that the micropore is composed of a large-diameter pore extending from the surface of the anodic oxide film to a depth of 10 nm to 1,000 nm, and a small-diameter pore communicating with the bottom of the large-diameter pore and extending from the communication point to a depth of 20 nm to 2,000 nm, with the average diameter of the large-diameter pore on the surface of the anodic oxide film being 15 nm to 100 nm, and the average diameter of the small-diameter pore at the communication point being 13 nm or less.

[0276] Figure 1 is a schematic cross-sectional view of one embodiment of the aluminum support 12a. The aluminum support 12a has a laminated structure in which an aluminum plate 18 and an aluminum anodic oxide film 20a (hereinafter also simply referred to as "anodic oxide film 20a") are laminated in this order. The anodic oxide film 20a in the aluminum support 12a is located on the image recording layer side of the aluminum plate 18. In other words, it is preferable that the lithographic printing plate used in this disclosure has at least an anodic oxide film, an image recording layer, and a water-soluble resin layer on the aluminum plate in this order.

[0277] -Anodized coating- The following describes preferred embodiments of the anodic oxide coating 20a. The anodic oxide film 20a is a film produced on the surface of the aluminum plate 18 by an anodizing treatment, and this film has extremely fine micropores 22a that are substantially perpendicular to the film surface and uniformly distributed. The micropores 22a extend from the surface of the anodic oxide film 20a on the image recording layer side (the surface of the anodic oxide film 20a opposite to the aluminum plate 18 side) along the thickness direction (towards the aluminum plate 18 side).

[0278] The average diameter (average aperture diameter) of the micropores 22a in the anodic oxide film 20a on the anodic oxide film surface is preferably greater than 10 nm and less than or equal to 100 nm. In particular, from the viewpoint of balancing print resistance, stain resistance, and image visibility, 15 nm to 60 nm is more preferable, 20 nm to 50 nm is even more preferable, and 25 nm to 40 nm is particularly preferable. The diameter inside the pore may be wider or narrower than that of the surface layer. When the average diameter exceeds 10 nm, it exhibits excellent print resistance and image visibility. Furthermore, when the average diameter is 100 nm or less, it also exhibits excellent print resistance. The average diameter of micropores 22a was obtained by observing the surface of the anodic oxide film 20a with a field emission scanning electron microscope (FE-SEM) at a magnification of 150,000x (N=4 images), measuring the diameter of micropores (diameter) at 50 locations within a 400nm × 600nm range in the resulting 4 images, and averaging the result. If the shape of the micropore 22a is not circular, the equivalent diameter of a circle is used. The "equivalent diameter of a circle" is the diameter of a circle that is assumed to have the same projected area as the projected area of ​​the opening.

[0279] The shape of the micropore 22a is not particularly limited; in Figure 1, it is roughly tubular (roughly cylindrical), but it may also be conical, with the diameter decreasing towards the depth (thickness) direction. Furthermore, the shape of the bottom of the micropore 22a is not particularly limited; it may be curved (convex) or flat.

[0280] In the support, the micropore may consist of a large-diameter pore extending to a certain depth from the surface of the anodic oxide film, and a small-diameter pore communicating with the bottom of the large-diameter pore and extending to a certain depth from the communication point. For example, as shown in Figure 2, the aluminum support 12b may include an aluminum plate 18 and an anodic oxide film 20b having micropores 22b composed of large-diameter holes 24 and small-diameter holes 26. For example, the micropores 22b in the anodic oxide film 20b consist of a large-diameter pore portion 24 extending from the surface of the anodic oxide film to a depth of 10 nm to 1,000 nm (depth D: see Figure 2), and a small-diameter pore portion 26 communicating with the bottom of the large-diameter pore portion 24 and extending from the communication point to a depth of 20 nm to 2,000 nm. Specifically, for example, the embodiment described in paragraphs 0107 to 0114 of Japanese Patent Application Publication No. 2019-162855 can be used.

[0281] -Method for manufacturing a support- A preferred method for manufacturing the support used in this disclosure is, for example, a manufacturing method that involves performing the following steps in order. • Surface roughening process: A process of applying a surface roughening treatment to an aluminum plate. • Anodizing process: A process of anodizing an aluminum plate that has undergone surface roughening treatment. • Pore widening process: A process in which an aluminum plate having an anodic oxide film obtained in the anodizing process is brought into contact with an acidic aqueous solution or an alkaline aqueous solution to enlarge the diameter of micropores in the anodic oxide film. The following details the procedures for each step.

[0282] ~Surface roughening treatment process~ The surface roughening process involves applying a surface roughening treatment, including electrochemical surface roughening, to the surface of the aluminum plate. This process is preferably carried out before the anodic oxidation process described later, but it may not be necessary if the surface of the aluminum plate already has a desirable surface shape. This process can be carried out by the method described in paragraphs 0086 to 0101 of Japanese Patent Application Publication No. 2019-162855.

[0283] ~Anodizing Process~ The procedure for the anodic oxidation process is not particularly limited as long as the above-described micropores are obtained, and known methods can be used. In the anodizing process, aqueous solutions of sulfuric acid, phosphoric acid, and oxalic acid can be used as the electrolytic bath. For example, the concentration of sulfuric acid can range from 100 g / L to 300 g / L. The conditions for the anodizing process are set appropriately depending on the electrolyte used, but for example, the electrolyte temperature is 5°C to 70°C (preferably 10°C to 60°C) and the current density is 0.5 A / dm². 2 ~60A / dm 2 (preferably 1 A / dm 2 ~60A / dm 2 ), voltage 1V to 100V (preferably 5V to 50V), electrolysis time 1 second to 100 seconds (preferably 5 seconds to 60 seconds), and film thickness 0.1g / m² 2 ~5g / m 2 (Preferably 0.2 g / m 2 ~3g / m 2 ) are some examples.

[0284] ~Pore-wide treatment~ Pore ​​widening is a process (pore diameter enlargement process) that enlarges the diameter of micropores (pore diameter) present in the anodic oxide film formed by the anodic oxidation process described above. Pore ​​widening can be performed by contacting the aluminum plate obtained by the anodic oxidation process described above with an acidic aqueous solution or an alkaline aqueous solution. The method of contact is not particularly limited, and examples include immersion and spraying methods.

[0285] The support may, if necessary, have a back coat layer on the side opposite to the image recording layer, which contains an organic polymer compound described in Japanese Patent Publication No. 5-45885 or a silicon alkoxy compound described in Japanese Patent Publication No. 6-35174, etc.

[0286] <<Undercoat layer>> The lithographic printing plate used in this disclosure preferably has an undercoat layer (sometimes called an intermediate layer) between the image recording layer and the support. The undercoat layer strengthens the adhesion between the support and the image recording layer in the exposed areas and makes it easier for the image recording layer to peel off from the support in the unexposed areas, thereby contributing to improved developability while suppressing a decrease in print durability. In addition, in the case of infrared laser exposure, the undercoat layer functions as a heat insulating layer, which has the effect of preventing the heat generated by exposure from diffusing to the support and reducing sensitivity.

[0287] Examples of compounds used in the undercoat layer include polymers having adsorbent groups and hydrophilic groups that can be adsorbed onto the support surface. Polymers having adsorbent groups and hydrophilic groups, and further having crosslinkable groups, are preferred to improve adhesion with the image recording layer. The compounds used in the undercoat layer may be low-molecular-weight compounds or polymers. Two or more compounds may be mixed and used as needed.

[0288] When the compound used in the undercoat layer is a polymer, copolymers of monomers having adsorbent groups, monomers having hydrophilic groups, and monomers having crosslinkable groups are preferred. Preferred adsorbent groups that can be adsorbed onto the support surface are phenolic hydroxyl groups, carboxyl groups, -PO3H2, -OPO3H2, -CONHSO2-, -SO2NHSO2-, and -COCH2COCH3. Preferred hydrophilic groups are sulfo groups or their salts, and carboxyl groups. Preferred crosslinking groups are acrylic groups, methacrylic groups, acrylamide groups, methacrylamide groups, and allyl groups. The polymer may have crosslinkable groups introduced by salt formation between the polar substituent of the polymer and a compound having a substituent oppositely charged to the polar substituent and an ethylenically unsaturated bond, or it may be further copolymerized with other monomers, preferably hydrophilic monomers.

[0289] Specifically, suitable examples include silane coupling agents having an ethylenically double bond reactive group that can be added and polymerized as described in Japanese Patent Publication No. 10-282679, and phosphorus compounds having an ethylenically double bond reactive group as described in Japanese Patent Publication No. 2-304441. Low molecular weight or high molecular weight compounds having a crosslinkable group (preferably an ethylenically unsaturated group), a functional group that interacts with the support surface, and a hydrophilic group as described in Japanese Patent Publication Nos. 2005-238816, 2005-125749, 2006-239867, and 2006-215263 are also preferably used. More preferable examples include polymers having adsorbent groups, hydrophilic groups, and crosslinkable groups that can be adsorbed onto the surface of a support, as described in Japanese Patent Publication No. 2005-125749 and Japanese Patent Publication No. 2006-188038.

[0290] The content of ethylenically unsaturated groups in the polymer used for the undercoat layer is preferably 0.1 mmol to 10.0 mmol, more preferably 0.2 mmol to 5.5 mmol per gram of polymer. The weight-average molecular weight (Mw) of the polymer used in the undercoat layer is preferably 5,000 or more, and more preferably between 10,000 and 300,000.

[0291] In addition to the above-mentioned undercoat compound, the undercoat layer may also contain, to prevent soiling over time, a chelating agent, a secondary or tertiary amine, a polymerization inhibitor, or a compound having an amino group or a functional group having polymerization-inhibiting ability that interacts with the support surface (for example, 1,4-diazabicyclo[2.2.2]octane (DABCO), 2,3,5,6-tetrahydroxy-p-quinone, chloranil, sulfophthalic acid, hydroxyethylethylenediaminetriacetic acid, dihydroxyethylethylenediaminediacetic acid, hydroxyethyliminodiacetic acid, etc.).

[0292] The primer layer is applied by a known method. The amount of primer layer applied (solid content) is 0.1 mg / m². 2 ~100mg / m 2 Preferably, 1 mg / m² 2 ~30mg / m 2 This is preferable.

[0293] <<Outermost layer>> The lithographic printing plates used in this disclosure may have an outermost layer (sometimes called a "protective layer" or "overcoat layer") on the side of the image recording layer opposite to the support side. Furthermore, the lithographic printing plate used in this disclosure preferably has a support, an image recording layer, and an outermost layer in this order. The thickness of the outermost layer is preferably greater than the thickness of the image recording layer. The outermost layer may have functions to suppress image formation inhibition reactions by blocking oxygen, as well as to prevent damage to the image recording layer and prevent ablation during high-intensity laser exposure.

[0294] Such properties for the outermost layer are described, for example, in U.S. Patent No. 3,458,311 and Japanese Patent Publication No. 55-49729. The oxygen-low permeable polymer used in the outermost layer can be either a water-soluble polymer or a water-insoluble polymer, and two or more types can be mixed as needed. However, from the viewpoint of on-machine developability, it is preferable to include a water-soluble polymer. In this disclosure, a water-soluble polymer means a polymer that dissolves at a rate of 1 g or more in 100 g of pure water at 70°C, and that does not precipitate when a solution containing 1 g of the polymer dissolved in 100 g of pure water at 70°C is cooled to 25°C. Examples of water-soluble polymers used in the outermost layer include polyvinyl alcohol, modified polyvinyl alcohol, polyvinylpyrrolidone, water-soluble cellulose derivatives, polyethylene glycol, and poly(meth)acrylonitrile. As the modified polyvinyl alcohol, acid-modified polyvinyl alcohol having a carboxyl group or a sulfo group is preferably used. Specifically, examples include the modified polyvinyl alcohols described in Japanese Patent Publication No. 2005-250216 and Japanese Patent Publication No. 2006-259137.

[0295] Among the water-soluble polymers mentioned above, it is preferable that the polymer contains polyvinyl alcohol, and it is even more preferable that it contains polyvinyl alcohol with a degree of saponification of 50% or more. The degree of saponification is preferably 60% or higher, more preferably 70% or higher, and even more preferably 85% or higher. There is no particular upper limit to the degree of saponification; it should be 100% or less. The degree of saponification described above is measured according to the method described in JIS K 6726:1994. Furthermore, one preferred embodiment of the outermost layer is one in which polyvinyl alcohol and polyethylene glycol are included.

[0296] In the case where the outermost layer in this disclosure contains a water-soluble polymer, the content of the water-soluble polymer relative to the total mass of the outermost layer is preferably 1% to 99% by mass, more preferably 3% to 97% by mass, and even more preferably 5% to 95% by mass.

[0297] The outermost layer preferably contains a hydrophobic polymer. A hydrophobic polymer is a polymer that dissolves in less than 5g of pure water at 125°C or does not dissolve at all in 100g of pure water. Examples of hydrophobic polymers include polyethylene, polystyrene, polyvinyl chloride, polyvinylidene chloride, alkyl poly(meth)acrylates (e.g., methyl poly(meth)acrylate, ethyl poly(meth)acrylate, butyl poly(meth)acrylate, etc.), and copolymers of these resin raw material monomers. Furthermore, it is preferable that the hydrophobic polymer includes polyvinylidene chloride resin. Furthermore, it is preferable that the hydrophobic polymer includes a styrene-acrylic copolymer (also known as styrene-acrylic resin). Furthermore, from the viewpoint of on-air developability, the hydrophobic polymer is preferably in the form of hydrophobic polymer particles.

[0298] Hydrophobic polymers may be used individually or in combination of two or more types.

[0299] If the outermost layer contains a hydrophobic polymer, the hydrophobic polymer content is preferably 1% to 70% by mass, more preferably 5% to 50% by mass, and even more preferably 10% to 40% by mass, relative to the total mass of the outermost layer.

[0300] In this disclosure, the area occupancy rate on the outermost surface of the hydrophobic polymer is preferably 30 area % or more, more preferably 40 area % or more, and even more preferably 50 area % or more. An example of the upper limit for the area occupancy rate on the outermost surface of a hydrophobic polymer is 90 area. The area occupancy rate of the outermost surface of a hydrophobic polymer can be measured as follows. Using an ULVAC-PHI nano TOFII time-of-flight secondary ion mass spectrometer (TOF-SIMS), the outermost surface is irradiated with a Bi ion beam (primary ions) at an accelerating voltage of 30 kV. By measuring the peaks of ions (secondary ions) corresponding to the hydrophobic regions (i.e., regions made of hydrophobic polymers) emitted from the surface, the hydrophobic regions are mapped to a depth of 100 μm. 2The area occupied by the hydrophobic portion is measured, and the area ratio of the hydrophobic portion is determined. This is defined as the "area ratio of the outermost surface of the hydrophobic polymer." For example, if the hydrophobic polymer is an acrylic resin, then C6H 13 O - Measurement is performed based on the peak. Furthermore, if the hydrophobic polymer is polyvinylidene chloride, C2H2Cl + Measurement is performed based on the peak. The above-mentioned area occupancy ratio can be adjusted by the amount of hydrophobic polymer added, etc.

[0301] The outermost layer preferably contains an infrared absorbent, and more preferably a decomposable infrared absorbent, from the viewpoint of visibility and storage stability. As infrared absorbing agents, those described above are preferred for use in the image recording layer.

[0302] The infrared absorber in the outermost layer may be used alone or in combination of two or more components. From the viewpoint of visibility over time and storage stability, the content of the infrared absorber in the outermost layer is preferably 0.10% to 50% by mass, more preferably 0.50% to 30% by mass, and even more preferably 1.0% to 20% by mass, relative to the total mass of the outermost layer.

[0303] The outermost layer preferably contains a color-developing agent from the viewpoint of improving the visibility of the exposed area. As a colorant, the above-mentioned colorant precursor is preferred in the image recording layer.

[0304] The colorant in the outermost layer may be used alone or in combination of two or more components. From the viewpoint of color development, the content of the coloring agent in the outermost layer is preferably 0.10% to 50% by mass, more preferably 0.50% to 30% by mass, and even more preferably 1.0% to 20% by mass, based on the total mass of the outermost layer.

[0305] The outermost layer may contain an inorganic layered compound to enhance oxygen barrier properties. The inorganic layered compound is a thin, flat particle and includes, for example, mica group materials such as natural mica and synthetic mica, talc represented by the formula: 3MgO·4SiO·H2O, teniolite, montmorillonite, saponite, hectorite, zirconium phosphate, and the like. The inorganic layered compound that is preferably used is a mica compound. For example, a mica compound of formula A(B,C) 2-5 D4O 10 Examples of mica groups include natural mica and synthetic mica represented by (OH,F,O)2 [where A is one of K, Na, or Ca; B and C are one of Fe(II), Fe(III), Mn, Al, Mg, or V; and D is Si or Al].

[0306] In the mica group, natural micas include muscovite, soda mica, phlogopite, biotite, and scallop mica. Synthetic micas include fluorinated phlogopite (KMg3(AlSi3O)). 10 ) F2, Potassium tetrasilicon mica KMg 2.5 Si4O 10 ) Non-swelling mica such as F2, and Na tetrasilyl mica NaMg 2.5 (Si4O 10 )F2, Na or Li teniolite (Na,Li)Mg2Li(Si4O 10 )F2, montmorillonite-based Na or Li hectorite (Na,Li) 1 / 8 Mg 2 / 5 Li 1 / 8 (Si4O 10 Examples include swelling mica such as F2. Furthermore, synthetic smectite is also useful.

[0307] Among the mica compounds mentioned above, fluorine-based swelling mica is particularly useful. Specifically, swelling synthetic mica has a layered structure consisting of unit crystal lattice layers with a thickness of about 10 Å to 15 Å (1 Å = 0.1 nm), and the intralattice metal atom substitution is significantly greater than in other clay minerals. As a result, the lattice layers suffer from a deficiency of positive charge, and Li is present between the layers to compensate for this. + na + Ca 2+ Mg 2+It adsorbs cations such as Li. The cations interposed between these layers are called exchangeable cations and can exchange with various cations. In particular, the cations between the layers are Li + na + In this case, the small ionic radius results in weak bonds between the layered crystal lattices, causing significant swelling in water. When sheared in this state, it easily cleaves and forms a stable sol in water. Swellable synthetic mica exhibits this tendency strongly and is therefore particularly preferred for use.

[0308] From the viewpoint of diffusion control, the shape of the mica compound is such that the thinner the particle, the better, and the larger the plane size, as long as it does not hinder the smoothness of the coated surface or the transmittance of active light. Therefore, the aspect ratio is preferably 20 or more, more preferably 100 or more, and particularly preferably 200 or more. The aspect ratio is the ratio of the major axis to the thickness of the particle, and can be measured, for example, from a projection image of a microscopic photograph of the particle. The larger the aspect ratio, the greater the effect obtained.

[0309] The particle size of the mica compound is preferably 0.3 μm to 20 μm, more preferably 0.5 μm to 10 μm, and particularly preferably 1 μm to 5 μm in average major axis. The average thickness of the particles is preferably 0.1 μm or less, more preferably 0.05 μm or less, and particularly preferably 0.01 μm or less. Specifically, for example, in the case of swelling synthetic mica, which is a representative compound, a preferred embodiment is a thickness of about 1 nm to 50 nm and a surface size (major axis) of about 1 μm to 20 μm.

[0310] The content of the inorganic layered compound is preferably 1% to 60% by mass, and more preferably 3% to 50% by mass, relative to the total mass of the outermost layer. Even when multiple types of inorganic layered compounds are used in combination, it is preferable that the total amount of inorganic layered compounds is within the above content range. Within this range, oxygen barrier properties are improved, and good sensitivity is obtained. In addition, a decrease in thickness can be prevented.

[0311] The outermost layer may contain known additives such as plasticizers for imparting flexibility, surfactants for improving coatability, and inorganic particles for controlling surface slipperiness. Furthermore, the outermost layer may contain the lipid-sensitive agents described in the image recording layer section.

[0312] The outermost layer is applied by a known method. The amount of the outermost layer applied (solid content) is 0.01 g / m². 2 ~10g / m 2 Preferably, 0.02 g / m 2 ~3g / m 2 More preferably, 0.02 g / m 2 ~1g / m 2 That is particularly preferable. The thickness of the outermost layer in the lithographic printing plate used in this disclosure is preferably 0.1 μm to 5.0 μm, and more preferably 0.3 μm to 4.0 μm. The thickness of the outermost layer in the lithographic printing plate used in this disclosure is preferably 1.1 to 5.0 times, and more preferably 1.5 to 3.0 times, the thickness of the image recording layer.

[0313] The lithographic printing plates used in this disclosure may have other layers besides those described above. Other layers are not particularly limited and may include known layers. For example, a backcoat layer may be provided on the side of the support opposite to the image recording layer, if necessary.

[0314] (Cleaning agent for lithographic printing plates developed on press) The plate cleaning agent for on-press type lithographic printing plates according to this disclosure contains 3.0% by mass or more of a solvent having a ClogP value greater than -1.5 and 2.5 or less, based on the total mass of the plate cleaning agent. A preferred embodiment of the plate cleaning agent for on-press development type lithographic printing plates according to this disclosure is the same as a preferred embodiment of the plate cleaning agent in the lithographic printing method according to this disclosure. [Examples]

[0315] The present disclosure will be described in detail below with reference to examples, but the disclosure is not limited to these examples. In these examples, unless otherwise specified, "%" and "parts" refer to "mass%" and "parts by mass," respectively. For polymer compounds, unless otherwise specified, the molecular weight is the weight-average molecular weight (Mw), and the ratio of constituent repeating units is expressed as a mole percentage. The weight-average molecular weight (Mw) is the value measured as a polystyrene equivalent by gel permeation chromatography (GPC).

[0316] [Preparation of printing plate 1] <Preparing the support structure> (a) Alkaline etching treatment An aluminum plate was etched by spraying it with a caustic soda aqueous solution containing 26% by mass of caustic soda and 6.5% by mass of aluminum ions at a temperature of 70°C. Afterward, it was rinsed with water by spraying. The amount of aluminum dissolved in the surface to be subsequently subjected to electrochemical roughening treatment was 5 g / m². 2 That was the case.

[0317] (b) Desmat treatment using an acidic aqueous solution (first desmat treatment) Next, a desmatt treatment was performed using an acidic aqueous solution. The acidic aqueous solution used for the desmatt treatment was a 150 g / L sulfuric acid solution. The solution temperature was 30°C. The acidic aqueous solution was sprayed onto the aluminum plate and desmatt treatment was performed for 3 seconds. After that, a water rinse was performed.

[0318] (c) Electrochemical roughening treatment Next, electrochemical surface roughening treatment was performed using an electrolyte solution with a hydrochloric acid concentration of 14 g / L, an aluminum ion concentration of 13 g / L, and a sulfuric acid concentration of 3 g / L, with alternating current. The electrolyte solution temperature was 30°C. The aluminum ion concentration was adjusted by adding aluminum chloride. The waveform of an alternating current is a sine wave with symmetrical positive and negative waveforms, with a frequency of 50 Hz, anode reaction time and cathode reaction time in one cycle of the alternating current at a ratio of 1:1, and current density at the peak current value of the alternating current waveform is 75 A / dm². 2Furthermore, the amount of electric charge was 450 C / dm², which is the sum of the electric charges that the aluminum plate participates in the anode reaction. 2 The electrolytic treatment is 112.5C / dm 2 The procedure was carried out in four stages, with a 4-second interval between applications. A carbon electrode was used as the counter electrode to the aluminum plate. Afterwards, a water rinsing treatment was performed.

[0319] (d) Alkaline etching treatment An aluminum plate that had undergone electrochemical roughening treatment was etched by spraying an aqueous solution of caustic soda with a concentration of 5% by mass of caustic soda and an aluminum ion concentration of 0.5% by mass at a temperature of 45°C. The amount of aluminum dissolved on the electrochemically roughened surface was 0.2 g / m². 2 That was the case. Afterwards, it was washed with water.

[0320] (e) Desmatt treatment using an acidic aqueous solution Next, a desmatt treatment was performed using an acidic aqueous solution. Specifically, the acidic aqueous solution was sprayed onto the aluminum plate and desmatt treatment was performed for 3 seconds. The acidic aqueous solution used for the desmatt treatment was an aqueous solution with a sulfuric acid concentration of 170 g / L and an aluminum ion concentration of 5 g / L. The temperature of the solution was 30°C.

[0321] (f) First stage anodizing treatment The first stage of anodizing (also called the first anodizing treatment) was performed using a DC electrolytic anodizing treatment apparatus 610 with the structure shown in Figure 3. Specifically, the first anodizing treatment was performed under the conditions shown in the "First Anodizing Treatment" column of Table 1 below, forming an anodic oxide film of a predetermined thickness. The anodic oxidation treatment apparatus 610 shown in Figure 3 will be described below. In the anodic oxidation treatment apparatus 610 shown in Figure 3, the aluminum plate 616 is transported as indicated by the arrows in Figure 3. In the power supply tank 612 where the electrolyte 618 is stored, the aluminum plate 616 is charged positively by the power supply electrode 620. Then, in the power supply tank 612, the aluminum plate 616 is transported upward by the roller 622, its direction is changed downward by the nip roller 624, and then it is transported toward the electrolytic treatment tank 614 where the electrolyte 626 is stored, and its direction is changed horizontally by the roller 628. Next, the aluminum plate 616 is charged negatively by the electrolytic electrode 630, so that an anodic oxide film is formed on its surface, and the aluminum plate 616 that has left the electrolytic treatment tank 614 is transported to the next process. In the anodizing apparatus 610, a direction-changing mechanism is formed by rollers 622, nip roller 624, and roller 628, and the aluminum plate 616 is conveyed in a mountain shape and an inverted U shape by the rollers 622, 624, and 628 in the space between the power supply tank 612 and the electrolytic treatment tank 614. The power supply electrode 620 and the electrolytic electrode 630 are connected to a DC power supply 634.

[0322] (g) Pore widening treatment The anodized aluminum plates described above were immersed in a caustic soda aqueous solution with a temperature of 40°C, a caustic soda concentration of 5% by mass, and an aluminum ion concentration of 0.5% by mass under the conditions shown in Table 1 below, and subjected to pore widening treatment. After that, they were rinsed with water using a spray.

[0323] (h) Second anodizing treatment The second stage of anodizing (also called the second anodizing treatment) was performed using a DC electrolytic anodizing treatment apparatus 610 with the structure shown in Figure 3. Specifically, the second anodizing treatment was performed under the conditions shown in the "Second Anodizing Treatment" column of Table 1 below to form an anodic oxide film of a predetermined thickness.

[0324] Support body 1 was fabricated in the manner described above. The L of the micropore anodic oxide film surface of the obtained support 1 * a * b * Lightness L in a color system *Table 2 summarizes the average diameter and depth of the oxide film surface in the large-diameter pores of the micropores, the average diameter (nm) and depth of the communicating positions of the small-diameter pores in the micropores, the depth (nm) of the large-diameter and small-diameter pores, the micropore density, and the thickness of the anodic oxide film (also called film thickness) from the bottom of the small-diameter pores to the surface of the aluminum plate. In Table 1, the film thickness (AD) in the "First Anodizing Treatment" column and the "Second Anodizing Treatment" column represent the film thickness obtained in each treatment. The electrolyte used is an aqueous solution containing the components listed in Table 1.

[0325] [Table 1]

[0326] [Table 2]

[0327] <Formation of the undercoat layer> On the obtained support 1, apply the primer layer solution with the following composition, with a dry coating amount of 0.1 g / m². 2 The coat was applied in this manner to form a base coat layer.

[0328] [Coating liquid for the undercoat layer] • Undercoat compound (see U-1 below, 11% aqueous solution): 0.10502 parts Sodium gluconate: 0.0700 parts • Surfactant (Emarex® 710, Nippon Emulsion Co., Ltd.): 0.00159 parts • Preservative (Biohope L, K.I. Chemicals Co., Ltd.): 0.00149 parts ·Wed: 3.29000 copies

[0329] [ka]

[0330] <Formation of the image recording layer> The image recording layer coating solution shown below was applied in a bar onto the undercoat layer, and then oven-dried at 120°C for 40 seconds, resulting in a dry coating amount of 1.0 g / m². 2 An image recording layer was formed, and a lithographic printing plate (printing plate 1) was obtained.

[0331] -Image recording layer coating liquid- Each of the components listed below was dissolved or dispersed in a mixed solvent of 1-methoxy-2-propanol (MFG):methyl ethyl ketone (MEK):methanol = 4:4:1 (mass ratio) to prepare an image recording layer coating solution with a solid content of 6% by mass. • Infrared absorber IR dye-4: Content after drying is 20 mg / m² 2 The amount • Infrared absorber IR dye-5: Content after drying is 20 mg / m² 2 The amount • Polymerization initiator IA-1 (see compound below, LUMO = -3.02 eV): 100 parts by mass • Electron-donating polymerization initiator TPB (sodium tetraphenylborate, HOMO = -5.90 eV): 20 parts by mass • Polymerizable compound M-1 (urethane (meth)acrylate oligomer, U-10HA (number of functional groups: 10), manufactured by Shin-Nakamura Chemical Industry Co., Ltd.): 500 parts by mass • Polymerizable compound M-2 (a bifunctional methacrylate compound, FST 510 from AZ Electronics (a reaction product of 1 molar equivalent of 2,2,4-trimethylhexamethylene diisocyanate and 2 molar equivalents of hydroxyethyl methacrylate, a 82% by mass solution of methyl ethyl ketone of the compound with the structure shown below)): 250 parts by mass • Polymerizable compound M-3 (ethoxylated bisphenol A dimethacrylate, compound with the structure shown below, BPE-80N manufactured by Shin-Nakamura Chemical Industry Co., Ltd.): 250 parts by mass • Colorants listed in Table 3 (S-1 in Examples 1-20 and Comparative Examples 1 and 2, the compounds listed below): 25 parts by mass • Anionic surfactant A-1 (compound with the following structure): 25 parts by mass • Fluorine-based surfactant W-1 (compound with the structure shown below, weight-average molecular weight: 13,000): 5 parts by mass

[0332] IR dye-4: Decomposition-type color-developing infrared absorber, compound with the following structure. IR dye-5: Non-degradable infrared absorber, compound with the following structure

[0333] [ka]

[0334] [ka]

[0335] [ka]

[0336] [ka]

[0337] [ka]

[0338] [ka]

[0339] <Formation of the outermost layer> On the image recording layer, the outermost coating solution described below is applied in a bar according to the information in Table 6, and then oven-dried at 120°C for 60 seconds until the dry coating amount is 0.41 g / m². 2 It formed the outermost layer. Through the above process, a lithographic printing plate (printing plate 1) was obtained.

[0340] -Outermost layer coating liquid- Each of the components listed below was dissolved or dispersed in deionized water to prepare a solution with a solid content of 20% by mass, thereby creating the outermost coating solution. • Infrared absorbers listed in Table 3: Amount such that the content after drying is as listed in Table 3. • Water-soluble polymer (polyvinyl alcohol, Mowiol 4-88, manufactured by Kuraray Co., Ltd.): 250 parts by mass • Hydrophobic polymer (polyvinylidene chloride aqueous dispersion, Solvin Diofan® A50): 250 parts by mass • Surfactant (nonionic surfactant, Lutensol® A8 manufactured by BASF): 10 parts by mass

[0341] [Preparation of printing plate 2] <<Surface treatment D>>: [Support having large-diameter and small-diameter holes] (Da) Alkaline etching treatment An aluminum plate was etched by spraying an aqueous solution of caustic soda (sodium hydroxide) with a concentration of 26% by mass and an aluminum ion concentration of 6.5% by mass onto it using a spray tube at a temperature of 70°C. Afterward, it was rinsed with water using a spray. The amount of aluminum dissolved in the surface to be subsequently subjected to electrochemical roughening treatment was 1.0 g / m². 2 That was the case.

[0342] (Db) Desmat treatment in acidic aqueous solution (first desmat treatment) Next, a desmatt treatment was performed in an acidic aqueous solution. The acidic aqueous solution used for the desmatt treatment was a 150 g / L sulfuric acid solution. The solution temperature was 30°C. The desmatt solution was sprayed and treated for 3 seconds. After that, a rinse with water treatment was performed.

[0343] (Dc) Electrochemical roughening treatment in hydrochloric acid aqueous solution Next, electrolytic surface roughening was performed using an electrolyte solution with a hydrochloric acid concentration of 14 g / L, an aluminum ion concentration of 13 g / L, and a sulfuric acid concentration of 3 g / L, with alternating current. The electrolyte solution temperature was 30°C. The aluminum ion concentration was adjusted by adding aluminum chloride. The waveform of the alternating current was a sine wave with symmetrical positive and negative waveforms, with a frequency of 50 Hz, anode reaction time and cathode reaction time in one cycle of the alternating current at a ratio of 1:1, and current density at the peak current value of the alternating current waveform was 75 A / dm². 2Furthermore, the amount of electric charge was 450 C / dm², which is the sum of the electric charges that the aluminum plate participates in the anode reaction. 2 The electrolytic treatment is 125C / dm 2 The procedure was carried out in four stages, with a 4-second interval between applications. A carbon electrode was used as the counter electrode to the aluminum plate. Afterwards, a water rinsing treatment was performed.

[0344] (Dd) Alkaline etching treatment An aluminum plate that had undergone electrochemical roughening treatment was etched by spraying it with a caustic soda aqueous solution containing 5% caustic soda and 0.5% aluminum ions at 45°C using a spray tube. The amount of aluminum dissolved on the electrochemically roughened surface was 0.2 g / m². 2 That was the case. Afterwards, it was washed with water.

[0345] (De) Desmat treatment in acidic aqueous solution Next, a desmatt treatment was performed in an acidic aqueous solution. The acidic aqueous solution used for the desmatt treatment was waste liquid generated in the anodizing process (5.0 g / L of aluminum ions dissolved in 170 g / L of sulfuric acid aqueous solution). The liquid temperature was 30°C. The desmatt solution was sprayed onto a spray bottle and the desmatt treatment was performed for 3 seconds.

[0346] (Df) First stage anodizing treatment The first stage of anodic oxidation was performed using a DC electrolytic anodic oxidation apparatus with the structure shown in Figure 3. An anodic oxidation was carried out under the conditions shown in Table 3 to form an anodic oxidation film of a predetermined thickness.

[0347] (Dg) Pore Wide Treatment The anodized aluminum plates described above were immersed in a caustic soda aqueous solution with a temperature of 35°C, a caustic soda concentration of 5% by mass, and an aluminum ion concentration of 0.5% by mass under the conditions shown in Table 1, and subjected to pore widening treatment. After that, they were rinsed with water using a spray.

[0348] (Dh) Second stage anodizing treatment The second stage of anodic oxidation was performed using a DC electrolytic anodic oxidation apparatus with the structure shown in Figure 3. An anodic oxidation was carried out under the conditions shown in Table 3 to form an anodic oxidation film of a predetermined thickness.

[0349] From the above surface treatment D, the support 2 described in Tables 3 and 4 was obtained.

[0350] The average diameter (nm) of the large-diameter pores on the surface of the anodic oxide film after the second anodizing process obtained above, the average diameter (nm) of the small-diameter pores at the connecting positions, the depth (nm) of the large-diameter and small-diameter pores, and the pit density (density of micropores, unit: pores / μm) are as follows: 2 The thickness (nm) of the anodic oxide film from the bottom of the small-diameter hole to the surface of the aluminum plate is summarized in Table 4. The average diameter of the micropores (average diameter of the large and small diameter pores) was calculated by observing the surfaces of the large and small diameter pores with an FE-SEM at a magnification of 150,000x (N=4 images), measuring the diameter of the micropores (large and small diameter pores) in the 400nm × 600nm range in the four resulting images, and averaging the result. In cases where the depth of the large diameter pores was great and it was difficult to measure the diameter of the small diameter pores, or when measuring enlarged diameter pores within the small diameter pores, the upper part of the anodic oxide film was cut, and then the various diameters were determined. The depth of the micropores (depth of large-diameter and small-diameter pores) was determined by observing a cross-section of the support (anodic oxide film) with FE-SEM (observation of large-diameter pore depth: 150,000x, observation of small-diameter pore depth: 50,000x), measuring the depth of 25 arbitrary micropores in the obtained image, and averaging the result. In Table 3, the film thickness (AD) in the "First Anodizing Treatment" column and the "Second Anodizing Treatment" column represent the film thickness obtained in each treatment. The electrolyte used is an aqueous solution containing the components listed in Table 3.

[0351] [Table 3]

[0352] [Table 4]

[0353] <Method for forming the undercoat layer> On the support 2, apply a primer coating liquid 2 with the following composition, at a dry coating rate of 20 mg / m². 2 The mixture was applied and dried in a 100°C oven for 30 seconds to form a base coat.

[0354] -Composition of primer coating liquid 2- • Polymer (see U-1 above): 0.14 parts • Kirest 400: 0.035 units • Kirest 3EAF: 0.035 parts • Surfactant (Emarex 710, manufactured by Nippon Emulsion Co., Ltd.): 0.0016 parts • Preservative (Biohope L, manufactured by K.I. Chemicals Co., Ltd.): 0.0015 parts ·Wednesday: 3.29 parts

[0355] <Formation of the image recording layer> Apply the image recording layer coating liquid 2 shown below to the undercoat layer in a bar, and oven dry at 120°C for 40 seconds, resulting in a dry coating amount of 0.7 g / m². 2 An image recording layer was formed.

[0356] -Preparation of Image Recording Layer Coating Solution 2- Image recording layer coating solution 2 contained the following components in the following mass ratios and was prepared with a mixed solvent of 1-methoxy-2-propanol (MFG):methyl ethyl ketone (MEK):methanol = 4:4:1 (mass ratio) to achieve a solid content of 6% by mass. The amounts added below indicate the solid content. Electron-accepting polymerization initiator Int-3: 109 parts Infrared absorber IR-2: 17.5 parts Infrared absorber IR-3: 1.3 parts Electron-donating polymerization initiator B-1: 25 parts Polymerizable compound M-4: 212 parts Polymer particles R-1: 400 parts Colorant S-7: 40 parts Chromogenic compound curcumin: 1 part Hydrophilic compound T-2: 6 parts Oil agent O-13: 12.5 parts Surfactant F-2: 4.2 parts

[0357] [Infrared absorber] IR-2 and IR-3: Compounds with the following structure

[0358] [ka]

[0359] Note that Bu represents an n-butyl group, and TsO - This represents a tosylate anion.

[0360] [Electron-accepting polymerization initiators] Int-3: Compounds with the following structure, where TsO - represents a tosylate anion, and Ph represents a phenyl group.

[0361] [ka]

[0362] [Electron-donating polymerization initiator] B-1: Compound with the following structure

[0363] [ka]

[0364] [Polymerizable compound] M-4: Urethane acrylate, manufactured by Shin Nakamura Chemical Industry Co., Ltd., U-15HA

[0365] [Coloring agent] S-7: The following compounds

[0366] [ka]

[0367] Note that Me represents a methyl group, and Et represents an ethyl group.

[0368] [Color-forming compound] Curcumin: The following compounds

[0369] [ka]

[0370] [Hydrophilic compound] T-2: Compound with the following structure

[0371] [ka]

[0372] [Oil-based product] O-13: The following compounds

[0373] [ka]

[0374] [Surfactants] F-2: Fluorine-based surfactant, Megafac F-781F (manufactured by DIC Corporation)

[0375] [Polymer particles] <Preparation of polymer particles R-1> • Microgel (polymer particles R-1): 2,640 parts • Distilled water: 2.425 parts The method for preparing the above microgel is shown below.

[0376] -Preparation of polyvalent isocyanate compounds- To a suspension of 17.78 parts (80 molar equivalents) of isophorone diisocyanate and 7.35 parts (20 molar equivalents) of the following polyhydric phenol compound (1) in ethyl acetate (25.31 parts), 0.043 parts of bismastris (2-ethylhexanoate) (Neostan U-600, manufactured by Nitto Kasei Co., Ltd.) was added and the mixture was stirred. Once the exothermic reaction subsided, the reaction temperature was set to 50°C and the mixture was stirred for 3 hours to obtain an ethyl acetate solution (50% by mass) of polyhydric isocyanate compound (1).

[0377] [ka]

[0378] -Preparation of microgels- The oil phase and aqueous phase components listed below were mixed and emulsified using a homogenizer at 12,000 rpm for 10 minutes. The resulting emulsion was stirred at 45°C for 4 hours, then 5.20 g of a 10% by mass aqueous solution of 1,8-diazabicyclo[5.4.0]undec-7-en-octylate (U-CAT SA102, manufactured by Sunapro Co., Ltd.) was added, stirred at room temperature for 30 minutes, and allowed to stand at 45°C for 24 hours. The solid content concentration was adjusted to 20% by mass with distilled water to obtain an aqueous dispersion of microgel (polymer particles R-1). The average particle size was measured by light scattering and found to be 0.20 μm.

[0379] ~Oil phase components~ (Component 1) Ethyl acetate: 12.0 parts (Component 2) An adduct prepared by adding trimethylolpropane (6 molar equivalents) and xylene diisocyanate (18 molar equivalents), to which terminally methylated polyoxyethylene (1 molar equivalent, number of oxyethylene units repeated: 90) is added (50% by mass ethyl acetate solution, manufactured by Mitsui Chemicals, Inc.): 3.76 parts (Component 3) Polyhydric isocyanate compound (1) (as a 50% by mass ethyl acetate solution): 15.0 parts (Component 4) 65% by mass ethyl acetate solution of dipentaerythritol pentaacrylate (SR-399, manufactured by Sartomer): 11.54 parts (Component 5) 10% ethyl acetate solution of sulfonate-type surfactant (Pionin A-41-C, manufactured by Takemoto Oil Co., Ltd.): 4.42 parts

[0380] ~Aqueous phase components~ Distilled water: 46.87 parts

[0381] <Formation of the outermost layer> The outermost coating solution 2 described below was applied in a bar onto the image recording layer and dried in an oven at 120°C for 60 seconds, resulting in a dry coating amount of 0.2 g / m². 2 It formed the outermost layer.

[0382] -Preparation of the outermost coating solution 2- The outermost coating solution 2 contained the following components in the following mass ratios and was prepared with deionized water to have a solid content of 6% by mass. The amounts added below indicate the solid content. Hydrophilic polymer WP-6: 40 parts Hydrophobic polymer L-3: 40 parts Surfactant F-1: 5 parts

[0383] [Hydrophilic polymer] WP-6: Cellulose, manufactured by Shin-Etsu Chemical Co., Ltd. (Metholose SM04)

[0384] [Hydrophobic polymer] L-3: Styrene-acrylic resin, manufactured by Nippon Paint Industrial Coatings Co., Ltd., FS-102

[0385] [Surfactants] F-1: Anionic surfactant, Rapisol A-80, manufactured by NOF Corporation.

[0386] [Preparation of printing plate 3] The support and the undercoat layer were formed in the same manner as for printing plate 1.

[0387] <Formation of the image recording layer> Apply the image recording layer coating liquid 3 shown below to the undercoat layer using a bar, and dry in an oven at 120°C for 40 seconds, resulting in a dry coating amount of 1.0 g / m². 2 An image recording layer was formed.

[0388] -Image recording layer coating liquid 3- Polymer dispersion: 0.675 parts Hydroxypropyl methylcellulose: 0.400 parts Monomer 1:0.036 parts Monomer 2:0.115 parts Monomer 3:0.087 parts Infrared absorber 1:0.028 parts Surfactant 1:0.045 parts Iodonium salt 1:0.073 parts Iodonium salt 2:0.053 parts Leuco-2 dye: 0.040 parts Phenothiazine: 0.005 parts 1-Propanol: 2.6 parts 2-Butanone: 3.5 parts 1-Methoxy-2-propanol: 0.92 parts δ-Butyrolactone: 0.10 parts Wednesday: 1.16 parts

[0389] Polymer dispersion: The polymer dispersion was prepared according to Example 10 of European Patent Application Publication No. 1,765,593 and used as a 23.5% by mass dispersion of n-propanol / water in an 80:20 mass ratio. Hydroxypropyl methylcellulose: 5% aqueous solution. 30% is methoxylated and 10% is hydroxypropoxylated. At 20°C, the viscosity of a 2% by mass aqueous solution is 5 mPa·s. Monomer 1: The following compound

[0390] [ka]

[0391] Monomer 2: The following compound

[0392] [ka]

[0393] Monomer 3: The following compound

[0394] [ka]

[0395] Infrared absorber 1: The following compound

[0396] [ka]

[0397] Surfactant 1: BYK302 manufactured by Byk Chemie was used as a 25% by mass solution in 1-methoxy-2-propanol. Iodonium salt 1: The following compounds

[0398] [ka]

[0399] Iodonium salt 2: The following compounds

[0400] [ka]

[0401] Leuco-2: The following compound

[0402] [ka]

[0403] Phenothiazine:: The following compounds

[0404] [ka]

[0405] [Preparation of printing plate 4] - Preparation of support 3: (EG nitrate + EG hydrochloride) - <Manufacturing of aluminum supports> A support for lithographic printing plates was manufactured by subjecting a 0.3 mm thick aluminum alloy plate of material 1S to the following treatment. Water washing was performed between all treatment steps, and after water washing, the liquid was removed using a nip roller.

[0406] <Alkaline etching treatment> An aluminum plate was etched by spraying an aqueous solution of caustic soda with a concentration of 26% by mass and an aluminum ion concentration of 6.5% by mass onto it using a spray tube at a temperature of 70°C. Afterward, it was rinsed with water using a spray. The amount of aluminum dissolved was 5 g / m². 2 That was the case.

[0407] <Desmat treatment in acidic aqueous solution> Next, a desmatt treatment was performed in an aqueous nitric acid solution. The aqueous nitric acid solution used for the desmatt treatment was the waste liquid from the electrochemical surface roughening process in the next step. The temperature of the solution was 50°C. The desmatt solution was sprayed onto the surface and the desmatt treatment was performed for 3 seconds.

[0408] <Electrochemical surface roughening treatment> Electrochemical surface roughening was continuously performed using a 60 Hz AC voltage with nitric acid electrolysis. The electrolyte used was an aqueous solution of 10.4 g / L nitric acid at 35°C, to which aluminum nitrate was added to adjust the aluminum ion concentration to 4.5 g / L. The AC power waveform is shown in Figure 4, with a current value travel time tp from zero to peak of 0.8 msec, a duty cycle of 1:1, and a trapezoidal rectangular wave AC. Electrochemical surface roughening was performed using a carbon electrode as the counter electrode. Ferrite was used as the auxiliary anode. The electrolytic cell shown in Figure 5 was used. The current density was 30 A / dm² (average current value). 2 5% of the current flowing from the power supply was diverted to the auxiliary anode. Electrical quantity (C / dm 2 ) is the total amount of electricity when the aluminum plate is at anode, which is 205 C / dm 2 That was the case. Afterwards, it was rinsed with water using a spray bottle.

[0409] <Alkaline etching treatment> The aluminum plate obtained above was etched by spraying an aqueous solution of caustic soda with a concentration of 5% by mass of caustic soda and an aluminum ion concentration of 0.5% by mass onto it using a spray tube at a temperature of 50°C. Afterward, it was rinsed with water using a spray. The amount of aluminum dissolved was 0.2 g / m². 2 That was the case.

[0410] <Desmat treatment using acidic aqueous solution> Next, a desmatt treatment was performed in an aqueous sulfuric acid solution. The aqueous sulfuric acid solution used for the desmatt treatment had a sulfuric acid concentration of 170 g / L and an aluminum ion concentration of 5 g / L. The temperature of the solution was 30°C. The desmatt solution was sprayed and the desmatt treatment was performed for 3 seconds.

[0411] <Electrochemical surface roughening treatment> A continuous electrochemical surface roughening treatment was performed using hydrochloric acid electrolysis with an AC voltage of 60 Hz. The electrolyte used was an aqueous solution of 5.0 g / L hydrochloric acid at a liquid temperature of 35°C, to which aluminum chloride was added to adjust the aluminum ion concentration to 4.5 g / L. The AC power waveform is shown in Figure 4, with a current value tp of 0.8 msec from zero to peak, a duty cycle of 1:1, and a trapezoidal rectangular wave AC. Electrochemical surface roughening was performed using a carbon electrode as the counter electrode. A ferrite anode was used as the auxiliary anode. The electrolytic cell shown in Figure 5 was used. The current density was 25 A / dm² (average current value). 2 Therefore, the amount of electricity in hydrochloric acid electrolysis (C / dm 2 ) is the total amount of electricity when the aluminum plate is at anode, which is 60 C / dm 2 That was the case. Afterwards, it was rinsed with water using a spray bottle.

[0412] <Alkaline etching treatment> The aluminum plate obtained above was etched by spraying an aqueous solution of caustic soda with a concentration of 5% by mass of caustic soda and an aluminum ion concentration of 0.5% by mass onto it using a spray tube at a temperature of 50°C. Afterward, it was rinsed with water using a spray. The amount of aluminum dissolved was 0.1 g / m².2 That was the case.

[0413] <Desmat treatment using acidic aqueous solution> Next, a desmatt treatment was performed in an aqueous sulfuric acid solution. Specifically, waste liquid generated in the anodizing process (5 g / L of aluminum ions dissolved in 170 g / L aqueous sulfuric acid solution) was used, and the desmatt treatment was performed at a liquid temperature of 35°C for 4 seconds. The desmatt solution was sprayed and the desmatt treatment was performed for 3 seconds.

[0414] <First stage: Anodizing treatment> The first stage of anodic oxidation was performed using a DC electrolytic anodic oxidation apparatus with the structure shown in Figure 3. The sulfuric acid concentration was 170 g / L, aluminum ion concentration was 5 g / L, the solution temperature was 52°C, and the current density was 30 A / dm². 2 Anodizing treatment was performed under specified conditions to form an anodic oxide film with a thickness of 110 nm. In the anodic oxidation treatment apparatus 610 shown in Figure 3, the aluminum plate 616 is transported as indicated by the arrows in Figure 3. In the power supply tank 612 where the electrolyte 618 is stored, the aluminum plate 616 is charged positively by the power supply electrode 620. Then, in the power supply tank 612, the aluminum plate 616 is transported upward by the roller 622, its direction is changed downward by the nip roller 624, and then it is transported toward the electrolytic treatment tank 614 where the electrolyte 626 is stored, and its direction is changed horizontally by the roller 628. Next, the aluminum plate 616 is charged negatively by the electrolytic electrode 630, so that an anodic oxide film is formed on its surface, and the aluminum plate 616 that has left the electrolytic treatment tank 614 is transported to the next process. In the anodizing apparatus 610, a direction-changing mechanism is formed by rollers 622, nip rollers 624, and rollers 628, and the aluminum plate 616 is conveyed in a mountain shape and an inverted U shape by rollers 622, nip rollers 624, and rollers 628 in the space between the power supply tank 612 and the electrolytic treatment tank 614. The power supply electrode 620 and the electrolytic electrode 630 are connected to a DC power supply 634. A tank wall 632 is positioned between the power supply tank 612 and the electrolytic treatment tank 614.

[0415] <Pore-wide processing> The anodized aluminum plate described above was immersed for 2.7 seconds in a caustic soda aqueous solution at a temperature of 40°C, with a caustic soda concentration of 5% by mass and an aluminum ion concentration of 0.5% by mass, to perform a pore widening treatment. After that, it was rinsed with water using a spray.

[0416] <Second stage: Anodizing treatment> The second stage of anodic oxidation was performed using a DC electrolytic anodic oxidation apparatus with the structure shown in Figure 3. The sulfuric acid concentration was 170 g / L, aluminum ion concentration was 5 g / L, the solution temperature was 52°C, and the current density was 25 A / dm². 2 An anodized coating with a thickness of 900 nm was formed by performing an anodized treatment under specified conditions, and an aluminum support (support 3) was fabricated.

[0417] <Formation of the undercoat layer> On the support 3, the undercoat coating liquid 1 with the above composition is applied at a dry coating rate of 0.1 g / m². 2 The coat was applied in this manner to form a base coat layer.

[0418] <Formation of the image recording layer> Apply the image recording layer coating liquid 4 shown below to the undercoat layer using a bar, and dry in an oven at 120°C for 40 seconds, resulting in a dry coating amount of 1.0 g / m². 2 An image recording layer was formed.

[0419] -Image recording layer coating liquid 4- Infrared absorber (IR Dye-5): 0.0400 parts Leuco-3 dye: 0.0200 parts Leuco-1 dye: 0.0200 parts Electron-accepting polymerization initiator (Int-1): 0.1090 parts Electron-donating polymerization initiator (B-1 above): 0.0250 parts Polymerizable compound (see M-5 below): 0.4714 parts Anionic surfactant (A-1 above): 0.0400 parts Fluorine-based surfactant (W-1 above): 0.0042 parts 2-Butanone: 4.3551 parts 1-Methoxy-2-propanol: 3.9260 parts Methanol: 2.6947 parts Polymer particles R: 2.3256 parts

[0420] Leuco-1 and 3: The following compounds

[0421] [ka]

[0422] Int-1: The following compound, HOMO energy level -6.70 eV, LUMO energy level -3.08 eV

[0423] [ka]

[0424] <Synthesis method for polymerizable compound (M-5)> A mixed solution of Takenate D-160N (polyisocyanate trimethylolpropane adduct, manufactured by Mitsui Chemicals, Inc., 4.7 parts), Arronix M-403 (manufactured by Toagosei Co., Ltd., in an amount that results in a 1:1 ratio between the NCO value of Takenate D-160N and the hydroxyl value of Arronix M-403), t-butylbenzoquinone (0.02 parts), and methyl ethyl ketone (11.5 parts) was heated to 65°C. Neostan U-600 (bismuth-based polycondensation catalyst, manufactured by Nitto Kasei Co., Ltd., 0.11 parts) was added to the reaction solution and heated at 65°C for 4 hours. The reaction solution was cooled to room temperature (25°C), and methyl ethyl ketone was added to synthesize a urethane acrylate (M-5) solution with a solid content of 50% by mass.

[0425] <Preparation of polymer particles R> -Preparation of oil phase components- 6.66 g of WANNATE® PM-200 (polyfunctional isocyanate compound: manufactured by Manka Chemical Co., Ltd.), 5.46 g of Takenate® D-116N (a 50% by mass ethyl acetate solution of an adduct of trimethylolpropane (TMP), m-xylylene diisocyanate (XDI), and polyethylene glycol monomethyl ether (EO90) (structure shown below): manufactured by Mitsui Chemicals, Inc.), 11.24 g of a 65% by mass ethyl acetate solution of SR399 (dipentaerythritol pentaacrylate: manufactured by Sartomer Co., Ltd.), 14.47 g of ethyl acetate, and 0.45 g of Pionin® A-41-C (manufactured by Takemoto Oil & Fat Co., Ltd.) were mixed and stirred at room temperature (25°C) for 15 minutes to obtain the oil phase component.

[0426] [ka]

[0427] -Preparation of aqueous phase components- 47.2g of distilled water was prepared as the aqueous phase component.

[0428] -Microcapsule Formation Process- The oil phase component was added to the aqueous phase component and mixed. The resulting mixture was then emulsified using a homogenizer at 12,000 rpm for 16 minutes to obtain an emulsion. 16.8 g of distilled water was added to the resulting emulsion, and the resulting liquid was stirred at room temperature for 180 minutes. Next, the stirred liquid was heated to 45°C and stirred for 5 hours while maintaining the liquid temperature at 45°C to remove ethyl acetate from the liquid. The solid content concentration was adjusted to 20% by mass with distilled water to obtain an aqueous dispersion of polymer particles R. The volume-average particle size of R was measured to be 165 nm using a laser diffraction / scattering particle size distribution analyzer LA-920 (manufactured by Horiba, Ltd.).

[0429] <Formation of the outermost layer> The outermost coating solution 3 described below was applied in a bar onto the image recording layer, and then oven-dried at 120°C for 60 seconds, resulting in a dry coating amount of 0.05 g / m². 2 The outermost layer was formed, and the printing plate 4 was prepared.

[0430] -Outermost layer coating liquid 3- Inorganic layered compound dispersion (1) (see below): 0.5625 parts Hydrophilic polymer (1) (20% aqueous solution of the following compound): 0.0825 parts Metroze SM04 (methylcellulose, manufactured by Shin-Etsu Chemical Co., Ltd., degree of methoxy substitution = 1.8): 0.0125 parts Rapisol A-80 (anionic surfactant, manufactured by NOF Corporation, 80% aqueous solution): 0.007 parts Ion-exchanged water: 4.3355 parts

[0431] [ka]

[0432] The method for preparing the inorganic layered compound dispersion (1) used in the protective layer coating solution described above is shown below. -Preparation of inorganic layered compound dispersion (1)- 193.6 parts of deionized water were mixed with 6.4 parts of synthetic mica (Somasif ME-100, manufactured by Coop Chemical Co., Ltd.), and the mixture was dispersed using a homogenizer until the average particle size (laser scattering method) reached 3 μm. The aspect ratio of the resulting dispersed particles was 100 or greater.

[0433] [Preparation of printing plate 5] A printing plate 5 was prepared in the same manner as the printing plate 4, except that the image recording layer coating liquid 4 was changed to the image recording layer coating liquid 5 shown below, and the outermost layer was formed as shown below.

[0434] -Image recording layer coating liquid 5- Infrared absorber (IR Dye-1 below): 0.0120 parts Infrared absorbent (IR Dye-5): 0.0250 parts Leuco dye (Leuco-3): 0.0200 parts Leuco dye (Leuco-1): 0.0200 parts Electron-accepting polymerization initiator (Int-1 above): 0.1090 parts Electron-donating polymerization initiator (B-1 above): 0.0250 parts Polymerizable compound (M-5 above): 0.4714 parts Anionic surfactant (A-1 above): 0.0400 parts Fluorine-based surfactant (W-1 above): 0.0042 parts 2-Butanone: 4.3551 parts 1-Methoxy-2-propanol: 3.6383 parts Methanol: 2.6947 parts The above polymer particles R: 2.6163 parts

[0435] IR Dye-1: The following compounds

[0436] [ka]

[0437] <Formation of the outermost layer> The outermost coating solution 4 described below was applied in a bar onto the image recording layer, and then oven-dried at 120°C for 60 seconds, resulting in a dry coating amount of 0.05 g / m². 2 The outermost layer was formed, and a lithographic printing plate was created.

[0438] -Outermost layer coating liquid 4- The above inorganic layered compound dispersion (1): 0.5625 parts Hydrophilic polymer (1) (20% aqueous solution of the above compound): 0.0825 parts Metroze SM04 (methylcellulose, manufactured by Shin-Etsu Chemical Co., Ltd., degree of methoxy substitution = 1.8): 0.0250 parts Rapisol A-80 (anionic surfactant, manufactured by NOF Corporation, 80% aqueous solution): 0.007 parts Ion-exchanged water: 43,300 units

[0439] [Original printing plate 6] - Preparation of support 4: (EG hydrochloric acid) - <<Alkaline etching treatment>>> An aluminum plate was etched by spraying it with a caustic soda aqueous solution containing 26% by mass of caustic soda and 6.5% by mass of aluminum ions at a temperature of 70°C, thereby roughening the surface of the aluminum plate with sandblasting. Afterward, it was rinsed with water by spraying. The amount of aluminum dissolved in the surface to be subsequently subjected to electrochemical roughening treatment was 5 g / m². 2 That was the case.

[0440] <<Desmatt treatment using acidic aqueous solution>> Next, a desmatt treatment was performed using an acidic aqueous solution. Specifically, the acidic aqueous solution was sprayed onto the aluminum plate and desmatt treatment was performed for 3 seconds. The acidic aqueous solution used for the desmatt treatment was a 150 g / L sulfuric acid solution. The temperature of the solution was 30°C.

[0441] <<Electrochemical surface roughening treatment (EG hydrochloric acid)>> Next, electrochemical surface roughening treatment was performed using hydrochloric acid electrolyte and alternating current. The hydrochloric acid concentration was 13 g / L, the aluminum concentration was 15 g / L, and the sulfuric acid concentration was 1 g / L. The aluminum ion concentration was adjusted by adding aluminum chloride. The waveform of the alternating current was a sine wave with symmetrical positive and negative waveforms, the frequency was 50 Hz, the anode reaction time and cathode reaction time in one cycle of the alternating current were 1:1, and a carbon electrode was used as the counter electrode to the aluminum plate. After that, a water washing treatment was performed.

[0442] <<Alkaline etching treatment>> An aluminum plate that has undergone electrochemical roughening treatment is subjected to an aqueous solution of caustic soda with a concentration of 5% by mass of caustic soda and an aluminum ion concentration of 0.5% by mass, at the liquid temperature listed in Table 1, and the amount of aluminum etched (g / m²) is determined. 2 The surface was adjusted to achieve the desired result, and etching was performed by spraying. The amount of aluminum etched from the electrochemically roughened surface was controlled by changing the etching temperature. After that, a water rinse was performed.

[0443] <<Desmatt treatment using acidic aqueous solution>> Next, a desmatt treatment was performed using an acidic aqueous solution. Specifically, the acidic aqueous solution was sprayed onto the aluminum plate and desmatt treatment was performed for 3 seconds. The acidic aqueous solution used for the desmatt treatment had a sulfuric acid concentration of 170 g / L and an aluminum ion concentration of 5 g / L. The temperature of the solution was 35°C.

[0444] <<First stage: Anodizing treatment (AD treatment)>> The first stage of anodic oxidation treatment was performed using a DC electrolytic anodic oxidation apparatus to form an anodic oxide film with a thickness of 110 nm.

[0445] <<Pore-wide treatment>> The anodized aluminum plate described above was immersed for 2.7 seconds in a caustic soda aqueous solution at 40°C with a caustic soda concentration of 5% by mass and an aluminum ion concentration of 0.5% by mass, and subjected to pore widening treatment. After that, it was rinsed with water using a spray.

[0446] <<Second stage: Anodizing treatment>> A second-stage anodic oxidation treatment was performed using a DC electrolytic anodic oxidation apparatus to form an anodic oxide film with a thickness of 1,500 nm, thereby fabricating support material 4.

[0447] <Formation of the undercoat layer> On the support shown in Table 1, apply primer coating liquid 1 with the following composition at a dry coating rate of 0.1 g / m². 2 The coat was applied in this manner to form a base coat layer.

[0448] <Formation of the image recording layer> The above image recording layer coating liquid 3 was applied in a bar onto the undercoat layer and then oven-dried at 50°C for 60 seconds, resulting in a dry coating amount of 0.9 g / m². 2 An image recording layer was formed, and a printing plate 6 was prepared.

[0449] (Examples 1-11 and Comparative Examples 1-4) <Preparation of the treatment solution> Each component listed in Table 5 was mixed in the amounts specified in Table 5 to prepare the respective processing solutions A to O (plate surface cleaning agents for on-press developing lithographic printing plates) for Examples 1 to 11 and Comparative Examples 1 to 4. Note that the units of the numerical values ​​in each component column listed in Table 5 are parts by mass.

[0450] [Table 5]

[0451] <Method for evaluating scratch and stain resistance> Each printing plate (1-6) was prepared according to the following conditions. Then, using a scratch test machine (manufactured by Shinto Kagaku Co., Ltd.), scratches were made on each plate by changing the load from 10g to 100g in 10g increments with a sapphire needle (0.1mm diameter). On-press development was then performed under the following printing conditions, and 100 copies were printed. Afterward, the scratch and stain recovery test described below was performed, followed by another 100 prints. The scratches and stains were then visually evaluated, and the scratch and stain recovery performance (scratch and stain suppression) was assessed according to the following evaluation criteria. A: Compared to no treatment, the recovery of scratches and stains is better. B: Compared to no treatment, the recovery of scratches and stains is slightly better. C: Compared to the case without treatment, scratches and stains do not recover.

[0452] -Plate making conditions- A thermal laser setter (CREO Quantum) was used to expose a 20mm wide solid image onto the printing plate. After exposure was complete, scratches were made on the unexposed areas of the plate using a scratch test machine. The plate was then mounted on a printing press, dampening solution and ink were supplied, and on-press development was performed. The following printing tests were then conducted.

[0453] -Printing conditions- Printing press: Heidelberg SX-74 Ink: DIC Corporation Oil-based process red ink Fusion G Red Dampening solution: PRESSMAX S-Z1 manufactured by Fujifilm Corporation was used, diluted to 3%.

[0454] -Scratch and stain recovery test- After the printing plate had been developed on the press, the scratched areas were treated using either Test 1 or Test 2 below, printing was resumed, and the recovery rate of scratches and stains (scratch and stain suppression rate) was evaluated. Test 1: Using a cloth soaked in the treatment solution used in each example, rub the scratched area of ​​the printed plate back and forth five times. Test 2: First, use a cloth soaked in the treatment solution L from Comparative Example 1 to rub the scratched area of ​​the printed plate back and forth five times. Then, use a cloth soaked in the treatment solution used in each example to rub the same area of ​​the scratched area of ​​the printed plate back and forth five times.

[0455] <Stop stain evaluation method> After preparing each of the printing plates 1-6 according to the conditions below, they were mounted on the printing press, developed on-press, and 100 copies were printed. After printing 100 copies, I stopped the printing press and removed the printing plate. The treatment solution was soaked into a cloth and used to wipe the printing plate surface five times. After that, the plate was left for one hour under conditions of 25°C and 70% RH. After one hour, the unattended printing plate was reattached to the printing press, and 100 copies were printed. The level of smudges on the 30th print was evaluated according to the following criteria. A: Has a stain-inhibiting effect. B: Has a slight stain-inhibiting effect. C: No stain-inhibiting effect

[0456] -Plate making conditions- A thermal laser setter (CREO Quantum) was used to expose a 200mm wide 30% to 100% (200 lpi) gradient mesh pattern. The exposed plate was mounted on the printing press, dampening solution and ink were supplied, and after the on-press development was completed, a printing test was conducted according to the evaluation method described above.

[0457] -Printing conditions- Printing press: Heidelberg SX-74 Ink: DIC Corporation Oil-based process red ink Fusion G Red Dampening solution: PRESSMAX S-S1 manufactured by Fujifilm Corporation was used, diluted to 3%.

[0458] The evaluation results are summarized in Table 6.

[0459] [Table 6]

[0460] Furthermore, in Examples 1 to 11, using a sponge instead of cloth yielded the same level of effectiveness as using cloth.

[0461] The results shown in Table 6 indicate that the lithographic printing method according to the example is superior in scratch and stain suppression compared to the lithographic printing method according to the comparative example. Furthermore, it can be seen that the lithographic printing method according to the embodiment also exhibits excellent ability to suppress smudging that occurs when printing is temporarily paused, so-called stop smudging.

[0462] The disclosure of Japanese Patent Application No. 2021-158311, filed on 28 September 2021, is incorporated herein by reference in its entirety. All documents, patent applications, and technical standards described herein are incorporated by reference to the same extent as if each individual document, patent application, and technical standard were specifically and individually noted to be incorporated by reference. [Explanation of Symbols]

[0463] 12a,12b: Aluminum support, 14: Undercoat layer, 16: Image recording layer, 18: Aluminum plate, 20a,20b: Anodized film, 22a,22b: Micropore, 24: Large diameter hole, 26: Small diameter hole, D: Depth of large diameter hole, 50: Main electrolytic cell, 51: AC power supply, 52: Radial drum roller, 53a,53b: Main electrode, 54: Electrolyte supply port, 55: Electrolyte, 56: Auxiliary anode, 60: Auxiliary anode tank, W: Aluminum plate, S: Electrolyte supply direction, Ex: Electrolyte discharge direction, 610: Anodizing treatment apparatus, 612: 614: Power supply tank, 616: Electrolytic treatment tank, 618,26: Electrolyte, 620: Power supply electrode, 622,628: Roller, 624: Nip roller, 630: Electrolytic electrode, 632: Tank wall, 634: DC power supply, ta: Anode reaction time, tc: Cathode reaction time, tp: Time from 0 to peak current, Ia: Peak current on the anode cycle side, Ic: Peak current on the cathode cycle side, AA: Current for the anode reaction of the aluminum plate, CA: Current for the cathode reaction of the aluminum plate

Claims

1. A process of preparing a lithographic printing plate master having an image recording layer containing an infrared absorbent on a support, A step of exposing the aforementioned lithographic printing plate to an image, A step of developing at least the non-image portion of the image recording layer by supplying at least dampening water to the exposed lithographic printing plate, and The process includes cleaning the surface of the developed lithographic printing plate using a plate cleaning agent, The aforementioned plate cleaning agent contains 3.0% by mass or more of a solvent having a ClogP value greater than -1.5 and 2.5 or less, relative to the total mass of the plate cleaning agent. The solvent having a ClogP value greater than -1.5 and less than or equal to 2.5 contains a compound represented by the following formula (A). Lithographic printing method. 【Chemistry 1】 In formula (A), R 1 R represents a linear alkyl group having 1 to 5 carbon atoms or a branched alkyl group having 3 to 5 carbon atoms. 2 Each of these independently represents either a hydrogen atom or a methyl group, and m represents an integer from 1 to 5.

2. A process of preparing a lithographic printing plate master having an image recording layer containing an infrared absorbent on a support, A step of exposing the aforementioned lithographic printing plate to an image, A step of developing at least the non-image portion of the image recording layer by supplying at least dampening water to the exposed lithographic printing plate, and The process includes cleaning the surface of the developed lithographic printing plate using a plate cleaning agent, The aforementioned plate cleaning agent contains 3.0% by mass or more of a solvent having a ClogP value of 0.4 to 1.2, relative to the total mass of the plate cleaning agent. The solvent having a ClogP value of 0.4 to 1.2 is at least one selected from the group consisting of propylene glycol-n-butyl ether, ethylene glycol mono-t-butyl ether, diethylene glycol-n-butyl ether, ethylene glycol mono-n-butyl ether, propylene glycol-t-butyl ether, and Solfit. Lithographic printing method.

3. The lithographic printing method according to claim 1, wherein the developing step is a step of mounting the exposed lithographic printing plate to a printing press and developing at least the non-image portion of the image recording layer by supplying at least dampening water on the printing press.

4. The lithographic printing method according to any one of claims 1 to 3, wherein the plate surface cleaning agent further contains at least one selected from the group consisting of organic acids and salts thereof.

5. The lithographic printing method according to claim 4, wherein the total content of the organic acid and its salt is 0.002 moles or more in terms of organic acid per 100 g of the total amount of the plate cleaning agent.

6. The lithographic printing method according to claim 1 or claim 2, wherein the plate surface cleaning agent further contains at least one selected from the group consisting of inorganic acids and salts thereof.

7. The lithographic printing method according to claim 6, wherein the total content of the inorganic acid and its salt is 0.002 moles or more in terms of inorganic acid per 100 g of the total amount of the plate cleaning agent.

8. The lithographic printing method according to claim 1 or claim 2, wherein the plate surface cleaning agent further contains water and is a single-phase aqueous solution.

9. The lithographic printing method according to claim 8, wherein the water content is 90% by mass or less relative to the total mass of the plate cleaning agent.

10. The lithographic printing method according to claim 1 or claim 2, further comprising a step of treating the printing plate surface with a two-phase solution containing water and a hydrocarbon solvent before, during, or after the cleaning step.

11. The cleaning agent contains at least 3.0% by mass of a solvent with a ClogP value greater than -1.5 and 2.5 or less, relative to the total mass of the plate surface cleaning agent. The solvent having a ClogP value greater than -1.5 and less than or equal to 2.5 contains a compound represented by the following formula (A). A plate cleaning agent for on-press developing type lithographic printing plates. 【Chemistry 2】 In formula (A), R 1 R represents a linear alkyl group having 1 to 5 carbon atoms or a branched alkyl group having 3 to 5 carbon atoms. 2 Each of these independently represents either a hydrogen atom or a methyl group, and m represents an integer from 1 to 5.

12. The solvent has a ClogP value of 0.4 to 1.2 and is contained in an amount of 3.0% by mass or more relative to the total mass of the plate cleaning agent. The solvent having a ClogP value of 0.4 to 1.2 is at least one selected from the group consisting of propylene glycol-n-butyl ether, ethylene glycol mono-t-butyl ether, diethylene glycol-n-butyl ether, ethylene glycol mono-n-butyl ether, propylene glycol-t-butyl ether, and Solfit. A plate cleaning agent for on-press developing type lithographic printing plates.

13. The plate surface cleaning agent for on-press developing type lithographic printing plates according to claim 11 or claim 12, wherein the plate surface cleaning agent further contains at least one selected from the group consisting of organic acids and salts thereof.

14. The plate cleaning agent for on-press developing type lithographic printing plates according to claim 13, wherein the total content of the organic acid and its salt is 0.002 moles or more in terms of organic acid per 100 g of the total amount of the plate cleaning agent.

15. The plate surface cleaning agent for on-press developing type lithographic printing plates according to claim 11 or claim 12, wherein the plate surface cleaning agent further contains at least one selected from the group consisting of inorganic acids and salts thereof.

16. The plate cleaning agent for on-press developing type lithographic printing plates according to claim 15, wherein the total content of the inorganic acid and its salt is 0.002 moles or more in terms of inorganic acid per 100 g of the total amount of the plate cleaning agent.

17. The plate surface cleaning agent for on-press developing type lithographic printing plates according to claim 11 or claim 12, wherein the plate surface cleaning agent further contains water and is a single-phase aqueous solution.

18. The plate surface cleaning agent for on-press developing type lithographic printing plates according to claim 17, wherein the water content is 90% by mass or less with respect to the total mass of the plate surface cleaning agent.

Citation Information

Patent Citations

  • Paste printing plate washing agent for planographic printing

    JP1994155959A

  • Detergent for surface of planographic printing plate

    JP1994344680A

  • Plate surface cleaning agent for lithographic printing plate

    JP1998203043A

  • Finishing solution for photosensitive planographic printing plate

    JP1999258823A

  • Plate face cleaning agent for lithographic printing plate

    JP2000229486A